Formation and geological significance of carbonate firmgrounds and hardgrounds on the Rio Grande Rise (South Atlantic) - Alexandre Henrique Ferraz; Rafael Oliveira Silva; Pedro Walfir Martins e Souza Neto; Carina Ulsen; Lucy Gomes Sant'Anna; Paulo César Fonseca Giannini; Eugenio Pires Frazão; Victor Hugo Rocha Lopes; Luigi Jovane; Bramley J. Murton; Christian Millo (Sedimentary Geology, 2026)

Polysaccharide hydrogels as immunologically active vaccine depots for cancer immunotherapy - Melissa J. Borralho; Maria João Barreira; Eduardo Ferreira; José Alexandre Ferreira (Carbohydrate Polymers, 2026)

Sublethal toxicity of selenium nanoparticles in zebrafish early life stages: biochemical and behavioral responses - Pearl Ofoegbu; Rita Duarte; Soraia Almeida; Alexandre Marques; David Daniel; Luís Barros; Ricardo J. B. Pinto; Victor Galhano; Bruno Nunes (Environmental Science and Pollution Research, 2026)

Sub-inhibitory concentrations of antibiotics modulate antimicrobial resistance fate in a biofilm-grazer system - Alexandre J. Thibodeau; Florence Mouchet; Van Xuan Nguyen; Thomas Moura; Marion Vivant; Eric Pinelli; Maialen Barret (Environmental Pollution, 2026)

Flow responses to the discharge of a pair of competing tributaries in a tropical estuary - Juárez Braulio; Elisa Villegas-Rodríguez; J. Mauro Vargas-Hernández; Arnoldo Valle-Levinson; Alexandre Tisseaux-Navarro; Isaac Rodríguez-Padilla (Estuarine, Coastal and Shelf Science, 2026)

Effects of soybean oil and rumen-protected lipid sources on milk production and fatty acid profile in lactating ewes - Adrielly Lais A. da Silva; Matheus Sousa de P. Carlis; Paulo César.G. Dias Junior; Isabela J. dos Santos; Rhaíssa G. de Assis; Jamile H. Comelli; Daniel M. Polizel; Janaina S. Biava; Bruno I. Cappellozza; Alexandre V. Pires; Evandro M. Ferreira (Animal Feed Science and Technology, 2026)

Seafloor erosional processes within the Rio Grande Rise: Integrated results from past scientific expeditions - Gabriel Tagliaro; Alexandre Henrique Ferraz; Raylla Souza Silva; Christian Millo; Renata Regina Constantino; Bramley J. Murton; Luigi Jovane (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

Phenotypic variability of hydraulic residual conductance and its temperature sensitivity in Abies alba Mill - Stéphane Herbette; Andanson Stéphane; Gonzalez Alexandre; J. Blackman Chris; Cartailler Julien; Martin Ludovic; Cochard Hervé (Trees, 2026)

Subspecies taxonomy reflects social and geographic patterns of taxonomic effort in tetrapods - Jhonny J. M. Guedes; José Alexandre F. Diniz‐Filho; André V. L. Freitas; Mario R. Moura (Conservation Biology, 2026)
Subspecies have been used in conservation biology to account for intraspecific patterns in genetic diversity, which is crucial to long‐term population viability. Although over 3200 subspecies are currently assessed by the International Union for Conservation of Nature Red List, their biological relevance remains controversial. Here, we analyzed patterns of subspecies counts across more than 33,000 tetrapod species, and using hurdle mixed‐effect models, we modeled subspecies counts as a function of biological and sociocultural factors. Our results revealed a striking decline in the description of subspecies in recent decades, driven mostly by contemporary social factors. Birds exhibited the highest number of recognized subspecies, followed by mammals and reptiles, whereas amphibians currently lack any valid subspecies. Subspecies counts also varied spatially; temperate regions had more subspecies than tropical areas on average, as well as more species whose subspecies counts differ markedly from what would be expected given their attributes. Using multivariate models, we found preserved specimen availability, species range size, and geographic discontinuity (i.e., disjunct populations) as major predictors of subspecies counts. Additionally, well‐studied and recently described species were less likely to have subspecies. Our findings suggested that subspecies recognition is shaped by complex sociocultural and research‐related contexts rather than by purely biological criteria. This misalignment risks skewing conservation priorities, highlighting the need for more evidence‐based approaches that integrate molecular, phenotypic, and geographic data for subspecies delimitation. This approach will help ensure that conservation resources are directed toward biologically meaningful units to enhance the effectiveness of conservation strategies.

Toward an integrated understanding of animal weapons - Christine W. Miller; Dominic Cram; Sarah M. Lane; Romain Boisseau; Sophia Fitzgerald; Nicole Lopez; Allen J. Moore; Christina J. Painting; Alexandre V. Palaoro; Michael Ryan; Ummat Somjee; Camille Thomas-Bulle; et al. (Trends in Ecology & Evolution, 2026)

New findings on the performance of anaerobic reactors: Ecotoxicological assessment of sublethal effects of antibiotic mixtures in wastewater on freshwater invertebrates - Gleyson B. Castro; Mateus Cottorello-Fonsêca; Tallyson T.C. de Souza; David S. Alexandre; Juliano J. Corbi (Journal of Environmental Chemical Engineering, 2026)

Potential of guava pulps treated by ohmic heating as a delivery vehicle for probiotic bacteria: stability, functional properties, and in vitro digestibility - Newton C. Santos; Raphael L.J. Almeida; Virgínia M. de A. Silva; Thalis L.B. de Lima; Ronildo P. de Sousa Júnior; Victor H. de A. Ribeiro; Yaroslávia F. Paiva; Francislaine S. dos Santos; Deyzi S. Gouveia; Rennan P. de Gusmão; Alexandre J. de M. Queiroz; Josivanda P. Gomes; et al. (International Journal of Food Microbiology, 2026)

Forest restoration enhances soil health in tropical agricultural landscapes assessed by soil management assessment framework (SMAF) across land uses and soil types - Vanêssa Lopes Faria; Helen Carla Santana Amorim; Maria Cecília Vieira Totti; Fernanda Almeida Bócoli; Junior Cesar Avanzi; Sérgio Henrique Godinho Silva; Alexandre Uezu; Amanda J. Ashworth; Gerson L. Drescher; Lara Mota Corinto; Samara Martins Barbosa; Vinícius Ferreira Fernandes; et al. (Geoderma Regional, 2026)

Correction: Wind conditions do not consistently affect large-scale movement decisions of large savanna herbivores - Sara Gomez; Melinda Boyers; Alexandre Caron; Daniel Cornelis; Henjo de Knegt; Michel de Garine-Wichatitsky; Jasper A. J. Eikelboom; J. Werner Kilian; Norman Owen-Smith; Thomas Prin; Adrian M. Shrader; Jared A. Stabach; et al. (Oecologia, 2026)

Intergroup Encounters Among Wild White-Faced Capuchins (Cebus imitator) at a Densely Populated Field Site: Insights into Frequency, Intensity, and Participation - Sarah A. Kovalaskas; Agostina Colosimo; Vasco Alexandre Martins; Juan Carlos Ordoñez; Elena Morera Saborío; Jacinta C. Beehner; Thore J. Bergman; Marcela E. Benítez (International Journal of Primatology, 2026)
Intergroup encounters (IGEs) are a major feature of social life for group-living primates, influencing access to resources, reproductive opportunities, and territory. We examined IGE frequency, intensity, and participation in a high-density population of wild white-faced capuchin monkeys ( Cebus imitator ) at the Capuchinos de Taboga research project in Guanacaste, Costa Rica, using 4 years of data on three capuchin groups (4,984 observation hours, 218 IGEs). The IGE rates at Taboga (0.044/hr) were two to four times higher than those at nearby lower-density sites and did not vary with rainfall or temperature. More than half of IGEs involved high-intensity aggression (chases or contact aggression). Ordinal logistic models showed that the number of focal group participants was a consistent predictor of escalation, with each additional participant increasing the odds of higher intensity by 1.4 times, while ecological variables had little explanatory value. Participation was more likely for older individuals, males, alphas, and when individuals were closer to the center of core use areas; males participated more than females at distances further from the center of core use areas. Females participated in 44% of IGEs, with lactating females less likely to participate than cycling or pregnant females. Our findings suggest that high population density and overlapping ranges drive frequent and aggressive IGEs at Taboga and that escalation is shaped primarily by social rather than ecological factors. These results highlight the importance of social processes in territorial defense and underscore their role in shaping intergroup conflict in areas of high population density.

Projected Impacts of Climate Change on Interactions Between Plants and Avian Frugivores Across the Americas - Alexandre J. C. Rabeau; Alex L. Pigot; Joseph A. Tobias; Matthias Schleuning (Global Ecology and Biogeography, 2026)
Aim Frugivorous birds provide crucial seed‐dispersal functions in terrestrial ecosystems. However, the impact of climate change on plant–avian frugivore interactions remains unclear due to past methodological limitations. In this study, we address this by mapping these interactions across the Americas and projecting shifts in interaction diversity under future climate scenarios. Location North, South, and Central America. Time Period Present (1980–2010) and future (2070–2100). Major Taxa Studied Frugivorous birds and fleshy‐fruited plants. Methods Using a trait‐matching framework, we estimated interaction probabilities between frugivorous birds ( n = 539 species) and fleshy‐fruited plants ( n = 3280 species) at the ecoregion level. To estimate climate impacts, we modeled how interaction probabilities will change under future scenarios based on the overlap between avian climate niches and ecoregion climates. From these probabilities, we calculated plant–frugivore interaction diversity as the effective number of avian partners for a given plant species in an ecoregion. We then used simulations to examine how avian dietary flexibility and dispersal may buffer future diversity of plant–frugivore interactions. Results Under future climate scenarios, our models projected a decline in interaction diversity across most ecoregions, especially in tropical and subtropical biomes. Simulations indicated that interaction rewiring through dietary flexibility and dispersal could partially mitigate losses of interaction diversity, particularly in tropical forests. Main Conclusions Our results suggest that the diversity of plant–frugivore interactions in the Americas will decline in response to climate change, potentially undermining the stability of seed‐dispersal functions. We also show that the resilience of this function depends on the capacity of frugivorous birds to modify their geographic ranges or dietary preferences. However, the extent to which avian dispersal and adaptation will regulate future species interactions remains unknown, highlighting the importance of maintaining high plant–frugivore interaction diversity in current assemblages to buffer ecosystems against future climatic changes, especially in the tropics.

Modelling primary production: multitude of theories, or multitude of languages? - Jozef Skákala; Shubha Sathyendranath; Yuri Artioli; Deep S. Banerjee; Heather Bouman; Robert J. W. Brewin; Momme Butenschön; Stefano Ciavatta; Stephanie Dutkiewicz; Yanna Fidai; David Ford; Grinson George; et al. (Ocean Science, 2026)
Marine primary production, converting approximately 50 Gt of inorganic carbon into organic carbon per year, is an important component of the global carbon cycle, and a major determinant of past, present and future climate. Large-scale, long-term estimates of marine primary production rely primarily on two types of models: satellite-based models that make extensive use of remote-sensing data, and ecosystem models providing numerical simulation of ecological processes embedded in general ocean circulation models. Intercomparison exercises of model outputs (both within and across the two model types) have consistently revealed high discrepancies between estimated global ocean primary production, including divergent magnitudes and even opposite trends. Model-observation comparisons are also complex, because paucity of data, differences in measurement techniques, and evolving methodologies could all lead to difficulties with the interpretation of results. These uncertainties limit the applications of primary production models (both satellite-based and ecosystem), especially in the climate context, where an important question is whether climate change will drive significant future changes in regional or global primary production. Both satellite-based and ecosystem models rely on a range of fixed model parameters, whose values need to be carefully estimated and tested. In this paper, we suggest that such model parameters represent an underappreciated but important source of inter-model differences. With the proliferation of both satellite and in situ observations of relevant variables at global scales, and the availability of powerful statistical tools such as data assimilation and machine learning, we argue that time is right to systematically examine model parameters, gaining both better insights into parameter values and how those values might vary in space and time. We argue that such spatio-temporal parameter variability can be theoretically justified for ecosystem models with complexity similar to those commonly used within Earth System Models (ESMs) in climate studies. The spatially and temporally varying parameter values could serve to unify models that are structurally different. An important aspect of this unification could be the ability to infer the spatio-temporal variability of parameters in the less complex models from the emergent behaviour of the more complex ones. This could include ecosystem model simulations of nutrients, temperature, phytoplankton classes, or vertical distributions informing satellite-based models. We conclude that better understanding of model parameter roles and integration (or inter-calibration) of different types of models could reduce discrepancies among the primary production models and improve the reliability of marine primary production projections.

Equipping the next generation of plant taxonomists: Insights and recommendations - Ana Rita G. Simões; Frederik Leliaert; Gemma L.C. Bramley; Ruth P. Clark; Rhian J. Smith; Manuel Luján; Ian Ondo; Matilda J.M. Brown; Gabriel K. Ameka; Catherine W. Lukhoba; Renata Borosova; Bente B. Klitgård; et al. (Trends in Plant Science, 2026)

Distribution and taxonomic composition of leptocephali and hydrographic structure from New Zealand to the South Equatorial Current - Michael J. Miller; Shun Watanabe; Robert Schabetsberger; Nioka Behan-Kitto; Grace F. Cawley; Niamh Smith; Alisha M. Gill; Alexandre Che-Pelicier; Juliet E. Saul; Abigail Sim; Therese C. Miller; Sajini Dissanayake; et al. (Regional Studies in Marine Science, 2026)

Species delimitation based on phylogenetic analyses of males: A case study revealing the complex evolutionary history of giraffes - Alexandre Hassanin; Eva Jullemier; Bertrand Chardonnet; Terence J. Robinson (Molecular Phylogenetics and Evolution, 2026)

Biennial survey of freshly harvested maize grain mycobiota in northeastern Spain: identification, incidence, and interaction patterns - Alexandre Vicens-Sans; Sonia Marín; Antonio J. Ramos; Jean Carlos Correia Peres Costa; Francisco Molino (International Journal of Food Microbiology, 2026)

Effects of Channel Characteristics on Wastewater Chemical Transformation in Rivers - Robert A. Newbould; D. Mark Powell; Juliet Hodges; Alexandre Teixeira; Michael J. Whelan (Water, Air, & Soil Pollution, 2026)
Microbially-mediated transformations are important for removing wastewater chemicals in rivers. In-stream degradation rates are likely to be affected by channel morphology and size because these factors determine the extent of chemical contact between the water column and the microbial community in fixed biofilms, where most microbially-mediated processes are expected to take place. We hypothesize that transformation rate constants are inversely proportional to hydraulic radius ( R : the ratio of channel cross-sectional area to wetted perimeter). Microbial transformations are also predicted to be controlled systematically by bed sediment characteristics. This will be a function of sediment surface area per unit volume (for biofilm colonisation) and hyporheic exchange. Here, we test the above hypotheses in controlled 14-day laboratory experiments, by monitoring nitrification and biodegradation in stirred tanks with three different water depths and three different sediment sizes (sand, gravel and cobbles). Transformation rate constants were inversely proportional to depth, supporting the notion that channel morphology represents a significant system-specific control. Rate constants for nitrification were highest in the gravel treatments and lowest in sand. This suggests that intermediate grain sizes simultaneously allow good biofilm colonisation and solute exchange between sediment and the water column. There was, however, little difference in biodegradation rate constants between different sediment sizes. This study highlights the need to consider geomorphology in models of chemical exposure.

Metacommunity Structure, Species Richness and Species Composition of Reef Fish Trophic Guilds Along an Extensive Latitudinal Gradient in the Tropics - Alexandre da Gama Fernandes Vieira Júnior; Steven J. Presley; Michael R. Willig; Carlos Werner Hackradt; Fabiana Cézar Félix‐Hackradt; João Lucas Leão Feitosa (Journal of Biogeography, 2026)
Aim Our goals were (1) to identify the metacommunity structure of the reef fish fauna as well as the structure of its constituent trophic guilds (invertivores, generalist carnivores, omnivores, herbivores, planktivores and piscivores); (2) to evaluate the extent to which metacommunity compartmentalization is associated with biogeographic phenomena (isolation by distance, habitat filtering, estuarine plumes): and (3) to identify whether the latent environmental gradient that structures the metacommunity is related to latitude. Location Coral reefs of the Brazilian Biogeographic Province (BBP). Time Period 1998–2022. Major Taxa Studied Reef fish. Methods We categorized the BBP into biogeographic regions defined by spatio‐environmental characteristics and analysed the distribution of fish species in 150 sites that included a variety of reef types (abiogenic, biogenic and island‐associated reefs). For the entire fauna, and for each of its constituent trophic guilds, we ordinated their site‐by‐species incidence matrix using reciprocal averaging. Thereafter, we evaluated coherence, species turnover and species boundary clumping to determine the structure of each metacommunity. To quantify whether latitudinal variation affects the latent environmental gradient that structures the metacommunity, we performed Spearman rank correlation analyses of site scores from reciprocal averaging. In addition, we used a suite of nested general additive models and hierarchical a priori analyses to explore the extent to which compositional differences between biogeographic regions contributed to the compartmentalization of metacommunities. Results In general, the metacommunity structure of the reef fish fauna is moulded by latitudinal correlates and exhibits compartmentalization (Clementsian and quasi‐Clementsian structure) with compositionally distinct compartments arising because of isolation by distance (island vs. continental reefs), habitat filtering (abiogenic vs. biogenic reefs), or the influence of estuarine plumes associated with the mouths of large rivers. Nonetheless, the number and identity of compartments differed among trophic guilds. Island and continental reefs were compositionally distinct for the entire fish fauna, as well as for invertivores and omnivores. Biogenic and abiogenic reefs were compositionally distinct for omnivores, herbivores and piscivores. Northern and eastern biogenic reefs were compositionally distinct for invertivores, omnivores and piscivores. Main Conclusions Degree of isolation (island versus continental reefs) and dispersal barriers (habitat types and estuarine plumes) likely interact to affect the pervasive compartmentalization of marine fish metacommunities in the BBP. The extent to which they operate is guild‐specific, suggesting that the nature of compartmentalization in the fauna is a composite of contributions by different guilds, especially those with high species richness.

Continental‐Scale Evidence of Farm Management Impacts on Soil Carbon - Julian Helfenstein; Nick van Dijk; Anna Edlinger; Gabriel Y. K. Moinet; Sophie Q. van Rijssel; Alexandre M. J.‐C. Wadoux; Rachel Creamer; Carmen Vazquez; Vera L. Mulder (Global Change Biology, 2026)
There are high expectations that agricultural practices can mitigate climate change and improve soil health by increasing soil organic carbon (SOC) stocks. However, existing large scale SOC monitoring treats agricultural management as a black box, meaning that observed patterns and trends cannot inform on the option space of agricultural practices to improve or deteriorate SOC stocks. Here, we combine for the first time management data from large scale systematic farm surveys ( n = 248,362 farms) and representative soil monitoring data ( n = 8834 locations) to quantify the impact of agricultural practices on three SOC metrics across all pedoclimatic zones of Europe (EU + UK): stocks, stocks relative to pedoclimatic benchmarks, and yearly change in SOC concentration. Our findings show that in arable and tree crops, but not in grasslands, management intensity is a significant contributor to SOC loss, with impact varying by soil and climate region. However, we also observed that several practices (e.g., high share of manure, organic management, and a high proportion of leys in crop rotation) demonstrated potential for increasing SOC stocks. Under a scenario where all agricultural land in Europe would be managed as that of the 10% most optimally managed farms in terms of SOC benefit, SOC stocks would increase by 1.58 Pg C across Europe (95% CI: 1.27–1.89 Pg C). Whereas under a scenario where farms are managed as the 10% least optimally managed farms, SOC would decrease by −0.92 Pg C (−1.15 to −0.68 Pg C). However, it is important to note that these estimates reflect steady‐state SOC stocks only (i.e., they do not represent the transient build‐up or loss over time, or interactions with a changing climate). This paper thus quantifies how agricultural practices influence patterns in SOC stocks at the continental scale, identifying leverage points for site‐specific policies to improve SOC stocks.

Automating Ecological and Fisheries Modelling With Agentic AI - Christopher J. Brown; Leigha R. Aitken; Richard Takyi; Alexandre Tisseaux‐Navarro (Fish and Fisheries, 2026)
Fisheries modelling requires specialist training, but the availability of suitably skilled modellers is limiting delivery of science to inform management. Agentic AI can automate computing workflows and will increasingly be used in ecological modelling. However, the quality of AI generated results is of concern because of risks of logically flawed code and inconsistent answers. Here, we tested whether a general‐purpose AI agent (Roo Code) can write computer code and interpret results to complete three common ecological and fisheries modelling workflows: (1) fitting a von Bertalanffy growth curve to data, (2) writing code and interpreting results of a generalised linear model relating fish abundance to habitat and (3) completing a yield per recruit analysis. We used replicate prompts and a structured evaluation rubric to ask if the agents' results were accurate and if responses were consistent. The agent successfully completed all three tasks in some replicates; however, accuracy varied widely across replicates. Of the large language models we tested, Claude Sonnet 4.5 had the greatest accuracy and always produced accurate responses for the simplest modelling task, but was less consistently accurate for complex tasks. All models sometimes overlooked user instructions for which methods to use. Our findings show that agents can sometimes complete ecological and fisheries modelling, but that they are not yet consistent and accurate enough to rely on for management advice. We outline prompt designs and workflows that improve reliability and discuss the importance of ensuring human oversight for credibility of modelling that is used in management.

Taxonomic uncertainty: causes, consequences, and metrics - Leila Meyer; Richard J. Ladle; Rafaela J. Trad; Annelise Frazão; Lívia Frateles; Thainá Lessa; Rafael B. Pinto; Tiago M.S. Freitas; Geiziane Tessarolo; Jhonny J.M. Guedes; Rodrigo A. Castro-Souza; Herison Medeiros; et al. (Trends in Ecology & Evolution, 2026)

Genetic structure of the shea tree (Vitellaria paradoxa C.F. Gaertn.) population and fatty acid-based selection of elite genotypes in Benin - Guillaume J. Bodjrenou; Matice Gbètoho; Fernande Honfo; Cyril J. F. Kahn; M. Eric Schranz; Paul Césaire Gnanglè; Alain Hehn; Alexandre Olry; Enoch G. Achigan-Dako (Physiology and Molecular Biology of Plants, 2026)

Wind conditions do not consistently affect large-scale movement decisions of large savanna herbivores - Sara Gomez; Melinda Boyers; Alexandre Caron; Daniel Cornelis; Henjo de Knegt; Michel de Garine-Wichatitsky; Jasper A. J. Eikelboom; J. Werner Kilian; Norman Owen-Smith; Thomas Prin; Adrian M. Shrader; Jared A. Stabach; et al. (Oecologia, 2026)

Advances in plant spatial multi-omics data analysis - Jie Yao; Alexandre P. Marand; Yinqi Bai; Robert J. Schmitz; Longjiang Fan (Trends in Plant Science, 2026)

The plant ontology of cell types - Hongyu Chen; Pu Liang; Xiaolin Lu; Shuai Jiang; Jingjing Jin; Jiaqi Cai; Yaqian Lu; Dihuai Zheng; Jie Yao; Qinjie Chu; Huixia Shou; Chengxin Fu; et al. (Molecular Plant, 2026)

Infrared spectral signatures of nucleobases in interstellar ices II: Pyrimidines - Caroline Antunes Rosa; Alexandre Bergantini; Péter Herczku; Duncan V. Mifsud; Gergő Lakatos; Sándor T.S. Kovács; Béla Sulik; Zoltán Juhász; Sergio Ioppolo; Nigel J. Mason; Claudia Lage (Life Sciences in Space Research, 2026)

Anaerobic digestion waste as a nutrient source for closed-loop alkaline cultivation of a cyanobacterial consortium - Alexandre J. Paquette; Jayne E. Rattray; Agasteswar Vadlamani; Gabrielle Scheffer; Cigdem Demirkaya; Marc Strous; Hector De la Hoz Siegler (Biomass and Bioenergy, 2026)

Orange (Citrus sinensis) essential oil as feed additive for sheep: nutrient intake and apparent digestibility, nitrogen balance, and rumen fermentation characteristics - Paulo César G. Dias Junior; Ana Carolina S. Vicente; Isabela J. dos Santos; Letícia C. B. Soares; Adrielly L. A. da Silva; Rhaissa G. de Assis; Jamile Haddad Comelli; Daniel M. Polizel; Janaina S. Biava; Diogo F. A. Costa; Alexandre V. Pires; Evandro M. Ferreira (Tropical Animal Health and Production, 2026)

Evaluating an isotopic model for tracing the geographic origin of soybeans in Brazil - Maria Gabriella da Silva Araújo; Deoclecio Jardim Amorim; Rodrigo Figueiredo Almeida; Edmar Mazzi; Ana Claudia Gama Batista; Isabela Maria Souza-Silva; Alexandre Tadeu Brunello; Gabriela Bielefeld Nardoto; Gabriel J. Bowen; Luiz Antonio Martinelli (Food Chemistry, 2026)

Correction: Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)

WABAD : A world annotated bird acoustic dataset for passive acoustic monitoring - Cristian Pérez‐Granados; Jon Morant; Kevin F. A. Darras; Oscar H. Marín‐Gómez; Irene Mendoza; Miguel A. Muñoz‐Mohedano; Eduardo Santamaría‐García; Giulia Bastianelli; Alba Márquez‐Rodríguez; Michał Budka; Gerard Bota; José M. De la Peña‐Rubio; et al. (Ecology, 2026)
Under the current global biodiversity crisis, there is a need for automated and noninvasive monitoring techniques that can gather large amounts of data cost‐effectively at various ecological scales, from local to large spatial scales. These data can then be analyzed to inform stakeholders and decision‐makers. One such technique is passive acoustic monitoring, which is commonly coupled with automatic identification of animal species based on their sound. Automated sound analyses usually require the training of sound detection and identification algorithms. These algorithms are based on annotated acoustic datasets which mark the occurrence of sounds of species inside sound recordings. However, compiling large annotated acoustic datasets is time‐consuming and requires experts, and therefore, they normally cover reduced spatial, temporal, and taxonomic scales. This data paper presents WABAD, the World Annotated Bird Acoustic Dataset for passive acoustic monitoring. WABAD is designed to provide the public, the research community, and conservation managers with a novel and globally representative annotated acoustic dataset. This database includes 5047 min of audio files annotated to species‐level by local experts with the start and end time and the upper and lower frequencies of each identified bird vocalization in the recordings. The database has a wide taxonomic and spatial coverage, including information on 91,931 vocalizations from 1192 bird species recorded at 72 recording sites in 29 recording locations (mainly countries) and distributed across 13 biomes. WABAD can be used, for example, for developing and/or validating automatic species detection algorithms, answering ecological questions, such as assessing geographical variations on bird vocalizations, or comparing acoustic diversity indices with species‐based diversity indices. The dataset is published under a Creative Commons Attribution 4.0 International license that permits redistribution and reuse on the condition that the original work is properly credited.

A case for monitoring fungi of clinical relevance at beaches: enterococci measures do not correlate with all disease risks - Larissa Montás-Bravo; Helena M. Solo-Gabriele; Débora F. Gil; Ayaaz Amirali; Sebastian P. Arenas; Sofia Hoffman; Adriana Jimenez; Alexandre Mendonça; Rivka Reiner; Raquel Sabino; Konstantina Sarioglou; Mark E. Sharkey; et al. (Environmental Monitoring and Assessment, 2026)
Fungal disease is on the rise, coupled with fungal pathogens increasing in geographic range. Studies have shown that viable fungal pathogens may be present in beach sand and water, and consequently, efforts are ongoing in Europe to develop guidelines for fungi levels at beaches. In the USA, fungal diseases are a growing concern, and yet, they are not subject to public health reporting, and beach environments are currently not routinely monitored for fungal pathogens. This study measured fungal and enterococci levels at two beaches within a subtropical environment in Miami, FL. Samples were analyzed by culture-based methods, with fungi species confirmation by targeted PCR and sequencing. A unique aspect of this study is the analysis with higher incubation temperatures (37 °C and 40 °C) to isolate mesophilic fungi that can cause invasive infections. Results show that levels of fungi were strongly influenced by sample matrix (sand or water). The most common fungal species observed belonged to the Aspergillus and Candida genera, with the isolation of 25 taxa with reports of causing infections, of which 20 were previously reported to exhibit resistance to some or all classes of antifungals available. Results emphasize the need for fungal specific analyses to better understand beach-related disease risks. Given the current increase in cases of fungal diseases and the presence of viable fungi in the environment, integrating fungal measurements in routine microbiological monitoring programs is critical for assessing the beach transmission of pathogenic fungal disease and the control of emerging fungal pathogens.

Genotoxic and cytotoxic effects of dietary patterns and lifestyle factors: A cross-sectional comparison of Brazilian and Spanish gym users - Diene da Silva Schlickmann; Gabriela Cristina Uebel; Patrícia Molz; Nikolas Mateus Pereira de Souza; Renato Alberto Weber Colombelli; Aline Alves da Luz; Munithele Moraes Eisenhardt; Geovana Andrine Vogt; Caroline Brand; Eliane Aparecida de Castro; Pedro J. Benito; Alexandre Rieger; et al. (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2026)

Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)
Bees are essential for ecosystem functioning, pollinating many wild and crop plant species. Predicting which species are most vulnerable to global changes, and how their loss may impact ecosystems and human well-being, is critical. Comprehensive information on bee response and effect traits is fundamental to these assessments. However, the Raunkiærian shortfall—insufficient trait data—remains significant for bees, particularly in the Neotropics. Moreover, it remains uncertain whether conservation strategies based on functional diversity from temperate regions can be generalized to the Neotropics. To address this gap, we compiled a comprehensive and validated dataset on Brazilian bee traits, covering 24 traits related to sociality (100% of the species with some information), nesting (88%), body size (71%), and buzzing capacity (42%) on 2,066 Brazilian bee species. The trait data here presented is a crucial resource for evaluating bee species' pollination effectiveness and susceptibility to global change. Comparative analysis with regions with ample trait data—USA, Europe, and China—revealed notable differences. Brazilian bees exhibited a higher prevalence of aboveground nesting species, especially compared to Europe. The proportion of eusocial species was also greater than in Europe and the United States, and more similar to China. Differently from other regions, Brazilian eusocial bees were significantly smaller than their non-eusocial counterparts. These cross-regional comparisons highlight the importance of geographically tailored conservation strategies and underscore the need for extensive trait data to accurately predict regional vulnerabilities and ecological impacts in a rapidly changing world.

Dynamic Transitions in Fish Community Composition From the Amazon River Plume to Offshore Reefs - Osmar J. Luiz; Bruno E. Soares; Lucas T. Nunes; Israel Hidenburgo Cintra; Ronaldo Borges Barthem; Alexandre P. Marceniuk (Journal of Biogeography, 2026)
Aim To investigate the spatial and temporal dynamics of fish assemblages across the Northern Brazilian Shelf, a vast and complex ecosystem influenced by the Amazon River plume, we aimed to identify fish assemblage types, understand transitions between them from the river mouth to offshore reefs, and examine seasonal changes related to plume dynamics. Location Northern Brazilian Shelf (Western Atlantic Ocean), from the Amazon River mouth to the Great Amazon Reef System (GARS). Taxon Actinopterygii and Elasmobranchii. Methods We applied a presence‐absence Latent Dirichlet Allocation (LDA) model to fish occurrence records. This Bayesian mixed‐membership probabilistic approach inferred latent assemblages by analysing co‐occurring species and quantifying community types at the same site in varying proportions, suitable for characterising transitions. We then mapped these assemblages' proportional contributions and analysed their spatial distribution relative to seasonal changes in river discharge and freshwater plume influence. Results Four fish assemblages were identified with a clear coast‐to‐offshore zonation: (1) freshwater‐tolerant plume assemblage near the river mouth; (2) an estuarine–mud–plain assemblage on the inner shelf; (3) a mixed‐sand corridor assemblage in mid‐shelf; and (4) a reef‐associated assemblage on outer‐shelf GARS. The first three assemblages showed a seasonal reorganisation. During the wet season, strong plume influence led to spatially segregated assemblages. Conversely, the dry season's reduced plume resulted in increased community overlap, centred on the mid‐shelf assemblage. The reef assemblage (4) remained spatially stable across seasons. Main Conclusions The Amazon River plume's seasonal dynamics primarily drive fish community structure and connectivity across the Northern Brazilian Shelf. This study uncovers how assemblages transition from being shaped by environmental filtering (exhibiting strong zonation during peak plume) to a more overlapping distribution as plume influence weakens. These findings underscore the need for dynamic, seasonally adjusted management to conserve biodiversity and ecosystem function in this significant, and increasingly threatened, estuarine–marine transition zone.

Longitudinal effects of cerebrovascular reactivity and cerebral pulsatility in cognitively intact older adults with APOE4: links with cognition - Zacharie Potvin-Jutras; Pierre-Luc Tremblay; Hanieh Mohammadi; Sylvia Villeneuve; R. Nathan Spreng; Claudine J. Gauthier; Sylvia Villeneuve; Judes Poirier; John C.S. Breitner; Jennifer Tremblay-Mercier; Jordana Remz; Jean-Michel Raoult; et al. (GeroScience, 2025)

Scalable thermal imaging and processing framework for water status monitoring in vineyards - André Pires; Alexandre Bernardino; Gonçalo Victorino; J. Miguel Costa; Carlos M. Lopes; José Santos-Victor (Computers and Electronics in Agriculture, 2025)

Soil–climate interactions drive above-ground biomass in the Caatinga, the largest Neotropical seasonally dry tropical forest - Alexandre T. Brunello; Domingos Cardoso; Peter W. Moonlight; Ítalo A. C. Coutinho; John Cunha; Mário M. do Espírito Santo; Magna S. B. de Moura; Luciano P. de Queiroz; Rubens M. dos Santos; Tiina Särkinen; Raquel C. Miatto; Tony C. de S. Oliveira; et al. (Plant and Soil, 2025)

Crown Exposure Regulates Aboveground Wood Productivity Responses to Soil Fertility in Lowland Tropical Forests - José A. Medina‐Vega; Álvaro Duque; Daniel Zuleta; Nicolás Castaño; Renato Valencia; Salomón Aguilar; David Mitre; Rolando Pérez; Shawn K. Y. Lum; David F. R. P. Burslem; Michael J. O'Brien; Glen Reynolds; et al. (Ecology Letters, 2025)
Understanding the drivers of aboveground wood productivity (AWP) in tropical forests is crucial for explaining ecosystem functioning and predicting their responses to environmental change. While climatic water availability is a well‐established driver, the role of soil nutrients and their interaction with other resources remains uncertain. We investigated how soil nutrients and light interactions shape AWP in lowland tropical forests using fine‐scale soil and tree (≥ 1 cm DBH) data from 15 large forest plots. Canopy‐exposed trees are nutrient‐limited, with AWP increasing more with phosphorus (P) than with potassium (K), indicating P's greater role in plant growth and productivity. Conversely, understory AWP declined in fertile areas, likely due to intensified size‐asymmetric competition. At the population level (mean across canopy layers), no relationship between soil nutrients and AWP emerged because contrasting responses among layers offset any overall association. Our results suggest that fine‐scale heterogeneity and canopy stratification drive nutrient effects on tropical forest productivity.

Combining wood traits as a promising timber origin verification and its application in the Brazilian trade chain - Bruna Hornink; Daigard Ricardo Ortega-Rodriguez; Deoclecio J. Amorim; Peter Groenendijk; Kathelyn Paredes-Villanueva; José Guilherme Roquette; Ana Carolina M.C. Barbosa; Edson Vidal; Alexandre Bahia Gontijo; Monique S. Costa; Norma Rodrigues Nunes de Senna; Davi Neves de Lemos; et al. (Science of The Total Environment, 2025)

An Experimental Method for Measuring Permeability of Fragile, Irregularly Shaped Porous Media - J. Ryan O’Nan; Yejajul Hakim; Cameron Brewer; Alexandre Martin; Savio J. Poovathingal; Michael W. Renfro (Transport in Porous Media, 2025)

Soft Range Limits Shape Sensitivity to Forest Cover More Strongly Than Hard Range Limits - Natasha R. Granville; Alex L. Pigot; Benjamin Howes; Luiz dos Anjos; Victor Arroyo‐Rodriguez; Luc Barbaro; Jos Barlow; Matthew G. Betts; Alexis Cerezo; Pedro F. Develey; Jack H. Hatfield; Hervé Jactel; et al. (Global Ecology and Biogeography, 2025)
Aim Land‐use change is a major threat to biodiversity, yet there remains considerable unexplained variation in how it affects different populations of the same species. Here, we examine how sensitivity to forest cover changes depending on proximity to different limits of a species' range. By comparing responses as species approach their coastal (‘hard’) and inland (‘soft’) range limits, we aim to provide insight into the relative influence of mass effects, as compared to abiotic and biotic environmental suitability in shaping population sensitivity. Location Global. Time Period 1996–2019. Major Taxa Studied Birds. Methods We combined data from several large databases to obtain a dataset of 2543 bird species surveyed across 116 studies, spanning six continents. Using expert‐verified range maps, we calculated the position of populations relative to their species' nearest inland (‘soft’) and coastal (‘hard’) range limits and categorised the inland limits as equatorward‐ or poleward‐ facing. We investigated how distance to range limits and forest cover, derived from a 30 m‐resolution global dataset, affect the probability of species' incidence. Results We found that bird populations are more sensitive to forest cover when located closer to their species' inland (‘soft’) range limits, whereas this was not the case at coastal (‘hard’) range limits. The heightened sensitivity to forest cover at soft range limits was similar regardless of whether the range limit faced equatorward or poleward. Main Conclusions These results highlight how populations close to the soft limits of their species' ranges are at higher risk of extirpation resulting from loss of forest cover. This suggests that environmental conditions (e.g., climate), which become more challenging away from the core of the species' range, drive variability in sensitivity to forest cover.

Myiasis-causing flies in anurans: new interactions, geographic distribution, and an updated list of records in the Neotropics - Franciele Cristina de Souza; Victor Morais Ghirotto; Alexandre Polletini Neto; Camila Saraiva dos Anjos; André Luís F. da Silva; Rodrigo Lingnau; Emeline da S. Ceccon; Cátia Antunes de Melo-Patiu †; Mirco Solé; Silionamã P. Dantas; Claudio Borteiro; Domingos de J. Rodrigues; et al. (Biologia, 2025)

Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Rodrigo Tardin; Guilherme Maricato; Jeremy J. Kiszka; Mauricio Cantor; Israel Maciel; Gabriel Melo-Santos; Laura May-Collado; Ana Carolina Meirelles; Maria Isabel C. Gonçalves; Fábio G. Daura-Jorge; Renata S. Sousa-Lima; Yvonnick Le Pendu; et al. (Ocean & Coastal Management, 2025)

Effects of grassland community composition and digestate fertiliser on nitrous oxide emissions from soil - Ali S. Khan; John A. Finn; Alexandre B. de Menezes; Dominika J. Krol (Journal of Environmental Management, 2025)

Experimental assessment of antibiotic resistance in a Biofilm – Grazer system - Alexandre J. Thibodeau; Florence Mouchet; Van Xuan Nguyen; Eric Pinelli; Maialen Barret (Environmental Pollution, 2025)

Between tides and forests: diversity of social wasps (Vespidae: Polistinae) on the Brazilian Amazon coast - José de J. Corrêa-Neto; Alexandre Somavilla; Marcio Luiz de Oliveira (Wetlands Ecology and Management, 2025)

Humidity Control and Its Implications in the Storage of Apples and Pears: A Review - Robert K. Prange; A. Harrison Wright; Barbara J. Daniels-Lake; Daniel Alexandre Neuwald; Dirk Köpcke; Luiz Carlos Argenta (Applied Fruit Science, 2025)
At harvest, the water content of apples and pears is at its maximum, about 83–85% by mass. The rate of fruit water loss after harvest is a function of three factors: the fruit surface area, the epidermis water vapour permeance, and the difference in internal and external fruit water vapour pressure. However, the water vapour pressure difference is the only factor that can be controlled during storage, i.e. by altering the storage humidity. Curiously, most publications on apple and pear storage do not discuss storage humidity even though the postharvest quality of both depends largely upon it. Apples and pears can experience up to ~ 2% mass loss without loss of commercial value, but further mass loss creates visible shrivelling, and may also increase bitter pit, depending on the cultivar. The prevailing commercial advice has been to minimise mass loss by maximising the relative humidity at the chosen storage temperature. However, this advice should be re-evaluated, and humidity management protocols revised, from minimising mass loss to optimising mass loss. Growing evidence indicates that storage humidity affects the postharvest performance of apples and pears. A review of the literature over the last 100 years shows that some mass loss, achieved by lowering storage atmosphere humidity, can improve apple and pear quality by reducing non-bitter pit disorders, bruising, respiration, ethylene production and decay, especially if the mass loss occurs at the beginning of storage. The effects of mass loss on calcium-related disorders suggest that mass loss may affect postharvest calcium redistribution in the fruit. The fruit mass loss for refrigerated air and controlled atmosphere rooms can be estimated by collecting the defrost water from the refrigeration cooling coils and expressing this as a percentage of the initial total mass of fruit in the room. A ‘2-in-2’ guideline (up to 2% mass loss in the first 2 months) is proposed, but further research is needed to refine this guidance, especially for cultivars that may benefit from greater mass loss without increasing shrivelling or bitter pit.

Coral bleaching and mortality across a 24° latitudinal range in the Southwestern Atlantic during the fourth global bleaching event - Miguel Mies; Giovanna Destri; Carlos H. F. Lacerda; Júlia L. M. Carvalho; Júlia Y. Ibanhez; Arthur Z. Güth; André L. Luza; Luiza P. Campos; Aline C. Shimada; Kenzo N. T. Omaki; Bianca E. Jahn; Yasmim A. Abreu; et al. (Coral Reefs, 2025)

Late 21st‐Century Climate and Land Use Driven Loss of Plant Diversity in African Mountains - João de Deus Vidal Junior; Alexandre Antonelli; Clinton Carbutt; Vincent Ralph Clark; Tobias Fremout; Christopher Chapano; Inês Chelene; David Chuba; Tadesse Woldemariam Gole; Clayton Langa; Benoit Loeuille; Ermias Lulekal Molla; et al. (Global Change Biology, 2025)
With the 1.5°C–5°C increase in global temperature projected for this century, many plant species are expected to shift their distribution ranges to track their environmental requirements. Across several mountain regions, responses to climate change like upslope shifts may result in accelerated rates of species turnover, species richness increases in upper montane belts, and amplified habitat losses. Yet, evidence of how such processes may influence plant diversity in Africa is still scarce. Here, using a species distribution modeling approach, we quantify and map how different scenarios of climatic and land‐use changes may affect plant species ranges in African mountains. Using individually tuned models and dispersal buffers, we compared distribution losses and potential expansion through dispersal across 607 vascular plant species under three shared socioeconomic pathways for the end of the century. Our projections indicate that keeping warming under 2°C until 2100 under a sustainability scenario (SSP1.26), almost half (49.3%) of the species would experience a contraction in suitable areas, compared to 71%–75.6% in case these targets are not met (SSP3.70 and SSP5.85). Among these losses, mean contractions between 19% and 50.4% are predicted depending on the scenario. We project rates of upslope shifts that may be up to three times higher than the global calculated average. Contractions will be higher for species occurring at upper elevations, and trees and shrubs will show lower declines. Our findings align with previously reported trends of upslope shifts of species distributions but suggest that accelerated rates of change may limit the capacity of some species to track their niche based solely on their natural dispersal capacity. This implies that further efforts to improve habitat connectivity, restoration, and assisted migration may be necessary.

Predominance of L. monocytogenes Lineage I Clones in Wastewater, Ruminants, and Natural Environments - Yuval Markovich; Alexandra Moura; Jesús Gomis; Alexandre Leclercq; Ángel Gómez‐Martín; Hélène Bracq‐Dieye; Carla Palacios‐Gorba; Nathalie Tessaud‐Rita; Susana Ortolá; Guillaume Vales; M‐Adela Yáñez; Pierre Thouvenot; et al. (Environmental Microbiology, 2025)
Listeria monocytogenes is a saprophytic bacterium and a foodborne pathogen of humans and animals. Little is known about its distribution and genetic diversity across different environments within the same geographical region. We conducted a large‐scale longitudinal study in southeastern Spain monitoring Listeria spp. in untreated wastewater, ruminant farms, and natural environments over four seasons ( N = 1490 samples, N = 545 isolates) and in food and food‐processing environments ( N = 7395 samples, N = 255 isolates). Listeria spp. were more abundant in host‐associated than natural environments, and non‐pathogenic Listeria were more prevalent than L. monocytogenes in both niches. L. monocytogenes was detected in 42.7%, 11.4%, 4.2%, and 3.4% of wastewater, ruminant farms, natural environments, and food‐related samples, respectively. Hypervirulent lineage I accounted for 82.9% of L. monocytogenes isolates from wastewater, ruminant farms, and natural environments, while lineage II represented 74.1% in food‐related samples. Among 255 L. monocytogenes cgMLST types, 5% were shared across environments, demonstrating circulation between different environments. Persistent L. monocytogenes clones were detected in food processing environments and ruminant farms. Our data suggest anthropogenic activities and livestock drive Listeria spp. dissemination. These results provide insights into the interactions of Listeria spp. in the environment, improving surveillance strategies to reduce pathogen transmission, food contamination, and clinical cases.

Engaging and legitimizing communities: co-designing a community-based Marine Protected Area - Mafalda Rangel; Barbara Horta e Costa; Mª Helena Guimarães; Adriana Ressurreição; Pedro Monteiro; Frederico Oliveira; Luís Bentes; Nuno Sales Henriques; Inês Sousa; Sofia Alexandre; João Pontes; Carlos ML Afonso; et al. (Marine Policy, 2025)

Influence of algal drift and morphodynamic conditions on the fish assemblages and feeding guilds in ocean-exposed tropical beaches - Alexandre da Gama Fernandes Vieira-Júnior; Breno Silva Macário; Steven J. Presley; Michael R. Willig; André Luiz Machado Pessanha (Estuarine, Coastal and Shelf Science, 2025)

Spatial biases in oxygen-based Phanerozoic seawater temperature reconstructions - Alexandre POHL; Thomas W. WONG HEARING; Arnaud BRAYARD; Ethan GROSSMAN; Michael M. JOACHIMSKI; Guillaume LE HIR; Thomas LETULLE; Daniel J. LUNT; Mathieu MARTINEZ; Emmanuelle PUCEAT; Guillaume SUAN; Paul VALDES; et al. (Earth and Planetary Science Letters, 2025)

Whole cell microalgae: Potential to transform industry waste into sustainable ruminant feed - Kira J. Picknell; Nature Poddar; Janice I. McCauley; Alexandre V. Chaves; Peter J. Ralph (Bioresource Technology, 2025)

Digestive anatomy and diet of free-ranging maned wolf (Chrysocyon brachyurus) - Bruno Costa Silva; Luan Alexander de Oliveira; Marcus Clauss; Claudia Guimarães Costa; Leandro de Oliveira Marques Alexandre; María J. Duque-Correa (Mammalian Biology, 2025)
The maned wolf ( Chrysocyon brachyurus ) is the largest of the currently extant ten species of South American canids and is a monotypic taxon in the genus Chrysocyon , currently classified as Near Threatened by the IUCN. Here we report the anatomy of the gastrointestinal tract (GIT) of 12 free-ranging maned wolves (10 adults, six females, four males, and two juvenile males), nutritional analyses of the gastrointestinal tract (stomach, small, and large intestine) of eight individuals (six females and two males), and the macroscopical examination of the stomach contents of eight individuals (four adult females, two adult males, and two juvenile males). The general anatomy and the dimensions of the maned wolf`s GIT resembled that of other canids. The results of the dietary analyses reported in this study are similar to previously reported data for the species, confirming its omnivorous nature. Vertebrates were found in all stomachs, representing 42.5% of the total dietary mass. Vegetable material was also present in all stomachs, accounting for half of the total dietary mass (50.5%). Anthropogenic material, including cooked rice, glass, and ceramic fragments, were retrieved from the stomach of one individual; such opportunistic feeding behavior has been previously reported. When compared to other Carnivora species classified as omnivores, including the red fox ( Vulpes vulpes ) and the raccoon dog ( Nyctereutes procyonides ), these ‘omnivorous’ carnivores ingest distinctively higher levels of fiber compared to purely faunivorous Carnivora. This information might be important for feeding these species in ex-situ settings.

Synergistic effect of high-energy milling and organic intercalation on the kaolin properties and structural evolution - Alexandre Zaccaron; Fabiano Raupp-Pereira; Vitor de Souza Nandi; João C.C. Abrantes; Manuel J. Ribeiro; Adriano Michael Bernardin (Applied Clay Science, 2025)

Model seasonal and proxy spatial biases revealed by assimilated mid-Holocene seasonal temperatures - Shuo Hao; Xu Zhang; Yanwu Duan; Evan J. Gowan; Jiang Zhu; Alexandre Cauquoin; Jie Chen; Martin Werner; Fahu Chen (Science Bulletin, 2025)

The Biogeography of Soil Bacteria in Australia Exhibits Greater Resistance to Climate Change Than Fungi - Peipei Xue; Budiman Minasny; Mercedes Román Dobarco; Alexandre M. J.‐C. Wadoux; Jose Padarian Campusano; Andrew Bissett; Patrice de Caritat; Alex McBratney (Global Change Biology, 2025)
Soil microorganisms are crucial to ecosystem health, and their composition and distribution are shaped by a range of environmental factors. However, the effects of accelerating climate change on soil microbiomes remain under‐explored. This study examines the continental‐scale factors controlling soil microbiomes and evaluates their responses to climate change. We applied machine learning algorithms to analyze the distribution patterns of bacteria and fungi in 1300 Australian topsoil samples. Our results indicate that bacterial distributions align closely with the soil class map, highlighting the dominant impact of soil properties. In contrast, fungal distributions are more strongly associated with temperature gradients, emphasizing the critical role of climate. Climate projections for 2040 suggest a notable southward shift in both bacterial and fungal patterns, particularly around latitude 25° S. Moreover, our findings suggest that fungal biogeography is likely to undergo more pronounced changes, with approximately 24% of Australian topsoils expected to experience significant shifts in fungal community structure, compared to about 19% for bacteria, which appear more resistant. This study emphasizes the diverse vulnerabilities of soil microbial communities and stresses the need to account for microbial dynamics in future land use and management practices.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Strengthening Rigor and Reproducibility in Epigenome-Wide Association Studies of Social Exposures and Brain-Based Health Outcomes - Brooke G. McKenna; Alexandre A. Lussier; Matthew J. Suderman; Esther Walton; Andrew J. Simpkin; Anke Hüls; Erin C. Dunn (Current Environmental Health Reports, 2025)

Fluoroquinolone and sulfonamide antibiotics (single and mixtures) impair the motor function of zebrafish larvae at environmentally relevant concentrations - Gleyson B. Castro; Juliano J. Corbi; Mateus Cottorello-Fonsêca; Daniela Correia; Demetrio Raldúa; David S. Alexandre; Thandy Junio da Silva Pinto; Eva Prats; Melissa Faria (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Energy and property trade-offs in nanocellulose production: High-pressure homogenization at different processing consistencies - Giovana Signori-Iamin; Roberto J. Aguado; Jean-Luc Putaux; Alexandre F. Santos; Wim Thielemans; Marc Delgado-Aguilar (Chemical Engineering Journal, 2025)

Pan-Canadian Predictive Modeling of Lithium–Cesium–Tantalum Pegmatites with Deep Learning and Natural Language Processing - Mohammad Parsa; Christopher J. M. Lawley; Tarryn Cawood; Tania Martins; Renato Cumani; Steven E. Zhang; Aaron Thompson; Ernst Schetselaar; Steve Beyer; David R. Lentz; Jeff Harris; Hossein Jodeiri Akbari Fam; et al. (Natural Resources Research, 2025)
The discovery of new lithium resources is essential because lithium plays a vital role in the manufacturing of green technology. Along with brines and volcano–sedimentary deposits, approximately a one-third share of global lithium resources is associated with lithium-cesium-tantalum (LCT) pegmatites, with Canada hosting numerous examples. This research applied generative adversarial networks, natural language processing, and convolutional neural networks to generate mineral prospectivity models and support exploration targeting for Canadian LCT pegmatites. Geoscientific text data included within public bedrock geology maps and natural language processing were used to convert conceptual targeting criteria into evidence layers that complement more traditional, geophysical and geochronological data used for mineral prospectivity modeling (MPM). A multilayer architecture of convolutional neural networks, including an attention mechanism, was designed for data modeling. This architecture was trained and validated using variable synthetically generated class labels, input image sizes, and hyperparameters, resulting in an ensemble of 1000 models. The uncertainty of the ensemble was analyzed using a risk–return analysis, yielding a bivariate choropleth risk–return plot that facilitates the interpretation of prospectivity models for downstream applications. This was further complemented by employing post hoc interpretability algorithms to translate the black-box nature of neural networks into comprehensible content. The low-risk and high return class of our prospectivity models reduces the search space for discovering LCT pegmatites by 88%, delineating 99% of known LCT pegmatites in Canada. The results of this study suggest that our workflow (i.e., combining synthetic data generation, natural language processing, convolutional neural networks, and uncertainty propagation for MPM) facilitates decision-making for regional-scale lithium exploration and could also be applied to other mineral systems.

Potentiating-antibiotic and antibacterial properties of Luetzelburgia auriculata (ALLEMÃO) Ducke against MDR bacterial strains - Thiago S. Freitas; Janaina E. Rocha; Marcos J. F. Lima; Carla F. A. Nonato; Cicera J. Camilo; Cicera L. R. Paulo; Maria A. S. Alencar; Isaac M. Araújo; Karla S. T. G. Belém; Selvina P. Silva; Francisco N. Pereira Junior; Hélcio S. Santos; et al. (Vegetos, 2025)

Transfer of deoxynivalenol and fumonisins B1 and B2 from maize flour to maize/wheat-based bread - Alexandre Vicens-Sans; Sonia Marín; Vicente Sanchis; Antonio J. Ramos; Francisco Molino (International Journal of Food Microbiology, 2025)

What threats do Brazilian National parks face? - Alícia Helena Torres da Rocha; Jhonatan Guedes-Santos; Felipe Alexandre Santos Vieira; Ana Claudia Mendes Malhado; Richard J. Ladle; Jairo Lizandro Schmitt; Chiara Bragagnolo (Journal for Nature Conservation, 2025)

Impact of a bimodal dust distribution on the 2018 Martian global dust storm with the NASA Ames Mars global climate model - Richard A. Urata; Tanguy Bertrand; Melinda A. Kahre; R. John Wilson; Alexandre M. Kling; Michael J. Wolff (Icarus, 2025)

Review of landslide inventories for Nepal between 2010 and 2021 reveals data gaps in global landslide hotspot - Erin L. Harvey; Mark E. Kincey; Nick J. Rosser; Arishma Gadtaula; Ethan Collins; Alexander L. Densmore; Alexandre Dunant; Katie J. Oven; Katherine Arrell; Gopi K. Basyal; Megh Raj Dhital; Tom R. Robinson; et al. (Natural Hazards, 2025)
A review of landslide inventories provides an essential assessment of the state of knowledge around landslide hazard and can guide the focus of future studies. This is especially true in Nepal, which is highly prone to landslides, but lacks a comprehensive overview of landslide occurrence nationally. Here, we compile a database of 117 landslide inventories for Nepal released between 2010 and 2021. We review how these existing inventories shape our understanding of landsliding in Nepal and discuss how future research efforts could mitigate current challenges. We find that 40% of the country was only manually mapped once across the study period, and, crucially, these areas did not always correspond with areas of low landslide susceptibility. Instead, existing landslide inventories typically focus on specific areas, such as the region affected by the 2015 Gorkha Earthquake and major highway corridors. We also extrapolated the individual inventory characteristics from within this unique database to infer a national-scale areal density of 0.05 landslides per km 2 , equating to 6000 landslides across the country. This extrapolated value provides a baseline for future national-scale studies, especially for inventories created through automated mapping approaches. Our review highlights the importance of expanding the footprint of landslide inventories in Nepal to include regions with low mapping coverage and the need for inventories to be openly available, with clear protocols to enable inter-comparison. Whilst our review has focused on Nepal, these findings are likely to be relevant in other landslide-prone countries and our recommendations are intended to be applicable elsewhere.

New experimental constraints on seismic velocities and densities across the $$α $$–$$β $$ quartz transition at deep crustal conditions - Giulia Mingardi; Julien Gasc; Matteo Ardit; Ross J. Angel; Wilson A. Crichton; Dmitrii Druzhbin; Jerome Aubry; Alexandre Schubnel; Matteo Alvaro (Contributions to Mineralogy and Petrology, 2025)
At the pressure and temperature conditions of the lower crust, quartz undergoes a displacive phase transition from a trigonal ( $$α $$ ) to a hexagonal phase ( $$β $$ ). At room pressure, the $$α $$ – $$β $$ quartz transition occurs at 574.1 °C and it is associated with large changes in the thermodynamic and elastic properties. For that reason, it is interpreted as the cause of significant seismic velocity contrasts in the crust seen by seismic tomography. Existing thermodynamic models and Equations of State (EoS) of quartz are mostly constrained by data collected at room pressure (or at high pressure and room temperature). In this work we characterized the $$α $$ – $$β $$ quartz transition experimentally at simultaneous HP – HT conditions using synchrotron X-ray diffraction and acoustic measurements, and derived values of $$V_p$$ , $$V_s$$ , the adiabatic bulk modulus ( $$K_s$$ ) and the shear modulus ( G ). The data collected in the $$α $$ field agree with the models from the literature, so entrapment pressures of $$α $$ -quartz inclusions calculated via elastic barometry with these EoS should be reliable. However, our measured $$V_p$$ , $$V_s$$ , and $$K_s$$ are significantly lower than those predicted for $$β $$ -quartz. Whatever the cause of this discrepancy, interpretations of seismic data in terms of the properties of $$β $$ -quartz in the lower crust and calculations of entrapment conditions of quartz inclusions in the stability field of $$β $$ -quartz should be treated with caution.

Multiyear temperature variation in tropical mountain peatlands from the southern Espinhaço Mountain Range in Brazil - Diego Tassinari; Cristiano Christofaro; Uidemar M. Barral; Camila R. Costa; Thiago A. A. Pinto; William J. Do Carmo; Bárbara P. C. Silva; Érica P. Cardozo; Alexandre C. Silva (Journal of Mountain Science, 2025)

A seascape dichotomy in the role of small consumers for coral reef energy fluxes - Simon J. Brandl; Helen F. Yan; Jordan M. Casey; Nina M. D. Schiettekatte; Julianna J. Renzi; Alexandre Mercière; Fabien Morat; Isabelle M. Côté; Valeriano Parravicini (Ecology, 2025)
Biogeochemical fluxes through ecological communities underpin the functioning of ecosystems worldwide. These fluxes are often heavily influenced by small‐bodied consumers, such as insects, worms, mollusks, or small vertebrates, which transfer energy and nutrients from autotrophic sources to larger animals. Although coral reefs are one of the most productive ecosystems in the world, we know relatively little about how small consumers make energy available to larger predators and how their roles may vary across reefs. Here, we use community‐scale collections of small, bottom‐dwelling (“cryptobenthic”) reef fishes along with size spectrum analyses, stable isotopes, and demographic modeling to examine their role in harnessing and transferring carbon in two distinct coral reef habitats. Using a comprehensive dataset from Mo'orea (French Polynesia), we demonstrate that, despite only being separated by a narrow reef crest, forereef and backreef habitats harbor distinct communities of cryptobenthic fishes that play vastly divergent roles in carbon transfer. Forereef communities in Mo'orea are depauperate, largely consisting of predatory and planktivorous species that have comparatively high standing biomass (both individually and collectively). In these communities, the combination of size spectra and isotope values suggests important contributions of pelagic subsidies, but the rate of biomass production and turnover (i.e., the rate at which biomass is replenished) is relatively low. In contrast, cryptobenthic fish communities in the backreef are characterized by high abundances of the smallest bodied species, forming a traditional bottom‐heavy trophic pyramid that is fueled by benthic autotrophs. In these communities, benthic productivity fuels rapid production and turnover of fish biomass, while pelagic energy channels are notably less productive. Our integrative approach demonstrates the utility of combining multiple methods (e.g., isotopically informed demographic models) to trace energy fluxes through small consumer communities in complex ecosystems. Furthermore, our results highlight that coral reef productivity dynamics are highly habitat‐dependent and the role of the smallest coral reef consumers may be most pronounced in shallow systems with limited connectivity to the open ocean.

New records of peppermint shrimps from northeastern Brazil support Lysmata lipkei as junior synonym of Lysmata dispar - Rodrigo Guéron; J. Antonio Baeza; Gabriel Lucas Bochini; Mariana Terossi; Alexandre Oliveira Almeida (Regional Studies in Marine Science, 2025)

Triple oxygen and hydrogen stable isotope composition of water in Murchison carbonaceous chondrite accessed by thermogravimetry-enabled laser spectroscopy - Erik J. Oerter; Alexandre Garenne; Miguel Cisneros; George D. Cody; Michael Singleton; Conel M. O’D. Alexander (Chemical Geology, 2025)

Cannabidiol-Induced Autophagy Ameliorates Tau Protein Clearance - Talita A. M. Vrechi; Gabriel C. Guarache; Rafaela Brito Oliveira; Erika da Cruz Guedes; Adolfo G. Erustes; Anderson H. F. F. Leão; Vanessa C. Abílio; Antonio W. Zuardi; Jaime Eduardo C. Hallak; José Alexandre Crippa; Claudia Bincoletto; Rodrigo P. Ureshino; et al. (Neurotoxicity Research, 2025)
Tau is a neuronal protein that confers stability to microtubules; however, its hyperphosphorylation and accumulation can lead to an impairment of protein degradation pathways, such as autophagy. Autophagy is a lysosomal catabolic process responsible for degrading cytosolic components, being essential for cellular homeostasis and survival. In this context, autophagy modulation has been postulated as a possible therapeutic target for the treatment of neurodegenerative diseases. Studies point to the modulatory and neuroprotective role of the cannabinoid system in neurodegenerative models and here it was investigated the effects of cannabidiol (CBD) on autophagy in a human neuroblastoma strain (SH-SY5Y) that overexpresses the EGFP-Tau WT (Wild Type) protein in an inducible Tet-On system way. The results demonstrated that CBD (100 nM and 10 µM) decreased the expression of AT8 and total tau proteins, activating autophagy, evidenced by increased expression of light chain 3-II (LC3-II) protein and formation of autophagosomes. Furthermore, the cannabinoid compounds CBD, ACEA (CB1 agonist) and GW-405,833 (CB2 agonist) decreased the fluorescence intensity of EGFP-Tau WT; and when chloroquine, an autophagic blocker, was used, there was a reversal in the fluorescence intensity of EGFP-Tau WT with CBD (1 and 10 µM) and GW-405,833 (2 µM), demonstrating the possible participation of autophagy in these groups. Thus, it was possible to conclude that CBD induced autophagy in EGFP-Tau WT cells which increased tau degradation, showing its possible neuroprotective role. Hence, this study may contribute to a better understanding of how cannabinoids can modulate autophagy and present a potential therapeutic target in a neurodegeneration model. Graphical Abstract

DiverReef : A global database of the behavior of recreational divers and their interactions with reefs over 20 years - Vinicius J. Giglio; Johnatas Adelir‐Alves; Natalia Balzaretti Merino; Myrna Leticia Bravo‐Olivas; Emma F. Camp; Edoardo Casoli; Rosa Maria Chávez‐Dagostino; Eliana Ferretti; Douglas Fraser; Ana C. Grillo; Santiago Jiménez‐Guiérrez; Kelen L. Leite; et al. (Ecology, 2025)
Recreational diving is an important activity in reef environments worldwide, providing income and employment for coastal communities and connecting visiting divers to these ecosystems promoting conservation and stewardship. However, if poorly managed, diving has the potential to cause detrimental effects on benthic communities via mechanical damage caused by physical contact of divers with the reef, often in the form of unintentional fin kicks resulting from poor buoyancy. Understanding diver–reef interaction patterns is important to elucidate the potential impacts of diving tourism on the reef biota. The DiverReef database provides the first public dataset on the underwater behavior of recreational divers in shallow reef environments (

Epilithic algal composition and the functioning of Anthropocene coral reefs - Sterling B. Tebbett; Michael J. Emslie; Michelle J. Jonker; Scott D. Ling; Morgan S. Pratchett; Alexandre C. Siqueira; Angus A. Thompson; Helen F. Yan; David R. Bellwood (Marine Pollution Bulletin, 2025)

17O-excess of grass leaf phytoliths across the North American prairies records late-growing season daytime relative humidity - Minger Guo; Anne Alexandre; Fred J. Longstaffe; Christophe Peugeot; Elizabeth A. Webb (Chemical Geology, 2025)

Potential of Scenedesmus sp. and Aurantiochytrium spp. as protein and n-3 fatty acid sources in practical diets for juvenile Penaeus vannamei - Alberto J. P. Nunes; Felipe Nobre Façanha; Jordana Sampaio Leite; Alexandre F. Diógenes (Aquaculture International, 2025)

Small-scale fisheries in ecologically sensitive areas in Latin America and the Caribbean: Do marine protected areas benefit fisheries governance? - Ana Cinti; Luisa Ramirez; Mauricio Castrejón; Jaime A. Aburto; Luciana Loto; Stuart Fulton; Mario Rueda; Alexandre Schiavetti; Francisco J. Fernández-Rivera Melo; Manuel Bravo; Daniela Trigueirinho Alarcon; Valéria Penchel Araújo; et al. (Ambio, 2025)
Many small-scale fisheries (SSFs) in Latin America and the Caribbean (LAC) operate in ecologically sensitive areas, where balancing conservation and resource use is challenging. 'Multiple-use' marine protected areas (MPAs) have been implemented to accommodate SSFs (among other uses) within areas designated for conservation, creating opportunities and challenges for SSF governance. We analyzed eleven case studies from LAC to explore: (1) how different MPA institutional designs affect key aspects of SSF governance and (2) the links between these effects and the type of initiative that promoted MPA establishment (origin). Results indicate that the existence of an MPA benefited SSF governance in many ways, with more pronounced positive effects in MPAs with mixed to bottom-up origin supported by well-organized fishing groups. In addition, the presence of supportive MPA authorities that leveraged local capacities and initiatives and adopted flexible and collaborative governance systems made a difference in several cases. Lessons for integrating MPA and SSF governance are drawn.

Conservation of ant communities in cashew tree-based agroforestry systems: key roles of tree density and diversity - Anicet G. Dassou; Charlemagne D. S. J. Gbemavo; Alexis Onzo; Sathurnin Kpoto; Corinne M. Anagonou; Alexandre Dansi; Philippe Tixier; Dominique Carval (Agroforestry Systems, 2025)

Temporal trends in global reptile species descriptions over three decades - Jhonny J. M. Guedes; Hidalgo Valentim Gomes De Lima; Lucas R. Mendonça; Rosana Chen-Zhao; José Alexandre F. Diniz-Filho; Mario R. Moura (Systematics and Biodiversity, 2024)

Integrative species delimitation and biogeography of the Rhinella margaritifera species group (Amphibia, Anura, Bufonidae) suggest an intense diversification throughout Amazonia during the last 10 million years - Antoine Fouquet; Miqueias Ferrão; Miguel T. Rodrigues; Fernanda P. Werneck; Ivan Prates; Leandro J.C.L. Moraes; Tomas Hrbek; Juan C. Chaparro; Albertina P. Lima; Renata Perez; Andre Pansonato; Vinicius T. Carvalho; et al. (Systematics and Biodiversity, 2024)

Comprehensive characterization of European house dust contaminants: Concentrations and profiles, geographical variability, and implications for chemical regulation and health risk - Peter Haglund; Nikiforos A. Alygizakis; Adrian Covaci; Lisa Melymuk; Pernilla Bohlin Nizzetto; Pawel Rostkowski; Alexandre Albinet; Sylvana Alirai; Dagny Aurich; Stefan Bieber; Ana Ballesteros-Gómez; Amanda A. Brennan; et al. (Science of The Total Environment, 2024)

Diel movement patterns in nominally nocturnal coral reef fishes (Haemulidae and Lutjanidae): Intra vs. Interspecific variation - William P. Collins; David R. Bellwood; Renato A. Morais; Nathan J. Waltham; Alexandre C. Siqueira (Coral Reefs, 2024)
Movement of animals, habitat connectivity, and nutrient transport are key elements in the ecological functioning of coral reef ecosystems. However, most studies have focused on the diurnal component of these aspects; nocturnal patterns are less known. Our study aims to address this knowledge gap by assessing diel movement patterns in ecologically and commercially important nocturnal coral reef fishes. We evaluate 122-days of acoustic telemetry data from 4 nocturnal species in 2 coral reef fish families (Haemulidae and Lutjanidae) on the Great Barrier Reef. For all species, we found a clear division between daytime resting areas on the reef and a move towards off-reef areas at night. This was highlighted in the low number of detections at night and the high average transitions between receivers at twilight. Over our study period, average nocturnal space use area (minimum convex polygon) of Plectorhincus gibbosus was 328,089 m 2 , Plectorhincus lineatus 28,828 m 2 , and Lutjanus carponotatus 20,369 m 2 . However, results from a Principal Component Analysis revealed that space use, and movement, varied substantially within species; for 3 of the 4 species the main axis of variation correlated with individual-level behaviour. These large differences in individual space use patterns highlight the need for caution when using species averages when considering ecosystem functions. Overall, our preliminary observations provide a glimpse into the large spatial extent, potential habitat connectivity, and intra and interspecific variation in activity patterns among large nocturnal Indo-Pacific reef fishes. This highlights their potential importance in maintaining ecosystem links between coral reefs and adjacent habitats.

Soil characteristics drive contrasting patterns of association between symbiotic rhizobia of endemic and widespread Mimosa species in Brazil - Luc Rouws; Alexandre Barauna; Chrizelle Beukes; Janaina R.C. Rouws; Sergio Miana de Faria; Eduardo Gross; Fabio Bueno dos Reis; Marcelo F. Simon; Marta Maluk; David W. Odee; Stephanie Fordeyn; Gregory Kenicer; et al. (Applied Soil Ecology, 2024)

Supplementation with 25-hydroxicolecalciferol increases the nutritional efficiency and carcass growth of grazing Nellore young bulls - Fernanda S. Mudado; Melissa B. Silveira; Henrique J. Fernandes; Alexandre Perdigão; Diego M.M. dos Santos; Thomas H.R. da Silva; Jarbas M. da Silva Júnior; Isabelle E. de Matos; Victor V. de Carvalho; Tiago S. Acedo; Aline G. da Silva (Animal Feed Science and Technology, 2024)

FreshLanDiv : A Global Database of Freshwater Biodiversity Across Different Land Uses - Minghua Shen; Roel van Klink; Alban Sagouis; Danielle K. Petsch; Deborah Atieno Abong'o; Janne Alahuhta; Salman Abdo Al‐Shami; Laura Cecilia Armendáriz; Mi‐Jung Bae; Tiago Octavio Begot; Jerome Belliard; Jonathan Peter Benstead; et al. (Global Ecology and Biogeography, 2024)
Motivation Freshwater ecosystems have been heavily impacted by land‐use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land‐use categories. This compilation will be useful for addressing questions regarding land‐use change and its impact on freshwater biodiversity. Main Types of Variables Contained The database includes metadata of each study, sites location, sample methods, sample time, land‐use category and abundance of each taxon. Spatial Location and Grain The database contains data from across the globe, with 85% of the sites having well‐defined geographical coordinates. Major Taxa and Level of Measurement The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.

Phenology Across Scales: An Intercontinental Analysis of Leaf‐Out Dates in Temperate Deciduous Tree Communities - Nicolas Delpierre; Suzon Garnier; Hugo Treuil‐Dussouet; Koen Hufkens; Jianhong Lin; Colin Beier; Michael Bell; Daniel Berveiller; Matthias Cuntz; Giulio Curioni; Kyla Dahlin; Sander O. Denham; et al. (Global Ecology and Biogeography, 2024)
Aim To quantify the intra‐community variability of leaf‐out (ICVLo) among dominant trees in temperate deciduous forests, assess its links with specific and phylogenetic diversity, identify its environmental drivers and deduce its ecological consequences with regard to radiation received and exposure to late frost. Location Eastern North America (ENA) and Europe (EUR). Time Period 2009–2022. Major Taxa Studied Temperate deciduous forest trees. Methods We developed an approach to quantify ICVLo through the analysis of RGB images taken from phenological cameras. We related ICVLo to species richness, phylogenetic diversity and environmental conditions. We quantified the intra‐community variability of the amount of radiation received and of exposure to late frost. Results Leaf‐out occurred over a longer time interval in ENA than in EUR. The sensitivity of leaf‐out to temperature was identical in both regions (−3.4 days per °C). The distributions of ICVLo were similar in EUR and ENA forests, despite the latter being more species‐rich and phylogenetically diverse. In both regions, cooler conditions and an earlier occurrence of leaf‐out resulted in higher ICVLo. ICVLo resulted in ca. 8% difference of radiation received from leaf‐out to September among individual trees. Forest communities in ENA had shorter safety margins as regards the exposure to late frosts, and were actually more frequently exposed to late frosts. Main Conclusions We conducted the first intercontinental analysis of the variability of leaf‐out at the scale of tree communities. North American and European forests showed similar ICVLo, in spite of their differences in terms of species richness and phylogenetic diversity, highlighting the relevance of environmental controls on ICVLo. We quantified two ecological implications of ICVLo (difference in terms of radiation received and exposure to late frost), which should be explored in the context of ongoing climate change, which affects trees differently according to their phenological niche.

First geological survey and characterisation of a giant depression in carbonate strata at the Rio Grande Rise (southwestern Atlantic) - Alexandre Henrique Ferraz; Christian Millo; Paulo César Fonseca Giannini; Thales Chamarelli Felipe; André Luiz Silva Pestilho; Lena Virgínia Soares Monteiro; Carina Ulsen; Bramley J. Murton; Luigi Jovane (Geomorphology, 2024)

Molecular events accompanying aggregation-induced energy quenching in fucoxanthin-chlorophyll proteins - Maxime T.A. Alexandre; Tjaart P.J. Krüger; Andrew A. Pascal; Vasyl Veremeienko; Manuel J. Llansola-Portoles; Kathi Gundermann; Rienk van Grondelle; Claudia Büchel; Bruno Robert (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Upwelling-induced inflow pulses in a tropical bay during mid-summer drought - Alexandre Tisseaux-Navarro; Braulio Juárez; J. Mauro Vargas-Hernández; Sergio Cambronero-Solano; Mario Espinoza; Amaia Ruiz de Alegría-Arzaburu; Juan Pablo Salazar-Ceciliano (Regional Studies in Marine Science, 2024)

Variability of faecal microbiota and antibiotic resistance genes in flocks of migratory gulls and comparison with the surrounding environment - Dayana Jarma; Oriol Sacristán-Soriano; Carles M. Borrego; Francisco Hortas; Juan M. Peralta-Sánchez; José L. Balcázar; Andy J. Green; Esteban Alonso; Alexandre Sánchez-Melsió; Marta I. Sánchez (Environmental Pollution, 2024)

Experimental and numerical study of a base-isolated building subjected to vibrations induced by railway traffic - Paulo J. Soares; Robert Arcos; Pedro Alves Costa; Kenny F. Conto; Hassan Liravi; Aires Colaço; Alexandre Castanheira-Pinto; Luís Godinho; Joan Cardona (Engineering Structures, 2024)

Host diet drives gut microbiome convergence between coral reef fishes and mammals - Samuel Degregori; Nina M. D. Schiettekatte; Jordan M. Casey; Simon J. Brandl; Alexandre Mercière; Katherine R. Amato; Florent Mazel; Valeriano Parravicini; Paul H. Barber (Molecular Ecology, 2024)
Animal gut microbiomes are critical to host physiology and fitness. The gut microbiomes of fishes—the most abundant and diverse vertebrate clade—have received little attention relative to other clades. Coral reef fishes, in particular, make up a wide range of evolutionary histories and feeding ecologies that are likely associated with gut microbiome diversity. The repeated evolution of herbivory in fishes and mammals also allows us to examine microbiome similarity in relationship to diet across the entire vertebrate tree of life. Here, we generate a large coral reef fish gut microbiome dataset ( n = 499 samples, 19 species) and combine it with a diverse aggregation of public microbiome data ( n = 447) to show that host diet drives significant convergence between coral reef fish and mammalian gut microbiomes. We demonstrate that this similarity is largely driven by carnivory and herbivory and that herbivorous and carnivorous hosts exhibit distinct microbial compositions across fish and mammals. We also show that fish and mammal gut microbiomes share prominent microbial taxa, including Ruminoccocus spp. and Akkermansia spp., and predicted metabolic pathways. Despite the major evolutionary and ecological differences between fishes and mammals, our results reveal that their gut microbiomes undergo similar dietary selective pressures. Thus, diet, in addition to phylosymbiosis must be considered even when comparing the gut microbiomes of distantly related hosts.

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

What do women want to see in a personalized breast cancer risk report? A qualitative study of Asian women of two countries - Fatma Aldila; Fiona Ng FJ; Jessica Audrienna; Lynn Lim SJ; Shannon Tang; Sabrina Gabriel Tanu; Eric Aria Fernandez; Faustina Audrey Agatha; Marco Wijaya; Stevany Tiurma Br Sormin; Levana Sani; Astrid Irwanto; et al. (Journal of Community Genetics, 2024)

Orange (Citrus sinensis) essential oil inclusion in high-energy diets for feedlot lambs: productivity, eating behavior, carcass characteristics, rumen morphometry, and fatty acid profile of the meat - Paulo César G. Dias Junior; Adrielly L.A. da Silva; Isabela J. dos Santos; Leticia C.B. Soares; Matheus S.P. Carlis; Ana Carolina S. Vicente; Terezinha T. de Souza; Rhaissa G. de Assis; Janaina S. Biava; Simon Quigley; Alexandre V. Pires; Evandro M. Ferreira (Small Ruminant Research, 2024)

Recent deep-sea nematodes and agglutinated foraminifera select specific grains and bioclasts from their environments: Ecological implications - Sunil K. Das; Raj K. Singh; Mariem Saavedra-Pellitero; Julia Gottschalk; Carlos A. Alvarez Zarikian; Lester Lembke-Jene; Frank Lamy; Gisela Winckler; Jennifer L. Middleton; Helge W. Arz; Chandranath Basak; Anieke Brombacher; et al. (Marine Micropaleontology, 2024)

Draw me an oxidoreductase reacting with quinones - Marianne Broc; Michael V. Cherrier; Alexandre Uzel; Rodrigo Arias-Cartin; Pascal Arnoux; Gaël Brasseur; Farida Seduk; Bruno Guigliarelli; Stéphane Grimaldi; Pierre Legrand; Fabien Pierrel; Guy Schoen; et al. (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Re-domestication of feral pigs in Martinique: first results of growing-finishing trials to test meat consumption and consumers’ perceptions - N. Degras; K. Benony; M. Bructer; B. Bocage; C. Biamba; G. Alexandre; J-L. Gourdine (Tropical Animal Health and Production, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Optimizing ReBreed21 II: Fertility and reproductive efficiency in different parities during a shortened breeding season in beef cattle - João Paulo N. Andrade; Pedro J.L. Monteiro; Alexandre B. Prata; Adelino J. Robl; José Neto; Beatriz Lippe; Heuller S. Ribeiro; Diego Hartmman; Roberto Sartori; Milo C. Wiltbank (Theriogenology, 2024)

Late Miocene to Early Pliocene paleoceanographic evolution of the Central South Pacific: A deep-sea benthic foraminiferal perspective - Sunil K. Das; N. Mahanta; B. Sahoo; Raj K. Singh; Carlos A. Alvarez Zarikian; Manish Tiwari; Nishant Vats; Nihal; Frank Lamy; Gisela Winckler; Jennifer L. Middleton; Helge W. Arz; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Exploring Tailings Dam Stability Considering Uncertainties in the Critical State Parameters of the NorSand Model - Alexandre V. Silva; Guilherme J. C. Gomes; Jackeline R. C. Huertas; Eduardo S. Cândido (Geotechnical and Geological Engineering, 2024)

Follicular DNA Damage and Pesticide Exposure Among Latinx Children in Rural and Urban Communities - Cassandra Lepetit; Mohamed Gaber; Ke Zhou; Haiying Chen; Julia Holmes; Phillip Summers; Kim A. Anderson; Richard P. Scott; Carey N. Pope; Kirstin Hester; Paul J. Laurienti; Sara A. Quandt; et al. (Exposure and Health, 2024)
The intersectional risks of children in United States immigrant communities include environmental exposures. Pesticide exposures and their biological outcomes are not well characterized in this population group. We assessed pesticide exposure and related these exposures to DNA double-strand breaks (DSBs) in Latinx children from rural, farmworker families (FW; N = 30) and from urban, non-farmworker families (NFW; N = 15) living in North Carolina. DSBs were quantified in hair follicular cells by immunostaining of 53BP1, and exposure to 72 pesticides and pesticide degradation products were determined using silicone wristbands. Cholinesterase activity was measured in blood samples. DSB frequencies were higher in FW compared to NFW children. Seasonal effects were detected in the FW group, with highest DNA damage levels in April–June and lowest levels in October–November. Acetylcholinesterase depression had the same seasonality and correlated with follicular DNA damage. Organophosphate pesticides were more frequently detected in FW than in NFW children. Participants with organophosphate detections had increased follicular DNA damage compared to participants without organophosphate detection. Follicular DNA damage did not correlate with organochlorine or pyrethroid detections and was not associated with the total number of pesticides detected in the wristbands. These results point to rural disparities in pesticide exposures and their outcomes in children from vulnerable immigrant communities. They suggest that among the different classes of pesticides, organophosphates have the strongest genotoxic effects. Assessing pesticide exposures and their consequences at the individual level is key to environmental surveillance programs. To this end, the minimally invasive combined approach used here is particularly well suited for children.

A new exposure protocol adapted for wild bees reveals species-specific impacts of the sulfoximine insecticide sulfoxaflor - Justine Dewaele; Alexandre Barraud; Sara Hellström; Robert J. Paxton; Denis Michez (Ecotoxicology, 2024)
Wild bees are crucial pollinators of flowering plants and concerns are rising about their decline associated with pesticide use. Interspecific variation in wild bee response to pesticide exposure is expected to be related to variation in their morphology, physiology, and ecology, though there are still important knowledge gaps in its understanding. Pesticide risk assessments have largely focussed on the Western honey bee sensitivity considering it protective enough for wild bees. Recently, guidelines for Bombus terrestris and Osmia bicornis testing have been developed but are not yet implemented at a global scale in pesticide risk assessments. Here, we developed and tested a new simplified method of pesticide exposure on wild bee species collected from the field in Belgium. Enough specimens of nine species survived in a laboratory setting and were exposed to oral and topical acute doses of a sulfoximine insecticide. Our results confirm significant variability among wild bee species. We show that Osmia cornuta is more sensitive to sulfoxaflor than B. terrestris , whereas Bombus hypnorum is less sensitive. We propose hypotheses on the mechanisms explaining interspecific variations in sensitivity to pesticides. Future pesticide risk assessments of wild bees will require further refinement of protocols for their controlled housing and exposure.

Correction: Granzyme B degrades extracellular matrix and promotes inflammation and choroidal neovascularization - Gideon Obasanmi; Manjosh Uppal; Jing Z. Cui; Jeanne Xi; Myeong Jin Ju; Jun Song; Eleanor To; Siqi Li; Wania Khan; Darian Cheng; John Zhu; Lyden Irani; et al. (Angiogenesis, 2024)

Granzyme B degrades extracellular matrix and promotes inflammation and choroidal neovascularization - Gideon Obasanmi; Manjosh Uppal; Jing Z. Cui; Jeanne Xi; Myeong Jin Ju; Jun Song; Eleanor To; Siqi Li; Wania Khan; Darian Cheng; John Zhu; Lyden Irani; et al. (Angiogenesis, 2024)
Age-related macular degeneration (AMD) is a common retinal neurodegenerative disease among the elderly. Neovascular AMD (nAMD), a leading cause of AMD-related blindness, involves choroidal neovascularization (CNV), which can be suppressed by anti-angiogenic treatments. However, current CNV treatments do not work in all nAMD patients. Here we investigate a novel target for AMD. Granzyme B (GzmB) is a serine protease that promotes aging, chronic inflammation and vascular permeability through the degradation of the extracellular matrix (ECM) and tight junctions. Extracellular GzmB is increased in retina pigment epithelium (RPE) and mast cells in the choroid of the healthy aging outer retina. It is further increased in donor eyes exhibiting features of nAMD and CNV. Here, we show in RPE-choroidal explant cultures that exogenous GzmB degrades the RPE-choroid ECM, promotes retinal/choroidal inflammation and angiogenesis while diminishing anti-angiogenic factor, thrombospondin-1 (TSP-1). The pharmacological inhibition of either GzmB or mast-cell degranulation significantly reduces choroidal angiogenesis. In line with our in vitro data, GzmB-deficiency reduces the extent of laser-induced CNV lesions and the age-related deterioration of electroretinogram (ERG) responses in mice. These findings suggest that targeting GzmB, a serine protease with no known endogenous inhibitors, may be a potential novel therapeutic approach to suppress CNV in nAMD.

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Comparison of green solvents for the revalorization of orange by-products: Carotenoid extraction and in vitro antioxidant activity - Adriana Viñas-Ospino; Ana Rita Jesus; Alexandre Paiva; Maria J Esteve; Ana Frígola; Jesús Blesa; Daniel López-Malo (Food Chemistry, 2024)

The potential contribution of aquatic wildlife to antibiotic resistance dissemination in freshwater ecosystems: A review - Alexandre J. Thibodeau; Maialen Barret; Florence Mouchet; Van Xuan Nguyen; Eric Pinelli (Environmental Pollution, 2024)

The influence of olivine settling on the formation of basaltic cumulates revealed by micro-tomography and numerical simulations - Adrien J. Mourey; Alexandre Carrara; Thomas Shea; Fidel Costa; Marc-Antoine Longpré (Journal of Volcanology and Geothermal Research, 2024)

Capacity of community health centers to treat snakebite envenoming in indigenous territories of the Brazilian Amazon - André Sachett; Eleanor Strand; Thiago Serrão-Pinto; Alexandre da Silva Neto; Thais Pinto Nascimento; Sewbert Rodrigues Jati; Gisele dos Santos Rocha; Sediel Ambrósio Andrade; Fan Hui Wen; Manuela Berto Pucca; João Vissoci; Charles J. Gerardo; et al. (Toxicon, 2024)

Relational place-based solutions for environmental policy misalignments - Hannah M. Kobluk; Anne K. Salomon; Adam T. Ford; Andrew N. Kadykalo; Mateen A. Hessami; Pierre-Alexandre Labranche; Carmen Richter; Wendy J. Palen; ḥapinyuuk Tommy Happynook; Murray M. Humphries; Elena M. Bennett (Trends in Ecology & Evolution, 2024)

Winged resistance: Storks and gulls increase carriage of antibiotic resistance by shifting from paddy fields to landfills - Oriol Sacristán-Soriano; Dayana Jarma; Marta I. Sánchez; Noelia Romero; Esteban Alonso; Andy J. Green; Alexandre Sànchez-Melsió; Francisco Hortas; José Luis Balcázar; Juan Manuel Peralta-Sánchez; Carles M. Borrego (Science of The Total Environment, 2024)

Drivers and human impacts on topsoil bacterial and fungal community biogeography across Australia - Peipei Xue; Budiman Minasny; Alexandre M. J.‐C. Wadoux; Mercedes Román Dobarco; Alex McBratney; Andrew Bissett; Patrice de Caritat (Global Change Biology, 2024)
Soil microbial diversity mediates a wide range of key processes and ecosystem services influencing planetary health. Our knowledge of microbial biogeography patterns, spatial drivers and human impacts at the continental scale remains limited. Here, we reveal the drivers of bacterial and fungal community distribution in Australian topsoils using 1384 soil samples from diverse bioregions. Our findings highlight that climate factors, particularly precipitation and temperature, along with soil properties, are the primary drivers of topsoil microbial biogeography. Using random forest machine‐learning models, we generated high‐resolution maps of soil bacteria and fungi across continental Australia. The maps revealed microbial hotspots, for example, the eastern coast, southeastern coast, and west coast were dominated by Proteobacteria and Acidobacteria. Fungal distribution is strongly influenced by precipitation, with Ascomycota dominating the central region. This study also demonstrated the impact of human modification on the underground microbial community at the continental scale, which significantly increased the relative abundance of Proteobacteria and Ascomycota, but decreased Chloroflexi and Basidiomycota. The variations in microbial phyla could be attributed to distinct responses to altered environmental factors after human modifications. This study provides insights into the biogeography of soil microbiota, valuable for regional soil biodiversity assessments and monitoring microbial responses to global changes.

Local attitudes towards conservation governance in a large tropical multiple-use Marine Protected Area in Brazil - José Gilmar Cavalcante de Oliveira Júnior; Ana Paula de Oliveira Santos; Ana Claudia Mendes Malhado; Carolina Neves Souza; Chiara Bragagnolo; Aline Olímpio dos Santos; Evelynne Letícia dos Santos Farias Cardoso de Barros; Felipe Alexandre Santos Vieira; Inaê Farias Vieira Dantas; Jacqueline Costa Aldabalde; João Vitor Campos-Silva; Johnny Antonio da Silva Lima; et al. (Ocean & Coastal Management, 2024)

Reclassifying historical disasters: From single to multi-hazards - Ryan Lee; Christopher J. White; Mohammed Sarfaraz Gani Adnan; John Douglas; Miguel D. Mahecha; Fiachra E. O'Loughlin; Edoardo Patelli; Alexandre M. Ramos; Matthew J. Roberts; Olivia Martius; Enrico Tubaldi; Bart van den Hurk; et al. (Science of The Total Environment, 2024)

Comparison of the impact of UV-light emitting diode and UV lamp at pilot-plant scale level on quality parameters and consumer perception of fresh chicken meat - Arturo B. Soro; Cristina Botinestean; Sajad Shokri; Alexandre Juge; Shay Hannon; Paul Whyte; Declan J. Bolton; Paula Bourke; Mahesha M. Poojary; Brijesh K. Tiwari (Food Chemistry, 2024)

Mating system and inbreeding depression in Hymenaea stigonocarpa - Darlin U.G. Zaruma; Alexandre M. Sebbenn; Bruno C. Rossini; Ana C.F. Pardo; Marcela A.M. Silvestre; Jose Cambuim; Alexandre M. da Silva; Silvelise Pupin; Carlos J. Rodrigues; Celso L. Marino; Mário L.T. de Moraes (Tree Genetics & Genomes, 2024)

Global patterns and environmental drivers of forest functional composition - Elise Bouchard; Eric B. Searle; Pierre Drapeau; Jingjing Liang; Javier G. P. Gamarra; Meinrad Abegg; Giorgio Alberti; Angelica Almeyda Zambrano; Esteban Alvarez‐Davila; Luciana F. Alves; Valerio Avitabile; Gerardo Aymard; et al. (Global Ecology and Biogeography, 2024)
Aim To determine the relationships between the functional trait composition of forest communities and environmental gradients across scales and biomes and the role of species relative abundances in these relationships. Location Global. Time period Recent. Major taxa studied Trees. Methods We integrated species abundance records from worldwide forest inventories and associated functional traits (wood density, specific leaf area and seed mass) to obtain a data set of 99,953 to 149,285 plots (depending on the trait) spanning all forested continents. We computed community‐weighted and unweighted means of trait values for each plot and related them to three broad environmental gradients and their interactions (energy availability, precipitation and soil properties) at two scales (global and biomes). Results Our models explained up to 60% of the variance in trait distribution. At global scale, the energy gradient had the strongest influence on traits. However, within‐biome models revealed different relationships among biomes. Notably, the functional composition of tropical forests was more influenced by precipitation and soil properties than energy availability, whereas temperate forests showed the opposite pattern. Depending on the trait studied, response to gradients was more variable and proportionally weaker in boreal forests. Community unweighted means were better predicted than weighted means for almost all models. Main conclusions Worldwide, trees require a large amount of energy (following latitude) to produce dense wood and seeds, while leaves with large surface to weight ratios are concentrated in temperate forests. However, patterns of functional composition within‐biome differ from global patterns due to biome specificities such as the presence of conifers or unique combinations of climatic and soil properties. We recommend assessing the sensitivity of tree functional traits to environmental changes in their geographic context. Furthermore, at a given site, the distribution of tree functional traits appears to be driven more by species presence than species abundance.

Soil δ15N spatial distribution is primarily shaped by climatic patterns in the semiarid Caatinga, Northeast Brazil - Alexandre T. Brunello; Gabriela B. Nardoto; Fábio Luís S. Santos; João Paulo Sena-Souza; Carlos A.N. Quesada; Jonathan J. Lloyd; Tomas F. Domingues (Science of The Total Environment, 2024)

The deep dive of organohalogen compounds: Bioaccumulation in the top predators of mesopelagic trophic webs, pygmy and dwarf sperm whales, from the Southwestern Atlantic ocean - Nara de Oliveira-Ferreira; Elitieri B. Santos-Neto; Bárbara M.R. Manhães; Vitor L. Carvalho; Letícia Gonçalves; Pedro V. de Castilho; Eduardo R. Secchi; Silvina Botta; Milton C.C. Marcondes; Adriana C. Colosio; Marta J. Cremer; Haydée A. Cunha; et al. (Chemosphere, 2023)

N-acylhydrazone derivative modulates cell cycle regulators promoting mitosis arrest and apoptosis in estrogen positive MCF-7 breast cancer cells - Melissa Lúcia Melo; Rafael Fonseca; Fernanda Pauli; Bruno Zavan; João Adolfo Costa Hanemann; Marta Miyazawa; Ester Siqueira Caixeta; Júlia Louise Moreira Nacif; Alexandre Ferro Aissa; Eliezer J. Barreiro; Marisa Ionta (Toxicology in Vitro, 2023)

Brominated flame retardants and natural organobrominated compounds in a vulnerable delphinid species along the Brazilian coast - Lara G. Vidal; Nara De Oliveira-Ferreira; João Paulo M. Torres; Alexandre F. Azevedo; Ana Carolina O. Meirelles; Leonardo Flach; Camila Domit; Ana Bernadete L. Fragoso; Flávio J. Lima Silva; Vítor Luz Carvalho; Milton Marcondes; Lupércio A. Barbosa; et al. (Science of The Total Environment, 2023)

Antimicrobial and Antibiofilm Activities of Copper(II)-1,10-phenanthroline-5,6-pione Against Commensal Bacteria and Fungi Responsible for Vaginal Microbiota Dysbiosis - Graziela V. Rigo; Fernanda G. Cardoso; Michael Devereux; Malachy McCann; Alexandre J. Macedo; André L. S. Santos; Tiana Tasca (Current Microbiology, 2023)

Ericoid shrub encroachment shifts aboveground–belowground linkages in three peatlands across Europe and Western Siberia - Alexandre Buttler; Luca Bragazza; Fatima Laggoun‐Défarge; Sebastien Gogo; Marie‐Laure Toussaint; Mariusz Lamentowicz; Bogdan H. Chojnicki; Michał Słowiński; Sandra Słowińska; Małgorzata Zielińska; Monika Reczuga; Jan Barabach; et al. (Global Change Biology, 2023)
In northern peatlands, reduction of Sphagnum dominance in favour of vascular vegetation is likely to influence biogeochemical processes. Such vegetation changes occur as the water table lowers and temperatures rise. To test which of these factors has a significant influence on peatland vegetation, we conducted a 3‐year manipulative field experiment in Linje mire (northern Poland). We manipulated the peatland water table level (wet, intermediate and dry; on average the depth of the water table was 17.4, 21.2 and 25.3 cm respectively), and we used open‐top chambers (OTCs) to create warmer conditions (on average increase of 1.2°C in OTC plots compared to control plots). Peat drying through water table lowering at this local scale had a larger effect than OTC warming treatment per see on Sphagnum mosses and vascular plants. In particular, ericoid shrubs increased with a lower water table level, while Sphagnum decreased. Microclimatic measurements at the plot scale indicated that both water‐level and temperature, represented by heating degree days (HDDs), can have significant effects on the vegetation. In a large‐scale complementary vegetation gradient survey replicated in three peatlands positioned along a transitional oceanic–continental and temperate–boreal (subarctic) gradient (France–Poland–Western Siberia), an increase in ericoid shrubs was marked by an increase in phenols in peat pore water, resulting from higher phenol concentrations in vascular plant biomass. Our results suggest a shift in functioning from a mineral‐N‐driven to a fungi‐mediated organic‐N nutrient acquisition with shrub encroachment. Both ericoid shrub encroachment and higher mean annual temperature in the three sites triggered greater vascular plant biomass and consequently the dominance of decomposers (especially fungi), which led to a feeding community dominated by nematodes. This contributed to lower enzymatic multifunctionality. Our findings illustrate mechanisms by which plants influence ecosystem responses to climate change, through their effect on microbial trophic interactions.

The divergent effects of nitrate and ammonium application on mercury methylation, demethylation, and reduction in flooded paddy slurries - Ji Chen; Gongren Hu; Jiang Liu; Alexandre J. Poulain; Qiang Pu; Rong Huang; Bo Meng; Xinbin Feng (Journal of Hazardous Materials, 2023)

Residency, home range and inter-annual fidelity of three coastal fish species in a Mediterranean coastal lagoon - Alexandre Mignucci; Fabien Forget; Rémi Villeneuve; Olivier Derridj; Christopher W. McKindsey; David J. McKenzie; Jérôme Bourjea (Estuarine, Coastal and Shelf Science, 2023)

High cold tolerance and differential population response of third instars from the Zeugodacus tau complex to phytosanitary cold treatment in navel oranges - Vanessa S. Dias; Guy J. Hallman; Alexandre S. Araújo; Inajara V.G. Lima; Fabio L. Galvão-Silva; Luis A. Caravantes; Martha N.G. Rivera; Jhonatan S. Aguilar; Carlos E. Cáceres-Barrios; Marc J.B. Vreysen; Scott W. Myers (Postharvest Biology and Technology, 2023)

Being certain about uncertainties: a robust evaluation method for high-dose-rate prostate brachytherapy treatment plans including the combination of uncertainties - Andrew C. Kennedy; Michael J. J. Douglass; Alexandre M. C. Santos (Physical and Engineering Sciences in Medicine, 2023)
In high-dose-rate (HDR) prostate brachytherapy the combined effect of uncertainties cause a range of possible dose distributions deviating from the nominal plan, and which are not considered during treatment plan evaluation. This could lead to dosimetric misses for critical structures and overdosing of organs at risk. A robust evaluation method to assess the combination of uncertainties during plan evaluation is presented and demonstrated on one HDR prostate ultrasound treatment plan retrospectively. A range of uncertainty scenarios are simulated by changing six parameters in the nominal plan and calculating the corresponding dose distribution. Two methods are employed to change the parameters, a probabilistic approach using random number sampling to evaluate the likelihood of variation in dose distributions, and a combination of the most extreme possible values to access the worst-case dosimetric outcomes. One thousand probabilistic scenarios were run on the single treatment plan with 43.2% of scenarios passing seven of the eight clinical objectives. The prostate D 90 had a standard deviation of 4.4%, with the worst case decreasing the dose by up to 27.2%. The urethra D 10 was up to 29.3% higher than planned in the worst case. All DVH metrics in the probabilistic scenarios were found to be within acceptable clinical constraints for the plan under statistical tests for significance. The clinical significance of the results from the robust evaluation method presented on any individual treatment plan needs to be compared in the context of a historical data set that contains patient outcomes with robustness analysis data to ascertain a baseline acceptance.

The moderating role of macronutrient intake in relation to body composition and genotoxicity: A study with gym users - Diene da Silva Schlickmann; Patrícia Molz; Gabriela Cristina Uebel; Caroline Santos; Caroline Brand; Renato Alberto Weber Colombelli; Thalia Gama da Silva; Juliana Priebe Steffens; Eduarda da Silva Limberger Castilhos; Pedro J. Benito; Alexandre Rieger; Silvia Isabel Rech Franke (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2023)

Coastal upwelling influences population structure of dusky grouper Epinephelus marginatus: An integrative approach based on otolith chemistry and muscle stable isotopes - Cristiano Q. Albuquerque; Mario V. Condini; Susanne E. Tanner; Patrick Reis-Santos; Tatiana D. Saint’Pierre; Elisa Seyboth; Bianca Possamai; David J. Hoeinghaus; Alexandre M. Garcia (Marine Environmental Research, 2023)

The interaction between liver cirrhosis, infection by Streptococcus bovis, and colon cancer - Juan Corredoira; Enrique Miguez; Lara María Mateo; Ricardo Fernández-Rodríguez; José Francisco García-Rodríguez; Alexandre Pérez-González; Ana Sanjurjo; María Victoria Pulian; Blanca Ayuso-García; M. Serrano; M. J. Jove; P. Alonso; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Aerial photogrammetry techniques using drones to estimate morphometric measurements and body condition in South American small cetaceans - Lucas L. de Oliveira; Artur Andriolo; Marta J. Cremer; Alexandre N. Zerbini (Marine Mammal Science, 2023)
Aerial photogrammetry protocols using drones have proved efficient in monitoring free‐living cetaceans. In this work an aerial photogrammetry protocol using a drone was applied to estimate morphometric measurements and body condition variation in two endangered cetacean species, franciscanas ( Pontoporia blainvillei , n = 122) and Guiana dolphin ( Sotalia guianensis , n = 41). Sampling occurred in winter and summer in Babitonga Bay, southern Brazil. A 115 cm length object was used to calibrate the scale of measurements at different altitudes. A scale calibration model based on eGSD regression by flight altitude was developed ( RMSE = 0.039, r 2 = 0.9902, ΔAICc = 0.00) and used to convert measurements from pixels to centimeters. Five morphometric measurements (body length ‐ BL, widths at anterior pectoral fin ‐ AP, axilla ‐ AX, anterior dorsal fin ‐ AD, and posterior dorsal fin ‐ PD) were taken from each animal to infer body condition, in which, the widths in the anterior portions of the body as % BL, can be an auxiliary tool in the evaluation of variation in the body condition of the small cetaceans studied. The aerial photogrammetry protocol allowed for estimating morphometric measurements and monitoring seasonal changes in the body condition of the small cetaceans.

Wet brewers’ grains as a source of protein for feedlot lambs: Impacts on intake, apparent nutrient digestibility, ruminal fermentation, and nitrogen balance - Rhaíssa G. de Assis; Isabela J. dos Santos; Jennifer M. Gasparina; Natalia A. Bandoria; Brenda Alves; Paulo C.G. Dias; Ana C.S. Vicente; Letícia C.B. Soares; Daniel M. Polizel; Janaina S. Biava; Alexandre V. Pires; Evandro M. Ferreira (Small Ruminant Research, 2023)

Historical biogeography highlights the role of Miocene landscape changes on the diversification of a clade of Amazonian tree frogs - Diego A. Ortiz; Conrad J. Hoskin; Fernanda P. Werneck; Alexandre Réjaud; Sophie Manzi; Santiago R. Ron; Antoine Fouquet (Organisms Diversity & Evolution, 2023)
The diversification processes underlying why Amazonia hosts the most species-rich vertebrate fauna on earth remain poorly understood. We studied the spatio-temporal diversification of a tree frog clade distributed throughout Amazonia (Anura: Hylidae: Osteocephalus , Tepuihyla , and Dryaderces ) and tested the hypothesis that Miocene mega wetlands located in western and central Amazonia impacted connectivity among major biogeographic areas during extensive periods. We assessed the group’s diversity through DNA-based (16S rRNA) species delimitation to identify Operational Taxonomic Units (OTUs) from 557 individuals. We then selected one terminal for each OTU ( n = 50) and assembled a mitogenomic matrix (~14,100 bp; complete for 17 terminals) to reconstruct a Bayesian, time-calibrated phylogeny encompassing nearly all described species. Ancestral area reconstruction indicates that each genus was restricted to one of the major Amazonian biogeographic areas (western Amazonia, Guiana Shield and Brazilian Shield, respectively) between ~10 and 20 Mya, suggesting that they diverged and diversified in isolation during this period around the Pebas mega wetland. After 10 Mya and the transition to the modern configuration of the Amazon River watershed, most speciation within each genus continued to occur within each area. In Osteocephalus , only three species expanded widely across Amazonia (< 6 Mya), and all were pond-breeders. Species with other breeding modes remained mostly restricted to narrow ranges. The spectacular radiation of Osteocephalus was probably driven by climatic stability, habitat diversity and the acquisition of new reproductive modes along the Andean foothills and western Amazonia. Our findings add evidence to the importance of major hydrological changes during the Miocene on biotic diversification in Amazonia.

Addressing chemical pollution in biodiversity research - Gabriel Sigmund; Marlene Ågerstrand; Alexandre Antonelli; Thomas Backhaus; Tomas Brodin; Miriam L. Diamond; Walter R. Erdelen; David C. Evers; Thilo Hofmann; Thorsten Hueffer; Adelene Lai; Joao P. M. Torres; et al. (Global Change Biology, 2023)
Climate change, biodiversity loss, and chemical pollution are planetary‐scale emergencies requiring urgent mitigation actions. As these “triple crises” are deeply interlinked, they need to be tackled in an integrative manner. However, while climate change and biodiversity are often studied together, chemical pollution as a global change factor contributing to worldwide biodiversity loss has received much less attention in biodiversity research so far. Here, we review evidence showing that the multifaceted effects of anthropogenic chemicals in the environment are posing a growing threat to biodiversity and ecosystems. Therefore, failure to account for pollution effects may significantly undermine the success of biodiversity protection efforts. We argue that progress in understanding and counteracting the negative impact of chemical pollution on biodiversity requires collective efforts of scientists from different disciplines, including but not limited to ecology, ecotoxicology, and environmental chemistry. Importantly, recent developments in these fields have now enabled comprehensive studies that could efficiently address the manifold interactions between chemicals and ecosystems. Based on their experience with intricate studies of biodiversity, ecologists are well equipped to embrace the additional challenge of chemical complexity through interdisciplinary collaborations. This offers a unique opportunity to jointly advance a seminal frontier in pollution ecology and facilitate the development of innovative solutions for environmental protection.

To den or not to den. Contributions to the taphonomic history of the Early Pleistocene site of Venta Micena 4 (Orce, Guadix-Baza Basin) - Jose Yravedra Sainz de los Terreros; Carmen Luzón; Jose A. Solano; Gonzalo J. Linares-Matas; Verónica Estaca-Gomez; Juan José Rodríguez-Alba; Lloyd A. Courtenay; Darío Herranz-Rodrigo; Alexia Serrano-Ramos; José Cámara; Juha Saarinen; Christian Sánchez-Bandera; et al. (Quaternary Science Reviews, 2023)

Multiple origins of mountain biodiversity in New Zealand's largest plant radiation - Anne Thomas; Heidi M. Meudt; Matthew J. Larcombe; Javier Igea; William G. Lee; Alexandre Antonelli; Andrew J. Tanentzap (Journal of Biogeography, 2023)
Aim How mountains accumulate species diversity remains poorly understood, particularly the relative role of in situ cladogenesis compared with colonization from lower elevations. Here, we estimated the contributions of in situ cladogenesis and colonization in generating biodiversity of a large mountain plant radiation and determined the importance of niche adaptation and divergence in these processes. We expected cladogenesis would accompany novel habitats formed by mountain uplift, but colonization would become more important with time as dispersal opportunities accrue. Location New Zealand, Southern Alps. Taxon Veronica sect. Hebe (Plantaginaceae). Methods We estimated the most complete time‐calibrated phylogeny to date for Veronica sect. Hebe to quantify rates of in situ cladogenesis and colonization of mountain habitat based on historical biogeographical models. We used environmental niche modelling to quantify species' climate niches and estimate niche disparity and divergence over time. Results In situ cladogenesis generated more species in the mountains than colonization from lowlands. Whereas cladogenesis slowed over time, colonization increased, especially in the alpine zone. Both adaptive ecological speciation along climate niche axes and non‐adaptive, vicariant speciation contributed to cladogenesis. However, climate niche disparity through time became saturated, suggesting competition for niche space was important. Colonization brought more divergent species into mountain niches. Main Conclusions We suggest mountain diversity accumulates through three main stages: high cladogenesis after initial colonization, decreasing cladogenesis with increasing competition and increasing colonization after niches saturate, likely promoted by niche divergence. Combining lineage and mountain uplift trajectories, these stages provide a conceptual model to understand how diversity accumulates elsewhere. Assuming these deep‐time findings apply to anthropogenic conditions, alpine specialists could struggle to outcompete colonizers facilitated by climate change, especially from generalist clades. Considering novel competitive interactions alongside niche traits and biogeographical processes will be crucial for predicting the fate of alpine biodiversity in a changing world.

Later prehistoric tin mining in the Ervedosa mine (Vinhais, Portugal): evidence and context - Emmanuelle Meunier; Filipa Dias; João Fonte; Alexandre Lima; Alexandra Rodrigues; Carlo Bottaini; Rui J. C. Silva; João P. Veiga; Manuel F. C. Pereira; Elin Figueiredo (Archaeological and Anthropological Sciences, 2023)

Carotid artery stenting during endovascular thrombectomy for acute ischemic stroke with tandem occlusion: the Italian Registry of Endovascular Treatment in Acute Stroke - Fabrizio Sallustio; Giovanni Pracucci; Manuel Cappellari; Valentina Saia; Alfredo Paolo Mascolo; Federico Marrama; Roberto Gandini; Giacomo Koch; Marina Diomedi; Federica D’Agostino; Alessandro Rocco; Valerio Da Ros; et al. (Acta Neurologica Belgica, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

The potential of using Drosophila as bioindicator in a restinga environment - B. G. Alexandre; J. L. Poppe; R. Zanini; V. L. S. Valente; M. Deprá (International Journal of Tropical Insect Science, 2023)

Essential oil from Arnica montana on feedlot performance, ingestive behavior, carcass characteristics, rumen morphometrics characteristics and meat fatty acids profile of lambs - Paulo César G. Dias Junior; Isabela J. dos Santos; Adrielly L.A. da Silva; Rhaissa G. de Assis; Ana Carolina S. Vicente; Matheus S.P. Carlis; Letícia C.B. Soares; Jamile H. Comelli; Janaina S. Biava; Rafael C. Araujo; Alexandre V. Pires; Evandro M. Ferreira (Small Ruminant Research, 2023)

TimeFISH : Long‐term assessment of reef fish assemblages in a transition zone in the Southwestern Atlantic - Juan P. Quimbayo; Lucas T. Nunes; Fernanda C. Silva; Antônio B. Anderson; Diego R. Barneche; Angela M. Canterle; Isadora Cord; Andrea Dalben; Débora S. Ferrari; Luisa Fontoura; Thiago M. J. Fiuza; Ana M. R. Liedke; et al. (Ecology, 2023)
The TimeFISH database provides the first public time‐series dataset on reef fish assemblages in the southwestern Atlantic (SWA), comprising 15 years of data (2007–2022) based on standardized Underwater Visual Censuses (UVCs). The rocky reefs covered by our dataset are influenced by pronounced seasonal cycles of ocean temperatures with warm tropical waters from the Brazil Current in the summer (~27°C) and colder waters from the La Plata River Plume discharge and upwelling from the South Atlantic Central Water in the winter (~18°C). These oceanographic conditions characterize this area as the southernmost tropical–subtropical climatic transition zone in the Atlantic Ocean. As a result, reef fish assemblages are comprised of both tropical and subtropical species. All records included in TimeFISH were collected using UVCs, a nondestructive method that allows the estimation of fish species richness, abundance, and body size distributions. UVCs were performed through 40 m 2 belt transects by scuba diving in nine locations along the southern Brazilian coast (25–29°S). Four of these locations lie within the boundaries of the no‐entry Arvoredo Marine Biological Reserve, where fishing and recreational activities are forbidden, and the remaining locations are unprotected from these activities. During each belt transect, a diver swam at a constant depth above and parallel to the reef, identifying fish species, counting the number of individuals, and estimating the total body length (Lt in cm) of all detected individuals. All fish individuals in the water column (up to 2 m above the substratum) and at the bottom were targeted. In total, 202,965 individuals belonging to 163 reef fish species and 53 families were recorded across 1857 UVCs. All survey campaigns were funded by either public or mixed capital (private–public) sources, including seven grants from the Brazilian federal and Santa Catarina state governments. Part of the data has already been used in multiple MS.c. and Ph.D. theses and scientific articles. TimeFISH represents an important contribution for future studies aiming to examine temporal and spatial variations of reef fish assemblages in transition zones. No copyright restrictions apply to the use of this data set, other than citing this publication.

Spatial analysis of mercury and stable isotopes in the vulnerable Dusky Grouper Epinephelus marginatus along the Brazilian coast - Mario V. Condini; Christopher R. Malinowski; David J. Hoeinghaus; Brittany L. Harried; Aaron P. Roberts; Brianne K. Soulen; Kathleen J. Roark; Alexis J. Khursigara; Luciano G. Fischer; Bianca Possamai; Maurício Hostim-Silva; Alexandre M. Garcia (Marine Pollution Bulletin, 2023)

Essential oil from Arnica montana alters the protein metabolism in lambs fed with high-concentrate diets - Paulo César G. Dias Junior; Isabela J. dos Santos; Jennifer M. Gasparina; Natália A. Bandoria; Letícia C.B. Soares; Adrielly L.A. da Silva; Rhaissa G. de Assis; Daniel M. Polizel; Janaina S. Biava; Alexandre V. Pires; Evandro M. Ferreira (Small Ruminant Research, 2023)

Machine learning directed multi-objective optimization of mixed variable chemical systems - Oliver J. Kershaw; Adam D. Clayton; Jamie A. Manson; Alexandre Barthelme; John Pavey; Philip Peach; Jason Mustakis; Roger M. Howard; Thomas W. Chamberlain; Nicholas J. Warren; Richard A. Bourne (Chemical Engineering Journal, 2023)

Upscaling Mixing-Controlled Reactions in Unsaturated Porous Media - Lazaro J. Perez; Alexandre Puyguiraud; Juan J. Hidalgo; Joaquín Jiménez-Martínez; Rishi Parashar; Marco Dentz (Transport in Porous Media, 2023)
We study mixing-controlled chemical reactions in unsaturated porous media from a pore-scale perspective. The spatial heterogeneity induced by the presence of two immiscible phases, here water and air, in the pore space generates complex flow patterns that dominate reactive mixing across scales. To assess the impact of different macroscopic saturation states (the fraction of pore volume occupied by water) on mixing-controlled chemical reactions, we consider a fast irreversible reaction between two initially segregated dissolved species that mix as one solution displaces the other in the heterogeneous flow field of the water phase. We use the pore-scale geometry and water distributions from the laboratory experiments reported by Jiménez-Martínez et al. (Geophys. Res. Lett. 42: 5316–5324, 2015). We analyze reactive mixing in three complementary ways. Firstly, we post-process experimentally observed spatially distributed concentration data; secondly, we perform numerical simulations of flow and reactive transport in the heterogeneous water phase, and thirdly, we use an upscaled mixing model. The first approach relies on an exact algebraic map between conservative and reactive species for an instantaneous irreversible bimolecular reaction that allows to estimate reactive mixing based on experimental conservative transport data. The second approach is based on reactive random walk particle tracking simulations in the numerically determined flow field in the water phase. The third approach uses a dispersive lamella approach that accounts for the impact of flow heterogeneity on mixing in terms of effective dispersion coefficients, which are estimated from both experimental data and numerical random walk particle tracking simulations. We observe a significant increase in reactive mixing for decreasing saturation, which is caused by the stronger heterogeneity of the water phase and thus of the flow field. This is consistently observed in the experimental data and the direct numerical simulations. The dispersive lamella model, parameterized by the effective interface width, provides robust estimates of the evolution of the product mass obtained from the experimental and numerical data.

Winter wheat evapotranspiration and irrigation requirements across tropical and sub-tropical producing regions in Brazil - Rodolfo A. A. Pereira; Evandro H. F. M. Silva; Alexandre O. Gonçalves; Murilo S. Vianna; Tonny J. A. Silva; William Fenner; Paulo V. D. Vieira; Fábio R. Marin (Theoretical and Applied Climatology, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Silicon amendment induces resistance in rice to Diatraea saccharalis (Lepidoptera: Crambidae) - Ana Paula Pelosi; Franciele Cristina da Silva; Adriana G. Vaz; André Cirilo S. Almeida; Anderson Rodrigo da Silva; Michael J. Stout; Flávio G. de Jesus; José Alexandre F. Barrigossi (Arthropod-Plant Interactions, 2022)

Dispersal syndromes in challenging environments: A cross‐species experiment - Julien Cote; Maxime Dahirel; Nicolas Schtickzelle; Florian Altermatt; Armelle Ansart; Simon Blanchet; Alexis S. Chaine; Frederik De Laender; Jonathan De Raedt; Bart Haegeman; Staffan Jacob; Oliver Kaltz; et al. (Ecology Letters, 2022)
Dispersal is a central biological process tightly integrated into life‐histories, morphology, physiology and behaviour. Such associations, or syndromes, are anticipated to impact the eco‐evolutionary dynamics of spatially structured populations, and cascade into ecosystem processes. As for dispersal on its own, these syndromes are likely neither fixed nor random, but conditional on the experienced environment. We experimentally studied how dispersal propensity varies with individuals' phenotype and local environmental harshness using 15 species ranging from protists to vertebrates. We reveal a general phenotypic dispersal syndrome across studied species, with dispersers being larger, more active and having a marked locomotion‐oriented morphology and a strengthening of the link between dispersal and some phenotypic traits with environmental harshness. Our proof‐of‐concept metacommunity model further reveals cascading effects of context‐dependent syndromes on the local and regional organisation of functional diversity. Our study opens new avenues to advance our understanding of the functioning of spatially structured populations, communities and ecosystems.

Co-design of a marine protected area zoning and the lessons learned from it - Barbara Horta e Costa; M. Helena Guimarães; Mafalda Rangel; Adriana Ressurreição; Pedro Monteiro; Frederico Oliveira; Luís Bentes; Nuno Sales Henriques; Inês Sousa; Sofia Alexandre; João Pontes; Carlos M. L. Afonso; et al. (Frontiers in Marine Science, 2022)
Marine Protected Areas (MPAs) are a tool to safeguard marine natural systems, yet their effectiveness depends on how well they are integrated into the existing socioeconomic context. Stakeholder engagement in MPA design can contribute to increasing integration. This study focuses on the co-design of an MPA between researchers, public administration, the private sector, and non-governmental organizations. The proposed MPA is in Portugal and includes an area that is a hotspot for biodiversity and economic activities. This is the first MPA proposal in mainland Portugal co-designed using a participatory approach. This study highlights the steps of the zoning process and synthesizes the eight main lessons learned, useful for other cases, particularly for relatively small coastal MPAs with multiple socioeconomic activities. Three zoning proposals were developed and discussed within the participatory process. The proposals considered the best scientific and local knowledge available and were defined using ecological, socioeconomic, and shape-area guiding principles. In an iterative manner and following a participatory approach, compromises with stakeholders were achieved, and a final proposal, scientifically sound and socially accepted by most stakeholders, was delivered to the government. The final zoning plan will achieve ambitious conservation goals, including the largest fully protected area to be declared in mainland Portugal, while minimizing the impacts on the existing economic activities and promoting its sustainability. This process resulted in valuable lessons that may be applied elsewhere and guide future MPA implementation or rezoning of existing ones. These transdisciplinary and participatory processes can be time and resource-consuming but are vital for ensuring MPA effectiveness.

Global patterns in endemicity and vulnerability of soil fungi - Leho Tedersoo; Vladimir Mikryukov; Alexander Zizka; Mohammad Bahram; Niloufar Hagh‐Doust; Sten Anslan; Oleh Prylutskyi; Manuel Delgado‐Baquerizo; Fernando T. Maestre; Jaan Pärn; Maarja Öpik; Mari Moora; et al. (Global Change Biology, 2022)
Fungi are highly diverse organisms, which provide multiple ecosystem services. However, compared with charismatic animals and plants, the distribution patterns and conservation needs of fungi have been little explored. Here, we examined endemicity patterns, global change vulnerability and conservation priority areas for functional groups of soil fungi based on six global surveys using a high‐resolution, long‐read metabarcoding approach. We found that the endemicity of all fungi and most functional groups peaks in tropical habitats, including Amazonia, Yucatan, West‐Central Africa, Sri Lanka, and New Caledonia, with a negligible island effect compared with plants and animals. We also found that fungi are predominantly vulnerable to drought, heat and land‐cover change, particularly in dry tropical regions with high human population density. Fungal conservation areas of highest priority include herbaceous wetlands, tropical forests, and woodlands. We stress that more attention should be focused on the conservation of fungi, especially root symbiotic arbuscular mycorrhizal and ectomycorrhizal fungi in tropical regions as well as unicellular early‐diverging groups and macrofungi in general. Given the low overlap between the endemicity of fungi and macroorganisms, but high conservation needs in both groups, detailed analyses on distribution and conservation requirements are warranted for other microorganisms and soil organisms.

Widespread Hybridization between Invasive Bleak (Alburnus alburnus) and Iberian Chub (Squalius spp.): A Neglected Conservation Threat - Manuel Curto; Miguel Morgado-Santos; Carlos M. Alexandre; Maria Judite Alves; Hugo F. Gante; Christos Gkenas; João P. Medeiros; Paulo J. Pinheiro; Pedro R. Almeida; Maria Filomena Magalhães; Filipe Ribeiro (Fishes, 2022)
Hybridization between native and nonnative fish species is a major conservation issue, especially in ecosystems with high levels of endemism, such as Iberian streams. To date, hybridization with the invasive bleak Alburnus alburnus has been reported for the Iberian chub Squalius alburnoides and S. pyrenaicus and in scattered locations only. However, the bleak is spreading in the region, potentially increasing the risks of hybridization with other Squalius species. To gather a more comprehensive picture on the current geography of hybridization, we compiled records on hybrids between bleak and chub in Portugal and conducted genetical assessments of hybrids between bleak and S. carolitertii. We found that hybridization with bleak is widespread throughout Portuguese river basins and involves at least S. alburnoides, S. pyrenaicus and S. carolitertii. Hybridization with bleak may not only cause waste of reproductive effort and damage the genetic integrity of these endemic species but also promote shifts in the reproductive dynamics of the S. alburnoides hybrid complex, which includes individuals with various ploidy levels and combinations of parental genomes, reproducing sexually and asexually. We recommend that future studies characterize the fitness of bleak hybrids and their ecological and genetic interactions with native fish, in order to design effective conservation measures.

Impacts of Mercury Exposure Levels and Sources on the Demethylation of Methylmercury Through Human Gut Microbiota - Xian-Feng Yang; Shao-Chen Yang; Fu-Li Wen; Lin Feng; Bo Meng; Hai-Yan Hu; Bao-Lin Wang; Jun Li; Alexandre J. Poulain; Ping Li (Bulletin of Environmental Contamination and Toxicology, 2022)

Andean non‐volant small mammals: A dataset of community assemblages of non‐volant small mammals from the high Andes - Edgardo M. Rengifo; Jorge Brito; J. Pablo Jayat; Raisa Cairampoma; Agustina Novillo; Natali Hurtado; Ignacio Ferro; Cesar E. Medina; Alfonso Arguero; Sergio Solari; Jose Urquizo; Ariatna Villarreal; et al. (Ecology, 2022)
Information from diversity inventories was used to study patterns of biodiversity and species distribution, to identify potential priority areas for conservation, and to guide future sampling efforts. In this context, we compiled information on non‐volant small mammal communities from the high Andes (>2000 m). Here, we present an open source dataset containing information on diversity (species composition, number of individuals captured), inventory design (type of traps, sampling efforts), and environment (habitat) for both unpublished and published information. This study covers 630 mammalian communities, geographically distributed throughout the Andes in Venezuela, Colombia, Ecuador, Peru, Bolivia, Argentina, and Chile. We compiled a total of 26,412 individual records belonging to 240 species; the order with greatest number of records was Rodentia ( n = 25,319, 96.06%), followed by Didelphimorphia ( n = 373, 1.42%), Eulipotyphla ( n = 358, 1.36%) and Paucituberculata, ( n = 307, 1.16%). Andean non‐volant small mammal communities harbor a range from 1 to 17 species, with 93.06% of sites being composed of one to five species, 27.78% of sites with species richness varying from 6 to 10 species, and 4.17% sites composed of more than 10 species. Multiple sampling methods were used to survey non‐volant small mammals; the most representative methods were snap‐traps and Sherman traps, or a combination of both, in more than 81% of the studies. This data paper represents the first large dataset of faunal species inventories for the Andes. There are no copyright restrictions associated with the use of this dataset. Please cite this data paper when its data are used total or partially in research or teaching.

Impact of infectious diseases consultation among patients with infections caused by gram-negative rod bacteria: a systematic literature review and meta-analysis - Shinya Hasegawa; Satoshi Kakiuchi; Joseph Tholany; Takaaki Kobayashi; Alexandre R. Marra; Marin L. Schweizer; Riley J. Samuelson; Hiroyuki Suzuki (Infectious Diseases, 2022)

Diffusion of H 2 S from anaerobic thiolated ligand biodegradation rapidly generates bioavailable mercury - Benjamin R. Stenzler; Rui Zhang; Jeremy D. Semrau; Alan A. DiSpirito; Alexandre J. Poulain (Environmental Microbiology, 2022)
Summary Methylmercury is a potent neurotoxin that biomagnifies through food webs and which production depends on anaerobic microbial uptake of inorganic mercury (Hg) species. One outstanding knowledge gap in understanding Hg methylation is the nature of bioavailable Hg species. It has become increasingly obvious that Hg bioavailability is spatially diverse and temporally dynamic but current models are mostly built on single thiolated ligand systems, omitting ligand exchanges and interactions, or the inclusion of dissolved gaseous phases. In this study, we used a whole‐cell anaerobic biosensor to determine the role of a mixture of thiolated ligands on Hg bioavailability. Serendipitously, we discovered how the diffusion of trace amounts of exogenous biogenic H 2 S, originating from anaerobic microbial ligand degradation, can alter Hg speciation – away from H 2 S production site – to form bioavailable species. Regardless of its origins, H 2 S stands as a mobile mediator of microbial Hg metabolism, connecting spatially separated microbial communities. At a larger scale, global planetary changes are expected to accelerate the production and mobilization of H 2 S and Hg, possibly leading to increased production of the potent neurotoxin; this work provides mechanistic insights into the importance of co‐managing biogeochemical cycle disruptions.

Missing Data in Sea Turtle Population Monitoring: A Bayesian Statistical Framework Accounting for Incomplete Sampling - Lucy C. M. Omeyer; Trevelyan J. McKinley; Nathalie Bréheret; Gaëlle Bal; George Petchell Balchin; Abdon Bitsindou; Eva Chauvet; Tim Collins; Bryan K. Curran; Angela Formia; Alexandre Girard; Marc Girondot; et al. (Frontiers in Marine Science, 2022)
Monitoring how populations respond to sustained conservation measures is essential to detect changes in their population status and determine the effectiveness of any interventions. In the case of sea turtles, their populations are difficult to assess because of their complicated life histories. Ground-derived clutch counts are most often used as an index of population size for sea turtles; however, data are often incomplete with varying sampling intensity within and among sites and seasons. To address these issues, we: (1) develop a Bayesian statistical modelling framework that can be used to account for sampling uncertainties in a robust probabilistic manner within a given site and season; and (2) apply this to a previously unpublished long-term sea turtle dataset (n = 17 years) collated for the Republic of the Congo, which hosts two sympatrically nesting species of sea turtle (leatherback turtle [ Dermochelys coriacea ] and olive ridley turtle [ Lepidochelys olivacea ]). The results of this analysis suggest that leatherback turtle nesting levels dropped initially and then settled into quasi-cyclical levels of interannual variability, with an average of 573 (mean, 95% prediction interval: 554–626) clutches laid annually between 2012 and 2017. In contrast, nesting abundance for olive ridley turtles has increased more recently, with an average of 1,087 (mean, 95% prediction interval: 1,057–1,153) clutches laid annually between 2012 and 2017. These findings highlight the regional and global importance of this rookery with the Republic of the Congo, hosting the second largest documented populations of olive ridley and the third largest for leatherback turtles in Central Africa; and the fourth largest non-arribada olive ridley rookery globally. Furthermore, whilst the results show that Congo’s single marine and coastal national park provides protection for over half of sea turtle clutches laid in the country, there is scope for further protection along the coast. Although large parts of the African coastline remain to be adequately monitored, the modelling approach used here will be invaluable to inform future status assessments for sea turtles given that most datasets are temporally and spatially fragmented.

Exploring the Use of Seabirds as a Dynamic Ocean Management Tool to Mitigate Anthropogenic Risk to Large Whales - Tammy L. Silva; Kevin D. Powers; Jooke Robbins; Regina Asmutis-Silvia; Timothy V. N. Cole; Alex N. Hill; Laura J. Howes; Charles A. Mayo; Dianna Schulte; Michael A. Thompson; Linda J. Welch; Alexandre N. Zerbini; et al. (Frontiers in Marine Science, 2022)
Vessel strike and entanglement in fishing gear are global threats to large whales. United States management actions to reduce human-induced serious injury and mortality to large whales have been inadequate, partially due to static, spatial protection schemes that fail to adjust to distribution shifts of highly mobile animals. Whale conservation would benefit from dynamic ocean management, but few tools exist to inform dynamic approaches. Seabirds are often found in association with whales and can be tagged at lower cost and in higher numbers than whales. We explored the use of satellite-tagged seabirds (great shearwaters) as dynamic ocean management tools for near real-time identification of habitats where humpback and North Atlantic right whales aggregate, potentially increasing anthropogenic risk. We identified shearwater habitat use areas in the Gulf of Maine with 50% kernel density utilization distributions at yearly, monthly, and weekly scales using satellite-telemetry data from 2013-2018. We quantified overlap using whale sightings and whale satellite telemetry data at two spatial scales: Stellwagen Bank National Marine Sanctuary and the Gulf of Maine. Within the sanctuary, shearwaters overlapped with >50% of humpback sightings in 4 of 6 (67%) years, 15 of 23 (65%) months, and 50 of 89 (56%) of weeks. At the Gulf of Maine scale, shearwater use areas overlapped >50% of humpback sightings in 5 of 6 years (83%) and 16 of 22 (73%) months, and encompassed humpback 50% utilization distributions (based on satellite telemetry) in 2 of 3 (66%) years and 7/12 (58%) months analyzed. Overlap between shearwaters and right whales was much lower, with >50% overlap in only 1 of 6 (17%) years and 3 of 23 (13%) months. These initial results demonstrate that satellite-tagged shearwaters can be indicators of humpback whale habitat use in both space and time. With further study, tagged shearwaters may provide near-real time information necessary to operationalize dynamic management to mitigate human impacts on humpback whales.

Role of 5-HT2A receptors in the effects of ayahuasca on ethanol self-administration using a two-bottle choice paradigm in male mice - Yasmim A. Serra; Thaísa Barros-Santos; Alexia Anjos-Santos; Natali D. Kisaki; Caio Jovita-Farias; João P. C. Leite; Maria C. E. Santana; João P. S. A. Coimbra; Nailton M. S. de Jesus; Agnieszka Sulima; Paulo C. R. Barbosa; Elena L. A. Malpezzi-Marinho; et al. (Psychopharmacology, 2022)

A tubular ceramic membrane coated with TiO2-P25 for radial addition of H2O2 towards AMX removal from synthetic solutions and secondary urban wastewater - Alexandre Diório; Jennyfer Díaz-Angulo; Reynel M. Castellanos; Ana I. Gomes; Rosângela Bergamasco; Marcelo Fernandes Vieira; Márcia Dezotti; Miguel Angel Mueses; Fiderman Machuca-Martinez; Vítor J. P. Vilar (Environmental Science and Pollution Research, 2022)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

First satellite‐tracked movements of pygmy blue whales ( Balaenoptera musculus brevicauda ) in New Zealand waters - Kimberly T. Goetz; Simon J. Childerhouse; David Paton; Mike Ogle; Krista van der Linde; Rochelle Constantine; Michael C. Double; Virginia Andrews‐Goff; Alexandre N. Zerbini; Paula A. Olson (Marine Mammal Science, 2022)

A dosimetric comparison of CT- and photogrammetry- generated 3D printed HDR brachytherapy surface applicators - Corey A. Bridger; Paul D. Reich; Alexandre M. Caraça Santos; Michael J. J. Douglass (Physical and Engineering Sciences in Medicine, 2022)

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Effect of host alternation on fitness of Diaphorina citri (Hemiptera: Psyllidae), huanglongbing bacterium vector - Juliana S. Oliveira; Carolina Reigada; Alexandre J. F. Diniz; José R. P. Parra (Applied Entomology and Zoology, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Estimating Bycatch Mortality for Marine Mammals: Concepts and Best Practices - Jeffrey E. Moore; Dennis Heinemann; Tessa B. Francis; Philip S. Hammond; Kristy J. Long; André E. Punt; Randall R. Reeves; Maritza Sepúlveda; Guðjón Már Sigurðsson; Margaret C. Siple; Gísli A. Víkingsson; Paul R. Wade; et al. (Frontiers in Marine Science, 2021)
Fisheries bycatch is the greatest current source of human-caused deaths of marine mammals worldwide, with severe impacts on the health and viability of many populations. Recent regulations enacted in the United States under the Fish and Fish Product Import Provisions of its Marine Mammal Protection Act require nations with fisheries exporting fish and fish products to the United States (hereafter, “export fisheries”) to have or establish marine mammal protection standards that are comparable in effectiveness to the standards for United States commercial fisheries. In many cases, this will require estimating marine mammal bycatch in those fisheries. Bycatch estimation is conceptually straightforward but can be difficult in practice, especially if resources (funding) are limiting or for fisheries consisting of many, small vessels with geographically-dispersed landing sites. This paper describes best practices for estimating bycatch mortality, which is an important ingredient of bycatch assessment and mitigation. We discuss a general bycatch estimator and how to obtain its requisite bycatch-rate and fisheries-effort data. Scientific observer programs provide the most robust bycatch estimates and consequently are discussed at length, including characteristics such as study design, data collection, statistical analysis, and common sources of estimation bias. We also discuss alternative approaches and data types, such as those based on self-reporting and electronic vessel-monitoring systems. This guide is intended to be useful to managers and scientists in countries having or establishing programs aimed at managing marine mammal bycatch, especially those conducting first-time assessments of fisheries impacts on marine mammal populations.

Using semi-latin square design for screening and comparison of local and improved Zea maize varieties tolerant to climate change in centre of Benin (West Africa) - Assota Bonanventure; Gbemavo D. S. J. Charlemagne; Adjahossou Naesse; Laly Judicael; Gbaguidi A. Anicet; Moussa A. Alio; Dansi A. Alexandre (Journal of Crop Science and Biotechnology, 2021)

Livestock activities in agroforestry systems in Guadeloupe: systems of production and functions - G. Alexandre; A. Cheval; J. Perrette; M. Apatout; J. L. Diman; A. Larade; A. Vinglassalon (Agroforestry Systems, 2021)

Ruminant‐associated Listeria monocytogenes isolates belong preferentially to dairy‐associated hypervirulent clones: a longitudinal study in 19 farms - Carla Palacios‐Gorba; Alexandra Moura; Jesús Gomis; Alexandre Leclercq; Ángel Gómez‐Martín; Hélène Bracq‐Dieye; María L. Mocé; Nathalie Tessaud‐Rita; Estrella Jiménez‐Trigos; Guillaume Vales; Ángel García‐Muñoz; Pierre Thouvenot; et al. (Environmental Microbiology, 2021)
Summary Studies have shown that ruminants constitute reservoirs of Listeria monocytogenes , but little is known about the epidemiology and genetic diversity of this pathogen within farms. Here we conducted a large‐scale longitudinal study to monitor Listeria spp. in 19 dairy farms during three consecutive seasons ( N = 3251 samples). L . innocua was the most prevalent species, followed by L . monocytogenes . Listeria monocytogenes was detected in 52.6% of farms and more frequently in cattle (4.1%) and sheep (4.5%) than in goat farms (0.2%). Lineage I accounted for 69% of L . monocytogenes isolates. Among animal samples, the most prevalent sublineages (SL) and clonal complexes (CC) were SL1/CC1, SL219/CC4, SL26/CC26 and SL87/CC87, whereas SL666/CC666 was most prevalent in environmental samples. Sixty‐one different L . monocytogenes cgMLST types were found, 28% common to different animals and/or surfaces within the same farm and 21% previously reported elsewhere in the context of food and human surveillance. Listeria monocytogenes prevalence was not affected by farm hygiene but by season: higher prevalence was observed during winter in cattle, and during winter and spring in sheep farms. Cows in their second lactation had a higher probability of L . monocytogenes faecal shedding. This study highlights dairy farms as a reservoir for hypervirulent L . monocytogenes .

Best Practices for Assessing and Managing Bycatch of Marine Mammals - Paul R. Wade; Kristy J. Long; Tessa B. Francis; André E. Punt; Philip S. Hammond; Dennis Heinemann; Jeffrey E. Moore; Randall R. Reeves; Maritza Sepúlveda; Genoa Sullaway; Guðjón Már Sigurðsson; Margaret C. Siple; et al. (Frontiers in Marine Science, 2021)
Bycatch in marine fisheries is the leading source of human-caused mortality for marine mammals, has contributed to substantial declines of many marine mammal populations and species, and the extinction of at least one. Schemes for evaluating marine mammal bycatch largely rely on estimates of abundance and bycatch, which are needed for calculating biological reference points and for determining conservation status. However, obtaining these estimates is resource intensive and takes careful long-term planning. The need for assessments of marine mammal bycatch in fisheries is expected to increase worldwide due to the recently implemented Import Provisions of the United States Marine Mammal Protection Act. Managers and other stakeholders need reliable, standardized methods for collecting data to estimate abundance and bycatch rates. In some cases, managers will be starting with little or no data and no system in place to collect data. We outline a comprehensive framework for managing bycatch of marine mammals. We describe and provide guidance on (1) planning for an assessment of bycatch, (2) collecting appropriate data (e.g., abundance and bycatch estimates), (3) assessing bycatch and calculating reference points, and (4) using the results of the assessment to guide marine mammal bycatch reduction. We also provide a brief overview of available mitigation techniques to reduce marine mammal bycatch in various fisheries. This paper provides information for scientists and resource managers in the hope that it will lead to new or improved programs for assessing marine mammal bycatch, establishing best practices, and enhancing marine mammal conservation globally.

Multiple lionfish (Pterois spp.) new occurrences along the Brazilian coast confirm the invasion pathway into the Southwestern Atlantic - Osmar J. Luiz; Wagner C. R. dos Santos; Alexandre P. Marceniuk; Luiz A. Rocha; Sergio R. Floeter; Clara E. Buck; Alex G. C. M. de Klautau; Carlos E. L. Ferreira (Biological Invasions, 2021)

Estimating the Abundance of Marine Mammal Populations - Philip S. Hammond; Tessa B. Francis; Dennis Heinemann; Kristy J. Long; Jeffrey E. Moore; André E. Punt; Randall R. Reeves; Maritza Sepúlveda; Guðjón Már Sigurðsson; Margaret C. Siple; Gísli Víkingsson; Paul R. Wade; et al. (Frontiers in Marine Science, 2021)
Motivated by the need to estimate the abundance of marine mammal populations to inform conservation assessments, especially relating to fishery bycatch, this paper provides background on abundance estimation and reviews the various methods available for pinnipeds, cetaceans and sirenians. We first give an “entry-level” introduction to abundance estimation, including fundamental concepts and the importance of recognizing sources of bias and obtaining a measure of precision. Each of the primary methods available to estimate abundance of marine mammals is then described, including data collection and analysis, common challenges in implementation, and the assumptions made, violation of which can lead to bias. The main method for estimating pinniped abundance is extrapolation of counts of animals (pups or all-ages) on land or ice to the whole population. Cetacean and sirenian abundance is primarily estimated from transect surveys conducted from ships, small boats or aircraft. If individuals of a species can be recognized from natural markings, mark-recapture analysis of photo-identification data can be used to estimate the number of animals using the study area. Throughout, we cite example studies that illustrate the methods described. To estimate the abundance of a marine mammal population, key issues include: defining the population to be estimated, considering candidate methods based on strengths and weaknesses in relation to a range of logistical and practical issues, being aware of the resources required to collect and analyze the data, and understanding the assumptions made. We conclude with a discussion of some practical issues, given the various challenges that arise during implementation.

Assessment of ecosystem services provided by livestock agroecosystems in the tropics: a case study of tropical island environment of Guadeloupe - J.-L. Gourdine; A. Fourcot; C. Lefloch; M. Naves; G. Alexandre (Tropical Animal Health and Production, 2021)
The present study aims to assess (1) the ecosystem services (ES) provided by LFS and (2) the differential ES between local (Creole) and exotic breeds from pig, cattle and goat. The ES are defined as the benefits that humans derive from LFS. They were summarized in 12 ES indicators that cover services related to provisioning, ecological and socio-cultural aspects and territorial vitality. A total of 106 LFS units that covers the five agroecological zones of Guadeloupe were analysed. Functional typologies of LFS per species were created from surveys. The effect of breed on the ES indicators was tested. Results showed that the 40 pig LFS units were separated into 3 clusters that were differentiated in ES according to provisioning ES (cluster 1), cultural use and sale to the neighborhood (cluster 2) and pork self-consumption (cluster 3). The typology of the 57 farms with cattle distinguished 4 clusters with differences in ES provided in self-consumption (cluster1), ecological ES (cluster 2), socio-cultural ES for racing or draught oxen (cluster 3) and ES associated with territory vitality (cluster 4). The 66 goat LFS units were classified into 3 clusters different in ES concerning self-consumption (cluster 1), cultural aspects (cluster 2) and provisioning ES (cluster 3). Our study highlights that ES indicators are not breed dependent ( P > 0.10) but rather livestock farming system dependent. The ES rely more on the rearing management than on the breed type, and up to now, there are no specifications in Guadeloupe to differentiate management between breeds.

Influence of high temperatures on physical properties and microstructure of gneiss - K. O. B. Costa; G. C. Xavier; M. T. Marvila; J. Alexandre; A. R. G. Azevedo; S. N. Monteiro (Bulletin of Engineering Geology and the Environment, 2021)

The evolution of latitudinal ranges in reef‐associated fishes: Heritability, limits and inverse Rapoport's rule - Marcio R. Pie; Raquel Divieso; Fernanda S. Caron; Alexandre C. Siqueira; Diego R. Barneche; Osmar J. Luiz (Journal of Biogeography, 2021)
Aim Variation in the size and position of geographical ranges is a key variable that underlies most biogeographical patterns. However, relatively little is known in terms of general principles driving their evolution, particularly in the marine realm. In this study we explore several fundamental properties regarding the evolution of reef fish latitudinal ranges, namely the degree of similarity in range size between ancestor and descendant lineages (i.e. phylogenetic signal); the evolution of range limits; and the latitudinal distribution of range sizes, particularly with respect to Rapoport's rule. Location Global. Taxon Reef‐associated fishes. Methods We integrate data on the latitudinal distribution and evolutionary history of 5,071 reef fish species with phylogenetic comparative methods to assess the level of phylogenetic signal in latitudinal range size, low‐ and high‐latitude limits and range midpoints, and to estimate rates of evolution of those traits. Finally, we test whether latitudinal ranges become smaller near the equator, as predicted by Rapoport's rule, using phylogenetic generalized least squares. Results There were varying levels of phylogenetic signal in latitudinal range size, low‐ and high‐latitude limits and range midpoints. Despite these differences, latitudinal midpoints were consistently shown to have the highest phylogenetic signal among all measured geographical features. Interestingly, the position of high‐latitude limits in general evolved at substantially faster rates than their low‐latitude counterparts. Finally, we confirm for the first time the existence of an inverse Rapoport's rule in reef‐associated fishes using phylogenetic comparative methods. Indeed, mean latitudinal range size of tropical species is nearly twice the size of their temperate counterparts (2,067 ± 1,431 km vs. 1,168 ± 725 km respectively). Main conclusions We uncovered several congruent patterns in phylogenetic signal and rates of evolution of latitudinal ranges, despite vastly disparate biogeographical distributions and ecological differences between the studied fish lineages. Such broad congruence across different taxa and oceans, as well as with previous data from terrestrial environments, suggests that the observed patterns might represent general principles governing geographical range evolution.

The Brazilian Cerrado is becoming hotter and drier - Gabriel S. Hofmann; Manoel F. Cardoso; Ruy J. V. Alves; Eliseu J. Weber; Alexandre A. Barbosa; Peter M. de Toledo; Francisco B. Pontual; Leandro de O. Salles; Heinrich Hasenack; José L. P. Cordeiro; Francisco E. Aquino; Luiz F. B. de Oliveira (Global Change Biology, 2021)
The Brazilian Cerrado is a global biodiversity hotspot with notoriously high rates of native vegetation suppression and wildfires over the past three decades. As a result, climate change can already be detected at both local and regional scales. In this study, we used three different approaches based on independent datasets to investigate possible changes in the daytime and nighttime temperature and air humidity between the peak of the dry season and the beginning of the rainy season in the Brazilian Cerrado. Additionally, we evaluated the tendency of dew point depression, considering it as a proxy to assess impacts on biodiversity. Monthly increases of 2.2−4.0℃ in the maximum temperatures and 2.4−2.8℃ in the minimum temperatures between 1961 and 2019 were recorded, supported by all analyzed datasets which included direct observations, remote sensing, and modeling data. The warming raised the vapor pressure deficit, and although we recorded an upward trend in absolute humidity, relative humidity has reduced by ~15%. If these tendencies are maintained, gradual air warming will make nightly cooling insufficient to reach the dew point in the early hours of the night. Therefore, it will progressively reduce both the amount and duration of nocturnal dewfall, which is the main source of water for numerous plants and animal species of the Brazilian Cerrado during the dry season. Through several examples, we hypothesize that these climate changes can have a high impact on biodiversity and potentially cause ecosystems to collapse. We emphasize that the effects of temperature and humidity on Cerrado ecosystems cannot be neglected and should be further explored from a land use perspective.

Regulatory approaches for genome edited agricultural plants in select countries and jurisdictions around the world - Jon Entine; Maria Sueli S. Felipe; Jan-Hendrik Groenewald; Drew L. Kershen; Martin Lema; Alan McHughen; Alexandre Lima Nepomuceno; Ryo Ohsawa; Reynante L. Ordonio; Wayne A. Parrott; Hector Quemada; Carl Ramage; et al. (Transgenic Research, 2021)
Genome editing in agriculture and food is leading to new, improved crops and other products. Depending on the regulatory approach taken in each country or region, commercialization of these crops and products may or may not require approval from the respective regulatory authorities. This paper describes the regulatory landscape governing genome edited agriculture and food products in a selection of countries and regions.

Occurrence but not intensity of mortality rises towards the climatic trailing edge of tree species ranges in European forests - Alexandre Changenet; Paloma Ruiz‐Benito; Sophia Ratcliffe; Thibaut Fréjaville; Juliette Archambeau; Annabel J. Porte; Miguel A. Zavala; Jonas Dahlgren; Aleksi Lehtonen; Marta Benito Garzón (Global Ecology and Biogeography, 2021)
Aim Tree mortality is increasing world‐wide, leading to changes in forest composition and altering global biodiversity. Nonetheless, owing to the multifaceted stochastic nature of tree mortality, large‐scale spatial patterns of mortality across species ranges and their underlying drivers remain difficult to understand. Our main goal was to describe the geographical patterns and drivers of the occurrence of mortality (presence of a mortality event) and the intensity of tree mortality (amount of mortality related to that mortality event) in Europe. We hypothesized that the occurrence of mortality represents background mortality and is higher in the margin than in core populations, whereas the intensity of mortality could have a more even distribution according to the spatial and temporal stochasticity of die‐off events. Location Europe (Spain, France, Germany, Belgium, Sweden and Finland). Major taxa studied More than 1.5 million trees belonging to 20 major forest tree species. Methods We developed binomial and truncated negative binomial models to tease apart the occurrence and intensity of tree mortality in National Forest Inventory plots at the range‐wide scale. The occurrence of mortality indicated that at least one tree had died in the plot, whereas the intensity of mortality referred to the number of dead trees per plot. Results The highest occurrence of mortality was found in peripheral regions and the climatic trailing edge linked with drought, whereas the intensity of mortality was driven by competition, drought and high temperatures and was scattered uniformly across species ranges. Main conclusions We show that tree background mortality, but not die‐off, is generally higher in the trailing‐edge populations. It remains to be explored whether other demographic traits, such as growth, reproduction and regeneration, also decrease at the trailing edge of European tree populations.

Evaluation of camera settings for photogrammetric reconstruction of humanoid phantoms for EBRT bolus and HDR surface brachytherapy applications - Corey A. Bridger; Michael J. J. Douglass; Paul D. Reich; Alexandre M. Caraça Santos (Physical and Engineering Sciences in Medicine, 2021)

Juvenile corals underpin coral reef carbonate production after disturbance - Jérémy Carlot; Mohsen Kayal; Hunter S. Lenihan; Simon J. Brandl; Jordan M. Casey; Mehdi Adjeroud; Ulisse Cardini; Alexandre Merciere; Benoit Espiau; Diego R. Barneche; Alessio Rovere; Laetitia Hédouin; et al. (Global Change Biology, 2021)
Sea‐level rise is predicted to cause major damage to tropical coastlines. While coral reefs can act as natural barriers for ocean waves, their protection hinges on the ability of scleractinian corals to produce enough calcium carbonate (CaCO 3 ) to keep up with rising sea levels. As a consequence of intensifying disturbances, coral communities are changing rapidly, potentially reducing community‐level CaCO 3 production. By combining colony‐level physiology and long‐term monitoring data, we show that reefs recovering from major disturbances can produce 40% more CaCO 3 than currently estimated due to the disproportionate contribution of juvenile corals. However, the buffering effect of highly productive juvenile corals is compromised by recruitment failures, which have been more frequently observed after large‐scale, repeated bleaching events. While the size structure of corals can bolster a critical ecological function on reefs, climate change impacts on recruitment may undermine this buffering effect, thus further compromising the persistence of reefs and their provision of important ecosystem services.

Systematics and biogeography of the Boana albopunctata species group (Anura, Hylidae), with the description of two new species from Amazonia - Antoine Fouquet; Pedro Marinho; Alexandre Réjaud; Thiago R. Carvalho; Marcel A. Caminer; Martin Jansen; Raíssa N. Rainha; Miguel T. Rodrigues; Fernanda P. Werneck; Albertina P. Lima; Tomas Hrbek; Ariovaldo A. Giaretta; et al. (Systematics and Biodiversity, 2021)

Musical Chairs on Temperate Reefs: Species Turnover and Replacement Within Functional Groups Explain Regional Diversity Variation in Assemblages Associated With Honeycomb Worms - Alexandre Muller; Camille Poitrimol; Flávia L. D. Nunes; Aurélien Boyé; Amelia Curd; Nicolas Desroy; Louise B. Firth; Laura Bush; Andrew J. Davies; Fernando P. Lima; Martin P. Marzloff; Claudia Meneghesso; et al. (Frontiers in Marine Science, 2021)
Reef-building species are recognized as having an important ecological role and as generally enhancing the diversity of benthic organisms in marine habitats. However, although these ecosystem engineers have a facilitating role for some species, they may exclude or compete with others. The honeycomb worm Sabellaria alveolata ( Linnaeus, 1767 ) is an important foundation species, commonly found from northwest Ireland to northern Mauritania, whose reef structures increase the physical complexity of the marine benthos, supporting high levels of biodiversity. Local patterns and regional differences in taxonomic and functional diversity were examined in honeycomb worm reefs from 10 sites along the northeastern Atlantic to explore variation in diversity across biogeographic regions and the potential effects of environmental drivers. While taxonomic composition varied across the study sites, levels of diversity remained relatively constant along the European coast. Assemblages showed high levels of species turnover compared to differences in richness, which varied primarily in response to sea surface temperatures and sediment content, the latter suggesting that local characteristics of the reef had a greater effect on community composition than the density of the engineering species. In contrast, the functional composition of assemblages was similar regardless of taxonomic composition or biogeography, with five functional groups being observed in all sites and only small differences in abundance in these groups being detected. Functional groups represented primarily filter-feeders and deposit-feeders, with the notable absence of herbivores, indicating that the reefs may act as biological filters for some species from the local pool of organisms. Redundancy was observed within functional groups that may indicate that honeycomb worm reefs can offer similar niche properties to its associated assemblages across varying environmental conditions. These results highlight the advantages of comparing taxonomic and functional metrics, which allow identification of a number of ecological processes that structure marine communities.

Metabolic status is not associated with job stress in individuals with obesity: the ELSA-Brasil baseline - Lia Imbiriba; Beatriz H. Tess; Rosane H. Griep; Maria J. M. Fonseca; Alexandre C. Pereira; Maria F. S. Diniz; Paulo A. Lotufo; Isabela M. Bensenor; Itamar S. Santos (International Archives of Occupational and Environmental Health, 2021)

Glenn R. VanBlaricom † 1949–2020 - Alexandre N. Zerbini; Anthony J. Orr; Amanda L. Bradford; Michael Kenner; Robert Suydam; Carlos Alvarez‐Flores; Leah R. Gerber; Kristin Laidre; Donna Hauser; Laura Hoberecht (Marine Mammal Science, 2021)

Ten golden rules for reforestation to optimize carbon sequestration, biodiversity recovery and livelihood benefits - Alice Di Sacco; Kate A. Hardwick; David Blakesley; Pedro H. S. Brancalion; Elinor Breman; Loic Cecilio Rebola; Susan Chomba; Kingsley Dixon; Stephen Elliott; Godfrey Ruyonga; Kirsty Shaw; Paul Smith; et al. (Global Change Biology, 2021)
Urgent solutions to global climate change are needed. Ambitious tree‐planting initiatives, many already underway, aim to sequester enormous quantities of carbon to partly compensate for anthropogenic CO 2 emissions, which are a major cause of rising global temperatures. However, tree planting that is poorly planned and executed could actually increase CO 2 emissions and have long‐term, deleterious impacts on biodiversity, landscapes and livelihoods. Here, we highlight the main environmental risks of large‐scale tree planting and propose 10 golden rules, based on some of the most recent ecological research, to implement forest ecosystem restoration that maximizes rates of both carbon sequestration and biodiversity recovery while improving livelihoods. These are as follows: (1) Protect existing forest first; (2) Work together (involving all stakeholders); (3) Aim to maximize biodiversity recovery to meet multiple goals; (4) Select appropriate areas for restoration; (5) Use natural regeneration wherever possible; (6) Select species to maximize biodiversity; (7) Use resilient plant material (with appropriate genetic variability and provenance); (8) Plan ahead for infrastructure, capacity and seed supply; (9) Learn by doing (using an adaptive management approach); and (10) Make it pay (ensuring the economic sustainability of the project). We focus on the design of long‐term strategies to tackle the climate and biodiversity crises and support livelihood needs. We emphasize the role of local communities as sources of indigenous knowledge, and the benefits they could derive from successful reforestation that restores ecosystem functioning and delivers a diverse range of forest products and services. While there is no simple and universal recipe for forest restoration, it is crucial to build upon the currently growing public and private interest in this topic, to ensure interventions provide effective, long‐term carbon sinks and maximize benefits for biodiversity and people.

An update of the Worldwide Integrated Assessment (WIA) on systemic insecticides. Part 2: impacts on organisms and ecosystems - Lennard Pisa; Dave Goulson; En-Cheng Yang; David Gibbons; Francisco Sánchez-Bayo; Edward Mitchell; Alexandre Aebi; Jeroen van der Sluijs; Chris J. K. MacQuarrie; Chiara Giorio; Elizabeth Yim Long; Melanie McField; et al. (Environmental Science and Pollution Research, 2021)
New information on the lethal and sublethal effects of neonicotinoids and fipronil on organisms is presented in this review, complementing the previous Worldwide Integrated Assessment (WIA) in 2015. The high toxicity of these systemic insecticides to invertebrates has been confirmed and expanded to include more species and compounds. Most of the recent research has focused on bees and the sublethal and ecological impacts these insecticides have on pollinators. Toxic effects on other invertebrate taxa also covered predatory and parasitoid natural enemies and aquatic arthropods. Little new information has been gathered on soil organisms. The impact on marine and coastal ecosystems is still largely uncharted. The chronic lethality of neonicotinoids to insects and crustaceans, and the strengthened evidence that these chemicals also impair the immune system and reproduction, highlights the dangers of this particular insecticidal class (neonicotinoids and fipronil), with the potential to greatly decrease populations of arthropods in both terrestrial and aquatic environments. Sublethal effects on fish, reptiles, frogs, birds, and mammals are also reported, showing a better understanding of the mechanisms of toxicity of these insecticides in vertebrates and their deleterious impacts on growth, reproduction, and neurobehaviour of most of the species tested. This review concludes with a summary of impacts on the ecosystem services and functioning, particularly on pollination, soil biota, and aquatic invertebrate communities, thus reinforcing the previous WIA conclusions (van der Sluijs et al. 2015).

Quercetin treatment increases H2O2 removal by restoration of endogenous antioxidant activity and blocks isoproterenol-induced cardiac hypertrophy - Joana Varlla de Lacerda Alexandre; Yuana Ivia Ponte Viana; Cícera Edna Barbosa David; Pedro Lourenzo Oliveira Cunha; Amanda Cabral Albuquerque; Anna Lídia Nunes Varela; Alicia J. Kowaltowski; Heberty Tarso Facundo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Strontium isotope stratigraphy through the Flatreef PGE-Ni-Cu mineralization at Turfspruit, northern limb of the Bushveld Igneous Complex: evidence of correlation with the Merensky Unit of the eastern and western limbs - Cédric C. Mayer; Pedro J. Jugo; Matthew I. Leybourne; Danie F. Grobler; Alexandre Voinot (Mineralium Deposita, 2021)
The origin of PGE-Ni-Cu mineralization in the Platreef, northern limb of the Bushveld Igneous Complex (BIC), and the possible correlation with the Merensky Reef in the eastern and western limbs has been long debated. The Platreef and Merensky Reef share the same stratigraphic position in the uppermost part of the Upper Critical Zone (UCZ), near the transition to the overlaying Main Zone (MZ). However, discrepancies in interpretations have been difficult to resolve due to the effects of intense magma-country rock interaction throughout most of the northern limb succession. To address this problem, we generated a detailed stratigraphic profile of the initial strontium isotopic ratio [Sr i = ( 87 Sr/ 86 Sr) i ] in plagioclase across a Flatreef interval lacking macroscopic evidence of country rock assimilation. The in situ Sr isotopic ratios in plagioclase were determined using LA-MC-ICP-MS analysis on 37 samples from a drill core (UMT094) at the Turfspruit project. Strontium isotope stratigraphy is useful because of a well-documented shift in Sr i near the base of the Merensky Unit in the eastern and western limbs. The results show the existence of a significant shift (from Sr i = 0.7060 to Sr i = 0.7090) that matches the isotopic shift documented through the Merensky Unit in the eastern and western limbs. Thus, this new Sr isotope data indicates that the main mineralized interval of the Flatreef can be stratigraphically correlated to the Merensky Reef in the remainder of the BIC. In addition, we interpret these results as compelling evidence to suggest that the main mineralization processes in the Flatreef were likely similar to those operating in the eastern and western limbs and that interaction with local country rocks was not a necessary condition.

Cypermethrin- and fipronil-based insecticides cause biochemical changes in Physalaemus gracilis tadpoles - Camila F. Rutkoski; Natani Macagnan; Alexandre Folador; Vrandrieli J. Skovronski; Aline M. B. do Amaral; Jossiele Wesz Leitemperger; Maiara Dorneles Costa; Paulo A. Hartmann; Caroline Müller; Vania L. Loro; Marilia T. Hartmann (Environmental Science and Pollution Research, 2021)

Asymmetric interlateral transfer of motor learning in unipedal dynamic balance - Alexandre J. Marcori; Luis A. Teixeira; Kelyn R. Mathias; Juliana B. Dascal; Victor H. A. Okazaki (Experimental Brain Research, 2020)

COSORE: A community database for continuous soil respiration and other soil‐atmosphere greenhouse gas flux data - Ben Bond‐Lamberty; Danielle S. Christianson; Avni Malhotra; Stephanie C. Pennington; Debjani Sihi; Amir AghaKouchak; Hassan Anjileli; M. Altaf Arain; Juan J. Armesto; Samaneh Ashraf; Mioko Ataka; Dennis Baldocchi; et al. (Global Change Biology, 2020)
Globally, soils store two to three times as much carbon as currently resides in the atmosphere, and it is critical to understand how soil greenhouse gas (GHG) emissions and uptake will respond to ongoing climate change. In particular, the soil‐to‐atmosphere CO 2 flux, commonly though imprecisely termed soil respiration ( R S ), is one of the largest carbon fluxes in the Earth system. An increasing number of high‐frequency R S measurements (typically, from an automated system with hourly sampling) have been made over the last two decades; an increasing number of methane measurements are being made with such systems as well. Such high frequency data are an invaluable resource for understanding GHG fluxes, but lack a central database or repository. Here we describe the lightweight, open‐source COSORE (COntinuous SOil REspiration) database and software, that focuses on automated, continuous and long‐term GHG flux datasets, and is intended to serve as a community resource for earth sciences, climate change syntheses and model evaluation. Contributed datasets are mapped to a single, consistent standard, with metadata on contributors, geographic location, measurement conditions and ancillary data. The design emphasizes the importance of reproducibility, scientific transparency and open access to data. While being oriented towards continuously measured R S , the database design accommodates other soil‐atmosphere measurements (e.g. ecosystem respiration, chamber‐measured net ecosystem exchange, methane fluxes) as well as experimental treatments (heterotrophic only, etc.). We give brief examples of the types of analyses possible using this new community resource and describe its accompanying R software package.

Ayahuasca blocks the reinstatement of methylphenidate-induced conditioned place preference in mice: behavioral and brain Fos expression evaluations - Henrique S. Reis; Isa R. S. Rodrigues; Alexia Anjos-Santos; Matheus Libarino-Santos; Yasmim A. Serra; Elisângela G. Cata-Preta; Daniella Oliveira-Campos; Natali D. Kisaki; Thaísa Barros-Santos; Thais S. Yokoyama; Fabio C. Cruz; Alexandre J. Oliveira-Lima; et al. (Psychopharmacology, 2020)

Historical biogeography identifies a possible role of Miocene wetlands in the diversification of the Amazonian rocket frogs (Aromobatidae: Allobates ) - Alexandre Réjaud; Miguel T. Rodrigues; Andrew J. Crawford; Santiago Castroviejo‐Fisher; Andrés F. Jaramillo; Juan C. Chaparro; Frank Glaw; Giussepe Gagliardi‐Urrutia; Jiří Moravec; Ignacio J. De la Riva; Pedro Perez; Albertina P. Lima; et al. (Journal of Biogeography, 2020)
Aim We investigate the spatiotemporal context of the diversification of Allobates , a widespread genus of Amazonian frogs with high species diversity particularly in western Amazonia. We tested if that diversity originated in situ or through repeated dispersals from other Amazonian areas and if this diversification took place during or after the Pebas system, a vast lacustrine system occupying most western Amazonia between 23 and 10 million years ago (Mya). Location Amazonia. Taxon Allobates (Anura: Aromobatidae). Methods We gathered a spatially and taxonomically extensive sampling of mitochondrial DNA sequences from 932 Allobates specimens to delimit Operational Taxonomic Units (OTUs). Complete mitogenomes of these OTUs were assembled to reconstruct a time‐calibrated phylogeny used to infer the historical and spatial origin of the Amazonian Allobates lineages. Results Phylogenetic analyses and ancestral area reconstruction suggested that most of the western Amazonian lineages resulted from in situ diversification and that these events occurred between the inferred origin of the genus (25 Mya) and 10 Mya, with a possible peak between 14 and 10 Mya. Dispersal among areas mostly occurred from western Amazonia towards the Brazilian and the Guiana Shields. Closely related Allobates OTUs display an allopatric pattern of distribution, matching interfluves delimited by modern Amazonian rivers. Main Conclusions In western Amazonia, diversification of Allobates appears to have been simultaneous with the last stages of the Pebas system (14–10 Mya). Subsequently (within the last 10 Mya), modern Amazonian river courses shaped the distribution pattern of Allobates species and possibly promoted allopatric speciation.

Mapping the effectiveness of nature‐based solutions for climate change adaptation - Alexandre Chausson; Beth Turner; Dan Seddon; Nicole Chabaneix; Cécile A. J. Girardin; Valerie Kapos; Isabel Key; Dilys Roe; Alison Smith; Stephen Woroniecki; Nathalie Seddon (Global Change Biology, 2020)
Nature‐based solutions (NbS) to climate change currently have considerable political traction. However, national intentions to deploy NbS have yet to be fully translated into evidence‐based targets and action on the ground. To enable NbS policy and practice to be better informed by science, we produced the first global systematic map of evidence on the effectiveness of nature‐based interventions for addressing the impacts of climate change and hydrometeorological hazards on people. Most of the interventions in natural or semi‐natural ecosystems were reported to have ameliorated adverse climate impacts. Conversely, interventions involving created ecosystems (e.g., afforestation) were associated with trade‐offs; such studies primarily reported reduced soil erosion or increased vegetation cover but lower water availability, although this evidence was geographically restricted. Overall, studies reported more synergies than trade‐offs between reduced climate impacts and broader ecological, social, and climate change mitigation outcomes. In addition, nature‐based interventions were most often shown to be as effective or more so than alternative interventions for addressing climate impacts. However, there were substantial gaps in the evidence base. Notably, there were few studies of the cost‐effectiveness of interventions compared to alternatives and few integrated assessments considering broader social and ecological outcomes. There was also a bias in evidence toward the Global North, despite communities in the Global South being generally more vulnerable to climate impacts. To build resilience to climate change worldwide, it is imperative that we protect and harness the benefits that nature can provide, which can only be done effectively if informed by a strengthened evidence base.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Roterbärite, PdCuBiSe3, a new mineral species from the Roter Bär mine, Harz Mountains, Germany - Anna Vymazalová; Alexandre R. Cabral; František Laufek; Wilfried Ließmann; Chris J. Stanley; Bernd Lehmann (Mineralogy and Petrology, 2020)

Differential diagnosis of asthma and restrictive respiratory diseases by combining forced oscillation measurements, machine learning and neuro-fuzzy classifiers - Jorge L. M. Amaral; Alexandre G. Sancho; Alvaro C. D. Faria; Agnaldo J. Lopes; Pedro L. Melo (Medical & Biological Engineering & Computing, 2020)

Implications of various effort-sharing approaches for national carbon budgets and emission pathways - Nicole J. van den Berg; Heleen L. van Soest; Andries F. Hof; Michel G. J. den Elzen; Detlef P. van Vuuren; Wenying Chen; Laurent Drouet; Johannes Emmerling; Shinichiro Fujimori; Niklas Höhne; Alexandre C. Kõberle; David McCollum; et al. (Climatic Change, 2020)
The bottom-up approach of the Nationally Determined Contributions (NDCs) in the Paris Agreement has led countries to self-determine their greenhouse gas (GHG) emission reduction targets. The planned ‘ratcheting-up’ process, which aims to ensure that the NDCs comply with the overall goal of limiting global average temperature increase to well below 2 °C or even 1.5 °C, will most likely include some evaluation of ‘fairness’ of these reduction targets. In the literature, fairness has been discussed around equity principles, for which many different effort-sharing approaches have been proposed. In this research, we analysed how country-level emission targets and carbon budgets can be derived based on such criteria. We apply novel methods directly based on the global carbon budget, and, for comparison, more commonly used methods using GHG mitigation pathways. For both, we studied the following approaches: equal cumulative per capita emissions, contraction and convergence, grandfathering, greenhouse development rights and ability to pay. As the results critically depend on parameter settings, we used the wide authorship from a range of countries included in this paper to determine default settings and sensitivity analyses. Results show that effort-sharing approaches that (i) calculate required reduction targets in carbon budgets (relative to baseline budgets) and/or (ii) take into account historical emissions when determining carbon budgets can lead to (large) negative remaining carbon budgets for developed countries. This is the case for the equal cumulative per capita approach and especially the greenhouse development rights approach. Furthermore, for developed countries, all effort-sharing approaches except grandfathering lead to more stringent budgets than cost-optimal budgets, indicating that cost-optimal approaches do not lead to outcomes that can be regarded as fair according to most effort-sharing approaches.

Characterization of planktonic and biofilm cells from two filamentous cyanobacteria using a shotgun proteomic approach - Maria João Leal Romeu; Dany Domínguez-Pérez; Daniela Almeida; João Morais; Alexandre Campos; Vítor Vasconcelos; Filipe J. M. Mergulhão (Biofouling, 2020)

Freshwater Inflow Variability Affects the Relative Importance of Allochthonous Sources for Estuarine Fishes - Bianca Possamai; David J. Hoeinghaus; Clarisse Odebrecht; Paulo C. Abreu; Leonardo E. Moraes; Alexandre C. A. Santos; Alexandre M. Garcia (Estuaries and Coasts, 2020)

Conservation assessment of cassava wild relatives in central Brazil - Marcelo F. Simon; Talita S. Reis; J. Moises Mendoza F.; Thalyssa K. M. Arquelão; João B. A. Bringel; Sérgio E. Noronha; Márcio L. L. Martins; Carlos A. S. Ledo; Marcos J. Silva; Alexandre B. Sampaio; Eraldo T. Matricardi; Aldicir Scariot (Biodiversity and Conservation, 2020)

Landslide response to the 27 October 2012 earthquake (MW 7.8), southern Haida Gwaii, British Columbia, Canada - Sophia Barth; Marten Geertsema; Alexandre R. Bevington; Alison L. Bird; John J. Clague; Tom Millard; Peter T. Bobrowsky; Andreas Hasler; Hongjiang Liu (Landslides, 2020)
In this paper, we examine the influence of the 27 October 2012, M w 7.8 earthquake on landslide occurrence in the southern half of Haida Gwaii (formerly Queen Charlotte Islands), British Columbia, Canada. Our 1350 km 2 study area is undisturbed, primarily forested terrain that has not experienced road building or timber harvesting. Our inventory of landslide polygons is based on optical airborne and spaceborne images acquired between 2007 and 2018, from which we extracted and mapped 446 individual landslides (an average of 33 landslides per 100 km 2 ). The landslide rate in years without major earthquakes averages 19.4 per year, or 1.4/100 km 2 /year, and the annual average area covered by non-seismically triggered landslides is 35 ha/year. The number of landslides identified in imagery closely following the 2012 earthquake, and probably triggered by it, is 244 or an average of about 18 landslides per 100 km 2 . These landslides cover a total area of 461 ha. In the following years—2013–2016 and 2016–2018—the number of landslides fell, respectively, to 26 and 13.5 landslides per year. In non-earthquake years, most landslides happen on south-facing slopes, facing the prevailing winds. In contrast, during or immediately after the earthquake, up to 32% of the landslides occurred on north and northwest-facing slopes. Although we could not find imagery from the day after the earthquake, overview reconnaissance flights 10 and 16 days later showed that most of the landslides were recent, suggesting they were co-seismic.

Cell membrane fatty acid and pigment composition of the psychrotolerant cyanobacterium Nodularia spumigena CHS1 isolated from Hopar glacier, Pakistan - Noor Hassan; Alexandre M. Anesio; Muhammad Rafiq; Jens Holtvoeth; Ian Bull; Christopher J. Williamson; Fariha Hasan (Extremophiles, 2020)

Microbial genomes retrieved from High Arctic lake sediments encode for adaptation to cold and oligotrophic environments - Matti O. Ruuskanen; Graham Colby; Kyra A. St.Pierre; Vincent L. St.Louis; Stéphane Aris‐Brosou; Alexandre J. Poulain (Limnology and Oceanography, 2020)
The Arctic is currently warming at an unprecedented rate, which may affect environmental constraints on the freshwater microbial communities found there. Yet, our knowledge of the community structure and functional potential of High Arctic freshwater microbes remains poor, even though they play key roles in nutrient cycling and other ecosystem services. Here, using high‐throughput metagenomic sequencing and genome assembly, we show that sediment microbial communities in the High Arctic's largest lake by volume, Lake Hazen, are phylogenetically diverse, ranging from Proteobacteria, Verrucomicrobia, Planctomycetes, to members of the newly discovered Candidate Phyla Radiation groups. These genomes displayed a high prevalence of pathways involved in lipid chemistry, and a low prevalence of nutrient uptake pathways, which might represent adaptations to the specific, cold (∼ 3.5°C) and extremely oligotrophic conditions in Lake Hazen. Despite these potential adaptations, it is unclear how ongoing environmental changes will affect microbial communities, the makeup of their genomic idiosyncrasies, as well as the possible implications at higher trophic levels.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Frag SAD : A database of diversity and species abundance distributions from habitat fragments - Jonathan M. Chase; Mario Liebergesell; Alban Sagouis; Felix May; Shane A. Blowes; Åke Berg; Enrico Bernard; Berry J. Brosi; Marc W. Cadotte; Luis Cayuela; Adriano G. Chiarello; Jean‐Francois Cosson; et al. (Ecology, 2019)
Habitat destruction is the single greatest anthropogenic threat to biodiversity. Decades of research on this issue have led to the accumulation of hundreds of data sets comparing species assemblages in larger, intact, habitats to smaller, more fragmented, habitats. Despite this, little synthesis or consensus has been achieved, primarily because of non‐standardized sampling methodology and analyses of notoriously scale‐dependent response variables (i.e., species richness). To be able to compare and contrast the results of habitat fragmentation on species’ assemblages, it is necessary to have the underlying data on species abundances and sampling intensity, so that standardization can be achieved. To accomplish this, we systematically searched the literature for studies where abundances of species in assemblages (of any taxa) were sampled from many habitat patches that varied in size. From these, we extracted data from several studies, and contacted authors of studies where appropriate data were collected but not published, giving us 117 studies that compared species assemblages among habitat fragments that varied in area. Less than one‐half (41) of studies came from tropical forests of Central and South America, but there were many studies from temperate forests and grasslands from all continents except Antarctica. Fifty‐four of the studies were on invertebrates (mostly insects), but there were several studies on plants (15), birds (16), mammals (19), and reptiles and amphibians (13). We also collected qualitative information on the length of time since fragmentation. With data on total and relative abundances (and identities) of species, sampling effort, and affiliated meta‐data about the study sites, these data can be used to more definitively test hypotheses about the role of habitat fragmentation in altering patterns of biodiversity. There are no copyright restrictions. Please cite this data paper and the associated Dryad data set if the data are used in publications.

Evolution of the 2014 Vulcan Creek landslide-dammed lake, Yukon, Canada, using field and remote survey techniques - Marc-André Brideau; Dan H. Shugar; Alexandre R. Bevington; Michael J. Willis; Carmen Wong (Landslides, 2019)

Stable isotopes reveal the common winter moult of central rectrices in a long-distance migrant songbird - Frédéric Jiguet; Kevin J. Kardynal; Markus Piha; Tuomas Seimola; José Luis Copete; Michel Alexandre Czajkowski; Valery Dombrovski; Ron Efrat; Simonas Minkevicius; Marko Raković; Michał Skierczyǹski; Keith A. Hobson (Journal of Ornithology, 2019)

Orthocuproplatinum, Pt3Cu, a new mineral from the Lubero region, North Kivu, Democratic Republic of the Congo - Alexandre R. Cabral; Roman Skála; Anna Vymazalová; Jaroslav Maixner; Chris J. Stanley; Bernd Lehmann; Jacques Jedwab (Mineralogy and Petrology, 2019)

Potential of industrial by-products and wastes from the Iberian Peninsula as carbon sources for sulphate-reducing bacteria - J. D. Carlier; L. M. Alexandre; A. T. Luís; M. C. Costa (International Journal of Environmental Science and Technology, 2019)

Could coastal plants in western Amazonia be relicts of past marine incursions? - Rodrigo Bernal; Christine D. Bacon; Henrik Balslev; Carina Hoorn; Sarah J. Bourlat; Hanna Tuomisto; Sonia Salamanca; Milan Teunissen van Manen; Ingrid Romero; Pierre Sepulchre; Alexandre Antonelli (Journal of Biogeography, 2019)
The rainforests of Amazonia comprise some of the most biologically diverse ecosystems on Earth. Despite this high biodiversity, little is known about how landscape changes that took place in deep history have affected the assembly of its species, and whether the impact of such changes on biodiversity can still be observed. Here, we present a hypothesis to explain our observation that plants typical of Neotropical coastal habitats also occur in western Amazonia, in some cases thousands of kilometres away from the coast. Evidence on their current distribution, dispersal biology and divergence times estimated from molecular phylogenies suggest that these plants may be the legacy of the large marine‐influenced embayment that dominated the area for millions of years in the Neogene. We hypothesize that coastal plants dispersed along the shores of this embayment and persisted as inland relicts after the marine incursion(s) retreated, probably with the aid of changes in soil conditions caused by the deposition of marine sediments. This dispersal corridor may also have facilitated the colonization of coastal environments by Amazonian lineages. These scenarios could imply an unexpected coastal source that has contributed to Amazonia's high floristic diversity and led to disjunct distributions across the Neotropics. We highlight the need for future studies and additional evidence to validate and shed further light on this potentially important pattern.

Four priorities for new links between conservation science and accounting research - Clément Feger; Laurent Mermet; Bhaskar Vira; Prue F.E. Addison; Richard Barker; Frank Birkin; John Burns; Stuart Cooper; Denis Couvet; Thomas Cuckston; Gretchen C. Daily; Colin Dey; et al. (Conservation Biology, 2019)
Article impact statement : New collaborations with accounting research can improve conservation impact of ecosystem‐based information systems.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Climate change will decrease the range of a keystone fish species in La Plata River Basin, South America - Renata Ruaro; Eliezer O. Conceição; Jislaine C. Silva; Emanuel G. Cafofo; Mirtha A. Angulo-Valencia; Tatiane Mantovano; Alfonso Pineda; Aline C. M. de Paula; Bárbara F. Zanco; Eloiza M. Capparros; Geovani A. Moresco; Isadora J. de Oliveira; et al. (Hydrobiologia, 2019)

Dynamics of genomic change during evolutionary rescue in the seed beetle Callosobruchus maculatus - Alexandre Rêgo; Frank J. Messina; Zachariah Gompert (Molecular Ecology, 2019)
Rapid adaptation can prevent extinction when populations are exposed to extremely marginal or stressful environments. Factors that affect the likelihood of evolutionary rescue from extinction have been identified, but much less is known about the evolutionary dynamics (e.g., rates and patterns of allele frequency change) and genomic basis of successful rescue, particularly in multicellular organisms. We conducted an evolve‐and‐resequence experiment to investigate the dynamics of evolutionary rescue at the genetic level in the cowpea seed beetle, Callosobruchus maculatus , when it is experimentally shifted to a stressful host plant, lentil. Low survival (~1%) at the onset of the experiment caused population decline. But adaptive evolution quickly rescued the population, with survival rates climbing to 69% by the F5 generation and 90% by the F10 generation. Population genomic data showed that rescue likely was caused by rapid evolutionary change at multiple loci, with many alleles fixing or nearly fixing within five generations of selection on lentil. Selection on these loci was only moderately consistent in time, but parallel evolutionary changes were evident in sublines formed after the lentil line had passed through a bottleneck. By comparing estimates of selection and genomic change on lentil across five independent C. maculatus lines (the new lentil‐adapted line, three long‐established lines and one case of failed evolutionary rescue), we found that adaptation on lentil occurred via somewhat idiosyncratic evolutionary changes. Overall, our results suggest that evolutionary rescue in this system can be caused by very strong selection on multiple loci driving rapid and pronounced genomic change.

Examining forest resilience to changing fire frequency in a fire‐prone region of boreal forest - Sarah J. Hart; Jonathan Henkelman; Philip D. McLoughlin; Scott E. Nielsen; Alexandre Truchon‐Savard; Jill F. Johnstone (Global Change Biology, 2019)
Future changes in climate are widely anticipated to increase fire frequency, particularly in boreal forests where extreme warming is expected to occur. Feedbacks between vegetation and fire may modify the direct effects of warming on fire activity and shape ecological responses to changing fire frequency. We investigate these interactions using extensive field data from the Boreal Shield of Saskatchewan, Canada, a region where >40% of the forest has burned in the past 30 years. We use geospatial and field data to assess the resistance and resilience of eight common vegetation states to frequent fire by quantifying the occurrence of short‐interval fires and their effect on recovery to a similar vegetation state. These empirical relationships are combined with data from published literature to parameterize a spatially explicit, state‐and‐transition simulation model of fire and forest succession. We use this model to ask if and how: (a) feedbacks between vegetation and wildfire may modify fire activity on the landscape, and (b) more frequent fire may affect landscape forest composition and age structure. Both field and GIS data suggest the probability of fire is low in the initial decades after fire, supporting the hypothesis that fuel accumulation may exert a negative feedback on fire frequency. Field observations of pre‐ and postfire composition indicate that switches in forest state are more likely in conifer stands that burn at a young age, supporting the hypothesis that resilience is lower in immature stands. Stands dominated by deciduous trees or jack pine were generally resilient to fire, while mixed conifer and well‐drained spruce forests were less resilient. However, simulation modeling suggests increased fire activity may result in large changes in forest age structure and composition, despite the feedbacks between vegetation–fire likely to occur with increased fire activity.

Genetic variation in thyroid folliculogenesis influences susceptibility to hypothyroidism-induced hearing impairment - Amanda H. Mortensen; Qing Fang; Michelle T. Fleming; Thomas J. Jones; Alexandre Z. Daly; Kenneth R. Johnson; Sally A. Camper (Mammalian Genome, 2019)

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

The importance of environment and life stage on interpretation of silky shark relative abundance indices for the equatorial Pacific Ocean - Cleridy E. Lennert‐Cody; Shelley C. Clarke; Alexandre Aires‐da‐Silva; Mark N. Maunder; Peter J. S. Franks; Marlon Román; Arthur J. Miller; Mihoko Minami (Fisheries Oceanography, 2019)
Recent large fluctuations in an index of relative abundance for the silky shark in the eastern Pacific Ocean have called into question its reliability as a population indicator for management. To investigate whether these fluctuations were driven by environmental forcing rather than true changes in abundance, a Pacific‐wide approach was taken. Data collected by observers aboard purse‐seine vessels fishing in the equatorial Pacific were used to compute standardized trends in relative abundance by region, and where possible, by shark size category as a proxy for life stage. These indices were compared to the Pacific Decadal Oscillation ( PDO ), an index of Pacific Ocean climate variability. Correlation between silky indices and the PDO was found to differ by region and size category. The highest correlations by shark size category were for small ( TL ]) and medium (90–150 cm TL ) sharks from the western region of the equatorial eastern Pacific ( EP ) and from the equatorial western Pacific. This correlation disappeared in the inshore EP . Throughout, correlations with the PDO were generally lower for large silky sharks (>150 cm TL ). These results are suggestive of changes in the small and medium silky indices being driven by movement of juvenile silky sharks across the Pacific as the eastern edge of the Indo‐Pacific Warm Pool shifts location with ENSO events. Lower correlation of the PDO with large shark indices may indicate that those indices were less influenced by environmental forcing and therefore potentially less biased with respect to monitoring population trends.

Sphagnum Species Modulate their Phenolic Profiles and Mycorrhizal Colonization of Surrounding Andromeda polifolia along Peatland Microhabitats - Geneviève Chiapusio; Vincent E. J. Jassey; Floriant Bellvert; Gilles Comte; Leslie A. Weston; Frederic Delarue; Alexandre Buttler; Marie Laure Toussaint; Philippe Binet (Journal of Chemical Ecology, 2018)

Photoecology of the Antarctic cyanobacterium Leptolyngbya sp. BC1307 brought to light through community analysis, comparative genomics and in vitro photophysiology - Nathan A. M. Chrismas; Christopher J. Williamson; Marian L. Yallop; Alexandre M. Anesio; Patricia Sánchez‐Baracaldo (Molecular Ecology, 2018)
Cyanobacteria are important photoautotrophs in extreme environments such as the McMurdo Dry Valleys, Antarctica. Terrestrial Antarctic cyanobacteria experience constant darkness during the winter and constant light during the summer which influences the ability of these organisms to fix carbon over the course of an annual cycle. Here, we present a unique approach combining community structure, genomic and photophysiological analyses to understand adaptation to Antarctic light regimes in the cyanobacterium Leptolyngbya sp. BC1307. We show that Leptolyngbya sp. BC1307 belongs to a clade of cyanobacteria that inhabits near‐surface environments in the McMurdo Dry Valleys. Genomic analyses reveal that, unlike close relatives, Leptolyngbya sp. BC1307 lacks the genes necessary for production of the pigment phycoerythrin and is incapable of complimentary chromatic acclimation, while containing several genes responsible for known photoprotective pigments. Photophysiology experiments confirmed Leptolyngbya sp. BC1307 to be tolerant of short‐term exposure to high levels of photosynthetically active radiation, while sustained exposure reduced its capacity for photoprotection. As such, Leptolyngbya sp. BC1307 likely exploits low‐light microenvironments within cyanobacterial mats in the McMurdo Dry Valleys.

Ocean Solutions to Address Climate Change and Its Effects on Marine Ecosystems - Jean-Pierre Gattuso; Alexandre K. Magnan; Laurent Bopp; William W. L. Cheung; Carlos M. Duarte; Jochen Hinkel; Elizabeth Mcleod; Fiorenza Micheli; Andreas Oschlies; Phillip Williamson; Raphaël Billé; Vasiliki I. Chalastani; et al. (Frontiers in Marine Science, 2018)

Genetic drift and uniform selection shape evolution of most traits in Eugenia dysenterica DC. (Myrtaceae) - Carolina R. D. Boaventura-Novaes; Evandro Novaes; Elias E. S. Mota; Mariana P. C. Telles; Alexandre S. G. Coelho; Lázaro J. Chaves (Tree Genetics & Genomes, 2018)

Mapping of novel salt tolerance QTL in an Excalibur × Kukri doubled haploid wheat population - Muhammad A. Asif; Rhiannon K. Schilling; Joanne Tilbrook; Chris Brien; Kate Dowling; Huwaida Rabie; Laura Short; Christine Trittermann; Alexandre Garcia; Edward G. Barrett-Lennard; Bettina Berger; Diane E. Mather; et al. (Theoretical and Applied Genetics, 2018)
Key message Novel QTL for salinity tolerance traits have been detected using non-destructive and destructive phenotyping in bread wheat and were shown to be linked to improvements in yield in saline fields. Abstract Soil salinity is a major limitation to cereal production. Breeding new salt-tolerant cultivars has the potential to improve cereal crop yields. In this study, a doubled haploid bread wheat mapping population, derived from the bi-parental cross of Excalibur × Kukri, was grown in a glasshouse under control and salinity treatments and evaluated using high-throughput non-destructive imaging technology. Quantitative trait locus (QTL) analysis of this population detected multiple QTL under salt and control treatments. Of these, six QTL were detected in the salt treatment including one for maintenance of shoot growth under salinity ( QG (1 – 5) .asl - 7A ), one for leaf Na + exclusion ( QNa.asl - 7A ) and four for leaf K + accumulation ( QK.asl - 2B.1 , QK.asl - 2B.2 , QK.asl - 5A and QK:Na.asl - 6A ). The beneficial allele for QG (1 – 5) .asl - 7A (the maintenance of shoot growth under salinity) was present in six out of 44 mainly Australian bread and durum wheat cultivars. The effect of each QTL allele on grain yield was tested in a range of salinity concentrations at three field sites across 2 years. In six out of nine field trials with different levels of salinity stress, lines with alleles for Na + exclusion and/or K + maintenance at three QTL ( QNa.asl - 7A , QK.asl - 2B.2 and QK:Na.asl - 6A ) excluded more Na + or accumulated more K + compared to lines without these alleles. Importantly, the QK.asl - 2B.2 allele for higher K + accumulation was found to be associated with higher grain yield at all field sites. Several alleles at other QTL were associated with higher grain yields at selected field sites.

Vascular plant‐mediated controls on atmospheric carbon assimilation and peat carbon decomposition under climate change - Konstantin Gavazov; Remy Albrecht; Alexandre Buttler; Ellen Dorrepaal; Mark H. Garnett; Sebastien Gogo; Frank Hagedorn; Robert T. E. Mills; Bjorn J. M. Robroek; Luca Bragazza (Global Change Biology, 2018)
Climate change can alter peatland plant community composition by promoting the growth of vascular plants. How such vegetation change affects peatland carbon dynamics remains, however, unclear. In order to assess the effect of vegetation change on carbon uptake and release, we performed a vascular plant‐removal experiment in two Sphagnum ‐dominated peatlands that represent contrasting stages of natural vegetation succession along a climatic gradient. Periodic measurements of net ecosystem CO 2 exchange revealed that vascular plants play a crucial role in assuring the potential for net carbon uptake, particularly with a warmer climate. The presence of vascular plants, however, also increased ecosystem respiration, and by using the seasonal variation of respired CO 2 radiocarbon (bomb‐ 14 C) signature we demonstrate an enhanced heterotrophic decomposition of peat carbon due to rhizosphere priming. The observed rhizosphere priming of peat carbon decomposition was matched by more advanced humification of dissolved organic matter, which remained apparent beyond the plant growing season. Our results underline the relevance of rhizosphere priming in peatlands, especially when assessing the future carbon sink function of peatlands undergoing a shift in vegetation community composition in association with climate change.

Marine Biotechnology in Brazil: Recent Developments and Its Potential for Innovation - Fabiano Thompson; Ricardo Krüger; Cristiane C. Thompson; Roberto G. S. Berlinck; Ricardo Coutinho; Melissa F. Landell; Mauro Pavão; Paulo A. S. Mourão; Ana Salles; Naiane Negri; Fabyano A. C. Lopes; Vitor Freire; et al. (Frontiers in Marine Science, 2018)

Iriarteeae palms tracked the uplift of Andean Cordilleras - Christine D. Bacon; Francisco J. Velásquez‐Puentes; Carina Hoorn; Alexandre Antonelli (Journal of Biogeography, 2018)
Aim The high biodiversity of northern South America is unparalleled and includes several centres of diversity such as Amazonia, the Andes and the Chocó. Movement of lineages amongst and within these bioregions is thought to be rare, and the effect of those dispersals on the distribution, diversity, and community assembly remains poorly understood. Here we address these effects by studying divergence times, biogeographical history, and species diversification of the palm tribe Iriarteeae, an ecologically dominant forest component. Location Central and South America. Methods We developed a calibrated phylogeny and a spatially explicit diversification model that incorporates molecular and fossil data. In these analyses, we included a new fossil Iriartea species Gemmamonocolpites galeanoana , derived from new samples of Miocene deposits in western Amazonia. We also estimated the geographical range evolution of lineages and tested whether speciation and extinction rates were affected by dispersal events using a simulation approach in Cla SSE . Results Dispersal amongst bioregions was not evenly distributed across the topology. We found that Amazonian communities are overdispersed across the phylogeny, whereas Andean taxa are clustered. Dispersal events were associated with increases in species diversification and were concomitant with periods of Andean uplift. Migration into montane areas occurred several times from lowland Amazonian ancestors, and montane taxa subsequently recolonized the Amazonian bioregion. Main conclusions Our results suggest that the diversification of Iriarteeae palms closely followed the west‐to‐east surface uplift history of the Northern Andes. From an early, lowland Amazonian ancestor, the first diversification events took place in the earliest emerging mountain chain, the Western Cordillera. From there multiple range expansions followed eastwards and back into the lowlands. This study demonstrates how geological events within a single mountain range can affect the geographical expansion and diversification of lineages.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Jaguar movement database: a GPS‐based movement dataset of an apex predator in the Neotropics - Ronaldo G. Morato; Jeffrey J. Thompson; Agustin Paviolo; Jesus A. de La Torre; Fernando Lima; Roy T. McBride; Rogerio C. Paula; Laury Cullen; Leandro Silveira; Daniel L. Z. Kantek; Emiliano E. Ramalho; Louise Maranhão; et al. (Ecology, 2018)
The field of movement ecology has rapidly grown during the last decade, with important advancements in tracking devices and analytical tools that have provided unprecedented insights into where, when, and why species move across a landscape. Although there has been an increasing emphasis on making animal movement data publicly available, there has also been a conspicuous dearth in the availability of such data on large carnivores. Globally, large predators are of conservation concern. However, due to their secretive behavior and low densities, obtaining movement data on apex predators is expensive and logistically challenging. Consequently, the relatively small sample sizes typical of large carnivore movement studies may limit insights into the ecology and behavior of these elusive predators. The aim of this initiative is to make available to the conservation‐scientific community a dataset of 134,690 locations of jaguars ( Panthera onca ) collected from 117 individuals (54 males and 63 females) tracked by GPS technology. Individual jaguars were monitored in five different range countries representing a large portion of the species’ distribution. This dataset may be used to answer a variety of ecological questions including but not limited to: improved models of connectivity from local to continental scales; the use of natural or human‐modified landscapes by jaguars; movement behavior of jaguars in regions not represented in this dataset; intraspecific interactions; and predator‐prey interactions. In making our dataset publicly available, we hope to motivate other research groups to do the same in the near future. Specifically, we aim to help inform a better understanding of jaguar movement ecology with applications towards effective decision making and maximizing long‐term conservation efforts for this ecologically important species. There are no costs, copyright, or proprietary restrictions associated with this data set. When using this data set, please cite this article to recognize the effort involved in gathering and collating the data and the willingness of the authors to make it publicly available.

The Impact of Experimental Temperature and Water Level Manipulation on Carbon Dioxide Release in a Poor Fen in Northern Poland - Mateusz Samson; Sandra Słowińska; Michał Słowiński; Mariusz Lamentowicz; Jan Barabach; Kamila Harenda; Małgorzata Zielińska; Bjorn J. M. Robroek; Vincent E. J. Jassey; Alexandre Buttler; Bogdan H. Chojnicki (Wetlands, 2018)

Diagnosing drought using the downstreamness concept: the effect of reservoir networks on drought evolution - Pieter R. van Oel; Eduardo S. P. R. Martins; Alexandre C. Costa; Niko Wanders; Henny A. J. van Lanen (Hydrological Sciences Journal, 2018)

Breeding implications of drought stress under future climate for upland rice in Brazil - Julian Ramirez‐Villegas; Alexandre B. Heinemann; Adriano Pereira de Castro; Flávio Breseghello; Carlos Navarro‐Racines; Tao Li; Maria C. Rebolledo; Andrew J. Challinor (Global Change Biology, 2018)
Rice is the most important food crop in the developing world. For rice production systems to address the challenges of increasing demand and climate change, potential and on‐farm yield increases must be increased. Breeding is one of the main strategies toward such aim. Here, we hypothesize that climatic and atmospheric changes for the upland rice growing period in central Brazil are likely to alter environment groupings and drought stress patterns by 2050, leading to changing breeding targets during the 21st century. As a result of changes in drought stress frequency and intensity, we found reductions in productivity in the range of 200–600 kg/ha (up to 20%) and reductions in yield stability throughout virtually the entire upland rice growing area (except for the southeast). In the face of these changes, our crop simulation analysis suggests that the current strategy of the breeding program, which aims at achieving wide adaptation, should be adjusted. Based on the results for current and future climates, a weighted selection strategy for the three environmental groups that characterize the region is suggested. For the highly favorable environment ( HFE , 36%–41% growing area, depending on RCP ), selection should be done under both stress‐free and terminal stress conditions; for the favorable environment ( FE , 27%–40%), selection should aim at testing under reproductive and terminal stress, and for the least favorable environment ( LFE , 23%–27%), selection should be conducted for response to reproductive stress only and for the joint occurrence of reproductive and terminal stress. Even though there are differences in timing, it is noteworthy that stress levels are similar across environments, with 40%–60% of crop water demand unsatisfied. Efficient crop improvement targeted toward adaptive traits for drought tolerance will enhance upland rice crop system resilience under climate change.

A versatile method for the preparation of particle-loaded microbubbles for multimodality imaging and targeted drug delivery - Joshua Owen; Calum Crake; Jeong Yu Lee; Dario Carugo; Estelle Beguin; Alexandre A Khrapitchev; Richard J Browning; Nicola Sibson; Eleanor Stride (Drug Delivery and Translational Research, 2018)

Hepatitis C virus infection among illicit drug users in an archipelago of the Amazon - Fabricio Q. Silva; Francisco J. A. Santos; Andreia P. Andrade; Suzy D. B. Pacheco; Benedikt Fischer; João Renato R. Pinho; José Alexandre R. Lemos; Aldemir B. Oliveira-Filho (Archives of Virology, 2018)

Biodiversity and climate determine the functioning of Neotropical forests - Lourens Poorter; Masha T. van der Sande; Eric J. M. M. Arets; Nataly Ascarrunz; Brian Enquist; Bryan Finegan; Juan Carlos Licona; Miguel Martínez‐Ramos; Lucas Mazzei; Jorge A. Meave; Rodrigo Muñoz; Christopher J. Nytch; et al. (Global Ecology and Biogeography, 2018)

Vapor–pressure deficit and extreme climatic variables limit tree growth - Paula Sanginés de Cárcer; Yann Vitasse; Josep Peñuelas; Vincent E. J. Jassey; Alexandre Buttler; Constant Signarbieux (Global Change Biology, 2018)
Assessing the effect of global warming on forest growth requires a better understanding of species‐specific responses to climate change conditions. Norway spruce and European beech are among the dominant tree species in Europe and are largely used by the timber industry. Their sensitivity to changes in climate and extreme climatic events, however, endangers their future sustainability. Identifying the key climatic factors limiting their growth and survival is therefore crucial for assessing the responses of these two species to ongoing climate change. We studied the vulnerability of beech and spruce to warmer and drier conditions by transplanting saplings from the top to the bottom of an elevational gradient in the Jura Mountains in Switzerland. We (1) demonstrated that a longer growing season due to warming could not fully account for the positive growth responses, and the positive effect on sapling productivity was species‐dependent, (2) demonstrated that the contrasting growth responses of beech and spruce were mainly due to different sensitivities to elevated vapor–pressure deficits ( VPD ), (3) determined the species‐specific limits to VPD above which growth rate began to decline, and (4) demonstrated that models incorporating extreme climatic events could account for the response of growth to warming better than models using only average values. These results support that the sustainability of forest trees in the coming decades will depend on how extreme climatic events will change, irrespective of the overall warming trend.

Tipping point in plant–fungal interactions under severe drought causes abrupt rise in peatland ecosystem respiration - Vincent E. J. Jassey; Monika K. Reczuga; Małgorzata Zielińska; Sandra Słowińska; Bjorn J. M. Robroek; Pierre Mariotte; Christophe V. W. Seppey; Enrique Lara; Jan Barabach; Michał Słowiński; Luca Bragazza; Bogdan H. Chojnicki; et al. (Global Change Biology, 2018)
Ecosystems are increasingly prone to climate extremes, such as drought, with long‐lasting effects on both plant and soil communities and, subsequently, on carbon (C) cycling. However, recent studies underlined the strong variability in ecosystem's response to droughts, raising the issue of nonlinear responses in plant and soil communities. The conundrum is what causes ecosystems to shift in response to drought. Here, we investigated the response of plant and soil fungi to drought of different intensities using a water table gradient in peatlands—a major C sink ecosystem. Using moving window structural equation models, we show that substantial changes in ecosystem respiration, plant and soil fungal communities occurred when the water level fell below a tipping point of −24 cm. As a corollary, ecosystem respiration was the greatest when graminoids and saprotrophic fungi became prevalent as a response to the extreme drought. Graminoids indirectly influenced fungal functional composition and soil enzyme activities through their direct effect on dissolved organic matter quality, while saprotrophic fungi directly influenced soil enzyme activities. In turn, increasing enzyme activities promoted ecosystem respiration. We show that functional transitions in ecosystem respiration critically depend on the degree of response of graminoids and saprotrophic fungi to drought. Our results represent a major advance in understanding the nonlinear nature of ecosystem properties to drought and pave the way towards a truly mechanistic understanding of the effects of drought on ecosystem processes.

Evaluation of Possible Consequences of Zika Virus Infection in the Developing Nervous System - Lais Takata Walter; Guilherme Shigueto Vilar Higa; Juliane Midori Ikebara; Danila Vedovello; Felipe Scassi Salvador; Silvia Honda Takada; Erika Reime Kinjo; Benjamin J. Whalley; Márcia Aparecida Sperança; Alexandre Hiroaki Kihara (Molecular Neurobiology, 2018)

Food patterns and nutritional assessment in Galician university students - José J. Porto-Arias; Tania Lorenzo; Alexandre Lamas; Patricia Regal; Alejandra Cardelle-Cobas; Alberto Cepeda (Journal of Physiology and Biochemistry, 2018)

Variation in the composition and activity of ants on defense of host plant Turnera subulata (Turneraceae): strong response to simulated herbivore attacks and to herbivore’s baits - Nayara G. Cruz; Paulo F. Cristaldo; Leandro Bacci; Camilla S. Almeida; Gabriela P. Camacho; Alisson S. Santana; Efrem J. M. Ribeiro; Alexandre P. Oliveira; Abraão A. Santos; Ana P. A. Araújo (Arthropod-Plant Interactions, 2018)

ATLANTIC MAMMAL TRAITS : a data set of morphological traits of mammals in the Atlantic Forest of South America - Fernando Gonçalves; Ricardo S. Bovendorp; Gabrielle Beca; Carolina Bello; Raul Costa‐Pereira; Renata L. Muylaert; Raisa R. Rodarte; Nacho Villar; Rafael Souza; Maurício E. Graipel; Jorge J. Cherem; Deborah Faria; et al. (Ecology, 2018)
Measures of traits are the basis of functional biological diversity. Numerous works consider mean species‐level measures of traits while ignoring individual variance within species. However, there is a large amount of variation within species and it is increasingly apparent that it is important to consider trait variation not only between species, but also within species. Mammals are an interesting group for investigating trait‐based approaches because they play diverse and important ecological functions (e.g., pollination, seed dispersal, predation, grazing) that are correlated with functional traits. Here we compile a data set comprising morphological and life history information of 279 mammal species from 39,850 individuals of 388 populations ranging from −5.83 to −29.75 decimal degrees of latitude and −34.82 to −56.73 decimal degrees of longitude in the Atlantic forest of South America. We present trait information from 16,840 individuals of 181 species of non‐volant mammals (Rodentia, Didelphimorphia, Carnivora, Primates, Cingulata, Artiodactyla, Pilosa, Lagomorpha, Perissodactyla) and from 23,010 individuals of 98 species of volant mammals (Chiroptera). The traits reported include body mass, age, sex, reproductive stage, as well as the geographic coordinates of sampling for all taxa. Moreover, we gathered information on forearm length for bats and body length and tail length for rodents and marsupials. No copyright restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Analyzing community‐weighted trait means across environmental gradients: should phylogeny stay or should it go? - Leandro D. S. Duarte; Vanderlei J. Debastiani; Marcos B. Carlucci; José Alexandre F. Diniz‐Filho (Ecology, 2018)
Functional traits mediate ecological responses of organisms to the environment, determining community structure. Community‐weighted trait means ( CWM ) are often used to characterize communities by combining information on species traits and distribution. Relating CWM variation to environmental gradients allows for evaluating species sorting across the metacommunity, either based on correlation tests or ordinary least squares ( OLS ) models. Yet, it is not clear if phylogenetic signal in both traits and species distribution affect those analyses. On one hand, phylogenetic signal might indicate niche conservatism along clade evolution, reinforcing the environmental signal in trait assembly patterns. On the other hand, it might introduce phylogenetic autocorrelation to mean trait variation among communities. Under this latter scenario, phylogenetic signal might inflate type I error in analysis relating CWM variation to environmental gradients. We explore multiple ways phylogenetic history may influence analysis relating CWM to environmental gradients. We propose the concept of neutral trait diffusion, which predicts that for a functional trait x , CWM variation among local communities does not deviate from the expectation that x evolved according to a neutral evolutionary process. Based on this framework we introduce a graphical tool called neutral trait diffusion representation ( NTDR ) that allows for the evaluation of whether it is necessary to carry out phylogenetic correction in the trait prior to analyzing the association between CWM and environmental gradients. We illustrate the NTDR approach using simulated traits, phylogenies and metacommunities. We show that even under moderate phylogenetic signal in both the trait used to define CWM and species distribution across communities, OLS models relating CWM variation to environmental gradients lead to inflated type I error when testing the null hypothesis of no association between CWM and environmental gradient. To overcome this issue, we propose a phylogenetic correction for OLS models and evaluate its statistical performance (type I error and power). Phylogeny‐corrected OLS models successfully control for type I error in analysis relating CWM variation to environmental gradients but may show decreased power. Combining the exploratory tool of NTDR and phylogenetic correction in traits, when necessary, guarantees more precise inferences about the environmental forces driving trait‐mediated species sorting across metacommunities.

Assessment of wound healing of tagged gray ( Eschrichtius robustus ) and blue ( Balaenoptera musculus ) whales in the eastern North Pacific using long‐term series of photographs - Stephanie A. Norman; Kiirsten R. Flynn; Alexandre N. Zerbini; Frances M. D. Gulland; Michael J. Moore; Stephen Raverty; David S. Rotstein; Bruce R. Mate; Craig Hayslip; Diane Gendron; Richard Sears; Annie B. Douglas; et al. (Marine Mammal Science, 2018)
Tags have been used to examine migration routes and habitat use of large whales for >40 yr, however, evaluation of tag wound healing has largely been short‐term, anecdotal or generalized. This study developed methods for systematic photographic assessment of long‐term external consequences of tag placement, to determine potential differences in wound healing between species and tag types and thus advise future tagging efforts to possibly minimize undesirable side effects. Tag site appearance and healing characteristics were evaluated by two reviewers and a time series evaluated by five veterinarians from photographs during 995 postdeployment encounters with 34 gray and 63 blue whales tagged in the North Pacific. Blue whale resightings were less frequent, but spanned a longer time period due to earlier tag deployments than the more frequent gray whale follow‐up observations. Swelling occurred in 74% of reencountered gray whales, with the highest frequency 6 mo postdeployment. Swellings were common in blue whales with early tag designs but rare with current models. Depressions occurred in 82% of gray and 71% of blue whales. This study demonstrates the value of follow‐up studies of tagged animals and systematic scoring of photographs to quantitatively compare tag response.

Patterns, biases and prospects in the distribution and diversity of Neotropical snakes - Thaís B. Guedes; Ricardo J. Sawaya; Alexander Zizka; Shawn Laffan; Søren Faurby; R. Alexander Pyron; Renato S. Bérnils; Martin Jansen; Paulo Passos; Ana L. C. Prudente; Diego F. Cisneros‐Heredia; Henrique B. Braz; et al. (Global Ecology and Biogeography, 2018)
Motivation We generated a novel database of Neotropical snakes (one of the world's richest herpetofauna) combining the most comprehensive, manually compiled distribution dataset with publicly available data. We assess, for the first time, the diversity patterns for all Neotropical snakes as well as sampling density and sampling biases. Main types of variables contained We compiled three databases of species occurrences: a dataset downloaded from the Global Biodiversity Information Facility (GBIF), a verified dataset built through taxonomic work and specialized literature, and a combined dataset comprising a cleaned version of the GBIF dataset merged with the verified dataset. Spatial location and grain Neotropics, Behrmann projection equivalent to 1° × 1°. Time period Specimens housed in museums during the last 150 years. Major taxa studied Squamata: Serpentes. Software format Geographical information system (GIS). Results The combined dataset provides the most comprehensive distribution database for Neotropical snakes to date. It contains 147,515 records for 886 species across 12 families, representing 74% of all species of snakes, spanning 27 countries in the Americas. Species richness and phylogenetic diversity show overall similar patterns. Amazonia is the least sampled Neotropical region, whereas most well‐sampled sites are located near large universities and scientific collections. We provide a list and updated maps of geographical distribution of all snake species surveyed. Main conclusions The biodiversity metrics of Neotropical snakes reflect patterns previously documented for other vertebrates, suggesting that similar factors may determine the diversity of both ectothermic and endothermic animals. We suggest conservation strategies for high‐diversity areas and sampling efforts be directed towards Amazonia and poorly known species.

Route Fidelity during Marine Megafauna Migration - Travis W. Horton; Nan Hauser; Alexandre N. Zerbini; Malcolm P. Francis; Michael L. Domeier; Artur Andriolo; Daniel P. Costa; Patrick W. Robinson; Clinton A. J. Duffy; Nicole Nasby-Lucas; Richard N. Holdaway; Phillip J. Clapham (Frontiers in Marine Science, 2017)

Redescription of the blacktip sea catfish Plicofollis dussumieri (Valenciennes) (Siluriformes: Ariidae), with a new record from the Red Sea and notes on the diversity and distribution of Plicofollis spp. - Alexandre P. Marceniuk; Sergey V. Bogorodsky; Ahmad O. Mal; Tilman J. Alpermann (Marine Biodiversity, 2017)

Biodiversity and climate determine the functioning of Neotropical forests - Lourens Poorter; Masha T. van der Sande; Eric J. M. M. Arets; Nataly Ascarrunz; Brian J. Enquist; Bryan Finegan; Juan Carlos Licona; Miguel Martínez‐Ramos; Lucas Mazzei; Jorge A. Meave; Rodrigo Muñoz; Christopher J. Nytch; et al. (Global Ecology and Biogeography, 2017)
Aim Tropical forests account for a quarter of the global carbon storage and a third of the terrestrial productivity. Few studies have teased apart the relative importance of environmental factors and forest attributes for ecosystem functioning, especially for the tropics. This study aims to relate aboveground biomass (AGB) and biomass dynamics (i.e., net biomass productivity and its underlying demographic drivers: biomass recruitment, growth and mortality) to forest attributes (tree diversity, community‐mean traits and stand basal area) and environmental conditions (water availability, soil fertility and disturbance). Location Neotropics. Methods We used data from 26 sites, 201 1‐ha plots and >92,000 trees distributed across the Neotropics. We quantified for each site water availability and soil total exchangeable bases and for each plot three key community‐weighted mean functional traits that are important for biomass stocks and productivity. We used structural equation models to test the hypothesis that all drivers have independent, positive effects on biomass stocks and dynamics. Results Of the relationships analysed, vegetation attributes were more frequently associated significantly with biomass stocks and dynamics than environmental conditions (in 67 vs. 33% of the relationships). High climatic water availability increased biomass growth and stocks, light disturbance increased biomass growth, and soil bases had no effect. Rarefied tree species richness had consistent positive relationships with biomass stocks and dynamics, probably because of niche complementarity, but was not related to net biomass productivity. Community‐mean traits were good predictors of biomass stocks and dynamics. Main conclusions Water availability has a strong positive effect on biomass stocks and growth, and a future predicted increase in (atmospheric) drought might, therefore, potentially reduce carbon storage. Forest attributes, including species diversity and community‐weighted mean traits, have independent and important relationships with AGB stocks, dynamics and ecosystem functioning, not only in relatively simple temperate systems, but also in structurally complex hyper‐diverse tropical forests.

ATLANTIC ‐ CAMTRAPS : a dataset of medium and large terrestrial mammal communities in the Atlantic Forest of South America - Fernando Lima; Gabrielle Beca; Renata L. Muylaert; Clinton N. Jenkins; Miriam L. L. Perilli; Ana Maria O. Paschoal; Rodrigo L. Massara; Adriano P. Paglia; Adriano G. Chiarello; Maurício E. Graipel; Jorge J. Cherem; André L. Regolin; et al. (Ecology, 2017)
Our understanding of mammal ecology has always been hindered by the difficulties of observing species in closed tropical forests. Camera trapping has become a major advance for monitoring terrestrial mammals in biodiversity rich ecosystems. Here we compiled one of the largest datasets of inventories of terrestrial mammal communities for the Neotropical region based on camera trapping studies. The dataset comprises 170 surveys of medium to large terrestrial mammals using camera traps conducted in 144 areas by 74 studies, covering six vegetation types of tropical and subtropical Atlantic Forest of South America (Brazil and Argentina), and present data on species composition and richness. The complete dataset comprises 53,438 independent records of 83 species of mammals, includes 10 species of marsupials, 15 rodents, 20 carnivores, eight ungulates and six armadillos. Species richness averaged 13 species (±6.07 SD ) per site. Only six species occurred in more than 50% of the sites: the domestic dog Canis familiaris , crab‐eating fox Cerdocyon thous , tayra Eira barbara , south American coati Nasua nasua , crab‐eating raccoon Procyon cancrivorus and the nine‐banded armadillo Dasypus novemcinctus . The information contained in this dataset can be used to understand macroecological patterns of biodiversity, community, and population structure, but also to evaluate the ecological consequences of fragmentation, defaunation, and trophic interactions.

Response to Editor to the comment by Delarue (2016) to our paper entitled ‘Persistent high temperature and low precipitation reduce peat carbon accumulation’ - Luca Bragazza; Alexandre Buttler; Bjorn J. M. Robroek; Remy Albrecht; Claudio Zaccone; Vincent E. J. Jassey; Constant Signarbieux (Global Change Biology, 2017)

Evaluation of TMPA 3B42 Precipitation Estimates during the Passage of Tropical Cyclones over New Caledonia - Anil Deo; Kevin J. E. Walsh; Alexandre Peltier (Theoretical and Applied Climatology, 2017)

Alternatives to regular urea for abating N losses in lettuce production under sub-tropical climate - Rafael R. Cantú; Celso Aita; Alexandre Doneda; Diego A. Giacomini; Alexandre Dessbesell; Marlon Arenhardt; Géssica G. De Bastiani; Stefen B. Pujol; Philippe Rochette; Martin H. Chantigny; Sandro J. Giacomini (Biology and Fertility of Soils, 2017)

Tidal effects on phytoplankton assemblages in a near‐pristine estuary: a trait‐based approach for the case of a shallow tropical ecosystem in Brazil - Gleyci A. O. Moser; Fernanda Reinhardt Piedras; Anna Beatriz J. Oaquim; Daiana S. Souza; Suzana G. Leles; Domênica T. de Lima; Ana Beatriz A. Ramos; Cássia de O. Farias; Alexandre M. Fernandes (Marine Ecology, 2017)
The study of near‐pristine estuaries can be used as a tool for mitigation projects of harmful effects in anthropogenic eutrophic systems, since one can analyze the effect of temporal and spatial variations generated mainly by natural forces. Phytoplankton taxonomy has been used as a classical indicator to assess changes in transitional water communities, however alternative methods based on morphological, behavioral and physiological traits offer the opportunity to compare sites or moments with different taxonomic compositions. Our goal, in this context, is to evaluate phytoplankton community short‐term and seasonal variability in a near‐pristine estuary, Barra Grande estuary (Ilha Grande, RJ , Brazil), through species functional traits and thus community functional diversity. Samplings were carried out in a mooring in complete tidal cycles, seasonally during 2012. Our results showed a diverse phytoplankton community with 38 frequent and abundant taxa, marked by density variation (1.2 × 10.4–2 × 10.7 cell L −1 ) in depth, with abundance inversely related to tidal currents. The functional structure of the phytoplankton community measured by functional diversity ( FD ), varied seasonally in and across a gradient of tidal energy. A core community, mainly represented by flagellates and dinoflagellates, occurred in all observations and was highly functional (high FD ), exploiting a variety of habitats. The chain‐forming diatoms were associated with high tidal energy, and occurred in higher densities during summer. Phytoplankton cell size, cell shape, and the ability to form colonies are extremely plastic traits that can be regulated by the environment, however, isolated tychopelagic diatoms were present in the study area across all seasons, with higher contributions in autumn and winter, reflecting the shallow characteristic of this system. During the winter, an exposed sandbar was formed, and the lack of connection with the ocean resulted in an abundance of riverine and brackish water taxa. In this near‐pristine estuary the densities and occurrences of HAB phytoplankton are low. Trait‐based analyses add information about community structure, which can be impacted by anthropogenic actions in urbanized coastal systems. Thus the information provided by this study regarding phytoplankton functional diversity and its relation to nutrients and hydrography in Barra Grande Estuary can be applied as a baseline model for the development of public policies.

Effect of changes in the nutritional status on the performances of growing Creole kids during an established nematode parasite infection - W. Ceï; H. Archimède; R. Arquet; Y. Félicité; D. Feuillet; A. Nepos; P. Mulciba; T. Etienne; G. Alexandre; J. C. Bambou (Tropical Animal Health and Production, 2017)

Genome-wide meta-analyses of nonsyndromic orofacial clefts identify novel associations between FOXE1 and all orofacial clefts, and TP63 and cleft lip with or without cleft palate - Elizabeth J. Leslie; Jenna C. Carlson; John R. Shaffer; Azeez Butali; Carmen J. Buxó; Eduardo E. Castilla; Kaare Christensen; Fred W. B. Deleyiannis; L. Leigh Field; Jacqueline T. Hecht; Lina Moreno; Ieda M. Orioli; et al. (Human Genetics, 2017)

Insights into regional patterns of Amazonian forest structure, diversity, and dominance from three large terra-firme forest dynamics plots - Alvaro Duque; Helene C. Muller-Landau; Renato Valencia; Dairon Cardenas; Stuart Davies; Alexandre de Oliveira; Álvaro J. Pérez; Hugo Romero-Saltos; Alberto Vicentini (Biodiversity and Conservation, 2017)

A multicenter assessment of single-cell models aligned to standard measures of cell health for prediction of acute hepatotoxicity - Rowena L. Sison-Young; Volker M. Lauschke; Esther Johann; Eliane Alexandre; Sébastien Antherieu; Hélène Aerts; Helga H. J. Gerets; Gilles Labbe; Delphine Hoët; Martina Dorau; Christopher A. Schofield; Cerys A. Lovatt; et al. (Archives of Toxicology, 2017)

Cystic fibrosis in Afro-Brazilians: XK haplotypes analysis supports the European origin of p.F508del mutation - D. A. S. de Souza; F. R. Faucz; R. B. de Alexandre; M. A. Santana; E. L. S. de Souza; F. J. C. Reis; L. Pereira-Ferrari; V. S. Sotomaior; L. Culpi; J. A. Phillips; S. Raskin (Genetica, 2017)

Toxicity effect of graphene oxide on growth and photosynthetic pigment of the marine alga Picochlorum sp. during different growth stages - Layla J. Hazeem; Mohamed Bououdina; Etienne Dewailly; Christian Slomianny; Alexandre Barras; Yannick Coffinier; Sabine Szunerits; Rabah Boukherroub (Environmental Science and Pollution Research, 2017)

Abundance and distribution of cetaceans in the Gulf of Alaska - Brenda K. Rone; Alexandre N. Zerbini; Annie B. Douglas; David W. Weller; Phillip J. Clapham (Marine Biology, 2017)

Differential Impact of Acclimation and Acute Water Deprivation in the Expression of Key Transcription Factors in Soybean Roots - Fábia Guimarães-Dias; Anna C. Neves-Borges; Alessandra J. Conforte; Leonardo Giovanella-Kampmann; André V. J. Ferreira; Regina M. S. Amorim; Magda A. Benevent; Maria Eugênia Lisei de Sá; Rosilene O. Mesquita; Fabiana A. Rodrigues; Alexandre L. Nepomuceno; Eduardo Romano; et al. (Plant Molecular Biology Reporter, 2016)

A local-scale approach to estuarine flood risk management - Paula Freire; Alexandre O. Tavares; Luís Sá; Anabela Oliveira; André B. Fortunato; Pedro P. dos Santos; Ana Rilo; João L. Gomes; João Rogeiro; Rui Pablo; Pedro J. Pinto (Natural Hazards, 2016)

Heavy metal and PCB spatial distribution pattern in sediments within an urban catchment—contribution of historical pollution sources - Celia Dias-Ferreira; Rosinda L. Pato; Jorge B. Varejão; Alexandre O. Tavares; Antonio J. D. Ferreira (Journal of Soils and Sediments, 2016)

Peatland vascular plant functional types affect dissolved organic matter chemistry - Bjorn J. M. Robroek; Remy J. H. Albrecht; Samuel Hamard; Adrian Pulgarin; Luca Bragazza; Alexandre Buttler; Vincent EJ Jassey (Plant and Soil, 2016)

Treatment with Parkinsonia aculeata combats insulin resistance-induced oxidative stress through the increase in PPARγ/CuZn-SOD axis expression in diet-induced obesity mice - Tiago Gomes Araújo; Alexandre Gabarra Oliveira; Juliana Falcato Vecina; Rodrigo Miguel Marin; Eryvelton Souza Franco; Mario J. Abdalla Saad; Maria Bernadete de Sousa Maia (Molecular and Cellular Biochemistry, 2016)

Resource availability influences aggression and response to chemical cues in the Neotropical termite Nasutitermes aff. coxipoensis (Termitidae: Nasutitermitinae) - Paulo F. Cristaldo; Ana P. A. Araújo; Camilla S. Almeida; Nayara G. Cruz; Efrem J. M. Ribeiro; Marcos L. C. Rocha; Alisson S. Santana; Abraão A. Santos; Alexandre Passos; Og De Souza; Daniela F. Florencio (Behavioral Ecology and Sociobiology, 2016)

Benthic nitrogen regeneration, fixation, and denitrification in a temperate, eutrophic lake: Effects on the nitrogen budget and cyanobacteria blooms - Mark J. McCarthy; Wayne S. Gardner; Moritz F. Lehmann; Alexandre Guindon; David F. Bird (Limnology and Oceanography, 2016)
Nitrogen (N) transformations and fluxes at the sediment‐water interface (SWI) were measured in Missisquoi Bay, Lake Champlain, to clarify the role of N in cyanobacterial blooms in temperate, eutrophic lakes. N sources (e.g., N fixation and tributary inputs), sinks (e.g., denitrification/anammox), and internal “links” (e.g., dissimilatory reduction to ; DNRA) were evaluated at a river discharge (PRM) and in the central basin (MB). Sediments were a more effective sink at PRM than MB. Sediments at both sites were a net source to the water column, but DNRA was not a consistent regeneration pathway. Net N 2 production at PRM in summer reversed to net N 2 consumption/fixation in fall. MB sediments produced N 2 at lower rates than PRM; these rates also reversed late in the season. Denitrification was limited by , especially at MB, and anammox may have contributed up to 10% of total N 2 production. Sediment N 2 fixation occurred simultaneously with denitrification throughout the ice‐free season and, on average, compensated 25–30% of total microbial N losses. A bottom‐water hypoxia event at MB in early July 2009 altered the N cycle, with lower actual denitrification rates and higher effluxes (not from DNRA), while phosphorus (P) flux was unaffected. The hypoxia‐altered N transformation pathways enhanced N bioavailability (but not P) and may have contributed to a non‐N‐fixing cyanobacterial bloom ( Microcystis ) observed 5 d later. A preliminary N budget incorporating sediment and water column sources and sinks and external loads suggested an ecosystem‐wide N deficit.

Comparison of UV photolysis, nanofiltration, and their combination to remove hormones from a drinking water source and reduce endocrine disrupting activity - Sandra Sanches; Alexandre Rodrigues; Vitor V. Cardoso; Maria J. Benoliel; João G. Crespo; Vanessa J. Pereira (Environmental Science and Pollution Research, 2016)

Stresses and Displacements in Steel-Lined Pressure Tunnels and Shafts in Anisotropic Rock Under Quasi-Static Internal Water Pressure - Alexandre J. Pachoud; Anton J. Schleiss (Rock Mechanics and Rock Engineering, 2016)

Recreational Diver Behavior and Contacts with Benthic Organisms in the Abrolhos National Marine Park, Brazil - Vinicius J. Giglio; Osmar J. Luiz; Alexandre Schiavetti (Environmental Management, 2016)

Spatial autocorrelation analysis and ecological niche modelling allows inference of range dynamics driving the population genetic structure of a Neotropical savanna tree - José Alexandre F. Diniz‐Filho; Ana Clara O. F. Barbosa; Rosane G. Collevatti; Lázaro J. Chaves; Levi Carina Terribile; Matheus S. Lima‐Ribeiro; Mariana P. C. Telles (Journal of Biogeography, 2016)
Aim Spatial autocorrelation analysis of genetic diversity was combined with ecological niche modelling ( ENM ) to better infer how ecological and evolutionary processes underlie population structure in Eugenia dysenterica, a widely distributed tree in the ‘Cerrado’ region of Central Brazil. Location ‘Cerrado’ region, Central Brazil. Methods Data were derived from 11 microsatellite loci in 23 populations of E. dysenterica , totalling 249 allele frequencies. The expected heterozygosity ( He ) within populations and the first principal coordinates extracted from pairwise F ST and from the difference between R ST and F ST among populations were correlated with shifts in suitability from ENM . Frequencies were then analysed using a spatial autocorrelation analysis based on Moran's I and Mantel tests to contrast population differentiation for mean allele frequencies, allele size and shifts in suitability since the Last Glacial Maximum inferred from ENM . Results Spatial correlograms based on Moran's I and Mantel tests showed a linear decrease in autocorrelation with distance, which revealed north‐west–south‐east gradients in allele frequencies, genetic diversity and differences between R ST and F ST . These spatial patterns varied among loci and alleles, and the strongest spatial patterns were found for more common alleles with higher levels of differentiation among populations and for those correlated with shifts in ENM suitability. Main conclusions Current genetic diversity and population structure in E. dysenterica can be explained by geographical range shifts associated with Quaternary climate dynamics, thus demonstrating the value of applying spatial analyses to study the ecological and evolutionary processes underlying differentiation even within populations possessing a continuous distribution.

Modelling the regional variability of the probability of high trihalomethane occurrence in municipal drinking water - Geneviève Cool; Alexandre Lebel; Rehan Sadiq; Manuel J. Rodriguez (Environmental Monitoring and Assessment, 2015)

Antibacterial activity of basil essential oil (Ocimum basilicum L.) in Italian-type sausage - Iloir Gaio; Adriana G. Saggiorato; Helen Treichel; Alexandre J. Cichoski; Viviane Astolfi; Rafael I. Cardoso; Geciane Toniazzo; Eunice Valduga; Natalia Paroul; Rogério L. Cansian (Journal of Consumer Protection and Food Safety, 2015)

Dietary Reliance on Benthic Primary Production as a Predictor of Mercury Accumulation in Freshwater Fish and Turtles - Julie L. Châteauvert; Gregory Bulté; Alexandre J. Poulain; Linda M. Campbell; Gabriel Blouin-Demers (Water, Air, & Soil Pollution, 2015)

Is the meiofauna a good indicator for climate change and anthropogenic impacts? - Daniela Zeppilli; Jozée Sarrazin; Daniel Leduc; Pedro Martinez Arbizu; Diego Fontaneto; Christophe Fontanier; Andrew J. Gooday; Reinhardt Møbjerg Kristensen; Viatcheslav N. Ivanenko; Martin V. Sørensen; Ann Vanreusel; Julien Thébault; et al. (Marine Biodiversity, 2015)

Heat stress during the Black Saturday event in Melbourne, Australia - Stephanie J. Jacobs; Timo Vihma; Alexandre B. Pezza (International Journal of Biometeorology, 2015)

Are social aggregation and temporary immigration driving high rates of increase in some Southern Hemisphere humpback whale populations? - Phillip J. Clapham; Alexandre N. Zerbini (Marine Biology, 2015)

Energy acquisition and allocation to egg production in relation to fish reproductive strategies - Richard S McBride; Stylianos Somarakis; Gary R Fitzhugh; Anu Albert; Nathalia A Yaragina; Mark J Wuenschel; Alexandre Alonso‐Fernández; Gualtiero Basilone (Fish and Fisheries, 2015)
Oogenesis in fishes follows a universal plan; yet, due to differences in the synchrony and rate of egg development, spawning frequency varies from daily to once in a lifetime. Some species spawn and feed in separate areas, during different seasons, by storing energy and drawing on it later for reproduction (i.e. capital breeding). Other species spawn using energy acquired locally, throughout a prolonged spawning season, allocating energy directly to reproduction (i.e. income breeding). Capital breeders tend to ovulate all at once and are more likely to be distributed at boreal latitudes. Income breeding allows small fish to overcome allometric constraints on egg production. Income breeders can recover more quickly when good‐feeding conditions are re‐established, which is a benefit to adults regarding bet‐hedging spawning strategies. Many species exhibit mixed capital‐ and income‐breeding patterns. An individual's position along this capital–income continuum may shift with ontogeny or in relation to environmental conditions, so breeding patterns are a conditional reproductive strategy. Poor‐feeding environments can lead to delayed maturation, skipped spawning, fewer spawning events per season or fewer eggs produced per event. In a few cases, variations in feeding environments appear to affect recruitment variability. These flexible processes of energy acquisition and allocation allow females to prioritize their own condition over their propagules' condition at any given spawning opportunity, thereby investing energy cautiously to maximize lifetime reproductive value. These findings have implications for temporal and spatial sampling designs, for measurement and interpretation of fecundity, and for interpreting fishery and ecosystem assessments.

Effects of enamel matrix genes on dental caries are moderated by fluoride exposures - John R. Shaffer; Jenna C. Carlson; Brooklyn O. C. Stanley; Eleanor Feingold; Margaret Cooper; Michael M. Vanyukov; Brion S. Maher; Rebecca L. Slayton; Marcia C. Willing; Steven E. Reis; Daniel W. McNeil; Richard J. Crout; et al. (Human Genetics, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Trophic ecology of dusky grouper Epinephelus marginatus (Actinopterygii, Epinephelidae) in littoral and neritic habitats of southern Brazil as elucidated by stomach contents and stable isotope analyses - Mario V. Condini; David J. Hoeinghaus; Alexandre M. Garcia (Hydrobiologia, 2015)

Ecological determinants of methylmercury bioaccumulation in benthic invertebrates of polar desert lakes - John Chételat; Alexandre J. Poulain; Marc Amyot; Louise Cloutier; Holger Hintelmann (Polar Biology, 2014)

Process-based modelling of erosion, sediment transport and reservoir siltation in mesoscale semi-arid catchments - Axel Bronstert; José-Carlos de Araújo; Ramon J. Batalla; Alexandre Cunha Costa; José Miguel Delgado; Till Francke; Saskia Foerster; Andreas Guentner; José Andrés López-Tarazón; George Leite Mamede; Pedro Henrique Medeiros; Eva Mueller; et al. (Journal of Soils and Sediments, 2014)

Detecting ecological groups from traits: a classification of subtropical tree species based on ecological strategies - Alexandre F. Souza; Cristiane Forgiarini; Solon J. Longhi; Juliano M. Oliveira (Brazilian Journal of Botany, 2014)

Indirect effects of experimental warming on dissolved organic carbon content in subsurface peat - Frédéric Delarue; Sébastien Gogo; Alexandre Buttler; Luca Bragazza; Vincent E. J. Jassey; Grégory Bernard; Fatima Laggoun-Défarge (Journal of Soils and Sediments, 2014)

Wolbachia do not live by reproductive manipulation alone: infection polymorphism in Drosophila suzukii and D. subpulchrella - Christopher A. Hamm; David J. Begun; Alexandre Vo; Chris C. R. Smith; Perot Saelao; Amanda O. Shaver; John Jaenike; Michael Turelli (Molecular Ecology, 2014)
Drosophila suzukii recently invaded North America and Europe. Populations in Hawaii, California, New York and Nova Scotia are polymorphic for Wolbachia , typically with Wolbachia in D. suzukii , denoted w S uz, is closely related to w R i, the variant prevalent in continental populations of D. simulans . w S uz is also nearly identical to Wolbachia found in D. subpulchrella , plausibly D. suzukii 's sister species. This suggests vertical Wolbachia transmission through cladogenesis (‘cladogenic transmission’). The widespread occurrence of 7–20% infection frequencies indicates a stable polymorphism. w S uz is imperfectly maternally transmitted, with wild infected females producing on average 5–10% uninfected progeny. As expected from its low frequency, w S uz produces no cytoplasmic incompatibility (CI), that is, no increased embryo mortality when infected males mate with uninfected females, and no appreciable sex‐ratio distortion. The persistence of w S uz despite imperfect maternal transmission suggests positive fitness effects. Assuming a balance between selection and imperfect transmission, we expect a fitness advantage on the order of 20%. Unexpectedly, Wolbachia ‐infected females produce fewer progeny than do uninfected females. We do not yet understand the maintenance of w S uz in D. suzukii . The absence of detectable CI in D. suzukii and D. subpulchrella makes it unlikely that CI‐based mechanisms could be used to control this species without transinfection using novel Wolbachia . Contrary to their reputation as horizontally transmitted reproductive parasites, many Wolbachia infections are acquired through introgression or cladogenesis and many cause no appreciable reproductive manipulation. Such infections, likely to be mutualistic, may be central to understanding the pervasiveness of Wolbachia among arthropods.

Science into policy; improving uptake and adoption of research: outcomes and conclusions - Paul De Barro; Stephen Goldson; Detlef Bartsch; Mikael Hirsch; Martyn Jeggo; John W. Lowenthal; Philip Macdonald; Ryan R. J. McAllister; Rod McCrea; Fiona McFarlane; Cathy Robinson; Kim Ritman; et al. (Journal of Consumer Protection and Food Safety, 2014)

Dampening prey cycle overrides the impact of climate change on predator population dynamics: a long‐term demographic study on tawny owls - Alexandre Millon; Steve J. Petty; Brian Little; Olivier Gimenez; Thomas Cornulier; Xavier Lambin (Global Change Biology, 2014)

A new ‘bio-comfort’ perspective for Melbourne based on heat stress, air pollution and pollen - Stephanie J. Jacobs; Alexandre B. Pezza; Vaughan Barras; John Bye (International Journal of Biometeorology, 2014)

Weighted estimate of extreme quantile: an application to the estimation of high flood return periods - Alexandre Lekina; Fateh Chebana; Taha B. M. J. Ouarda (Stochastic Environmental Research and Risk Assessment, 2014)

G2/M cell cycle arrest by an N-acetyl-D-glucosamine specific lectin from Psathyrella asperospora - Razina Rouf; Alexandre S. Stephens; Lina Spaan; Nadia X. Arndt; Christopher J. Day; Tom W. May; Evelin Tiralongo; Joe Tiralongo (Glycoconjugate Journal, 2014)

Resource partitioning among cladocerans in a littoral macrophyte zone: implications for the transfer of essential compounds - Hélène Masclaux; Gilles Bourdier; Pascal Riera; Martin J. Kainz; Lionel Jouve; Emilie Duffaud; Alexandre Bec (Aquatic Sciences, 2014)

Snow cover manipulation effects on microbial community structure and soil chemistry in a mountain bog - Bjorn J. M. Robroek; Amber Heijboer; Vincent E. J. Jassey; Mariet M. Hefting; T. Gerrit Rouwenhorst; Alexandre Buttler; Luca Bragazza (Plant and Soil, 2013)

A steroidal molecule present in the egg wax of the tick R hipicephalus ( B oophilus ) microplus inhibits bacterial biofilms - Karine R. Zimmer; Alexandre J. Macedo; Raquel B. Giordani; Jordan M. Conceição; Gianlucca G. Nicastro; Ana Laura Boechat; Regina L. Baldini; Wolf‐Rainer Abraham; Carlos Termignoni (Environmental Microbiology, 2013)
Summary The cattle tick R hipicephalus ( B oophilus) microplus lays eggs in the soil near the roots of grass, or in similar highly moist environments that are prone to biofilm formation. Tick eggs have a protective wax coating that may be a source of nutrients for microorganisms. However, as the eggs remain viable and show no visible signs of microbial colonization, we hypothesized that the coating might have anti‐biofilm properties. We show here that the coating inhibits biofilm formation by both G ram‐negative and G ram‐positive bacteria, though by different mechanisms. We have identified the anti‐biofilm molecule as N ‐(3‐sulfooxy‐25‐cholest‐5‐en‐26‐oyl)‐ L ‐isoleucine (boophiline), and we show that it inhibits the expression of fliC (flagellin) and cdrA (biofilm scaffold), whose products are necessary for biofilm formation in P seudomonas aeruginosa . Boophiline is a novel biofilm inhibitor being also effective against S taphylococcus epidermidis biofilm. In our study we show evidences of the boophiline mode of action in the protection of arthropod eggs against biofilm colonization.

The influence of litter quality on the relationship between vegetation and below-ground compartments: a Procrustean approach - Francy J. G. Lisboa; Guilherme M. Chaer; Ederson da C. Jesus; Sérgio M. de Faria; Fernando S. Gonçalves; Felipe M. Santos; Alexandre F. Castilho; Ricardo L. L. Berbara (Plant and Soil, 2013)

Horse-like walking, trotting, and galloping derived from kinematic Motion Primitives (kMPs) and their application to walk/trot transitions in a compliant quadruped robot - Federico L. Moro; Alexander Spröwitz; Alexandre Tuleu; Massimo Vespignani; Nikos G. Tsagarakis; Auke J. Ijspeert; Darwin G. Caldwell (Biological Cybernetics, 2013)

The SHARE European Earthquake Catalogue (SHEEC) 1000–1899 - M. Stucchi; A. Rovida; A. A. Gomez Capera; P. Alexandre; T. Camelbeeck; M. B. Demircioglu; P. Gasperini; V. Kouskouna; R. M. W. Musson; M. Radulian; K. Sesetyan; S. Vilanova; et al. (Journal of Seismology, 2013)

Anti-inflammatory and anti-arthritic activities of 3,4-dihydro-2,2-dimethyl-2H-naphthol[1,2-b]pyran-5,6-dione (β-lapachone) - Marília Maria Sitônio; Carlson H. R. de Carvalho Júnior; Ingrid de A. Campos; José Bruno Nunes Ferreira Silva; Maria do Carmo Alves de Lima; Alexandre J. S. Góes; Maria Bernadete Sousa Maia; Pedro J. Rolim Neto; Teresinha G. Silva (Inflammation Research, 2013)

Geographical gradients in the genome size variation of wild coffee trees (Coffea) native to Africa and Indian Ocean islands - Norosoa J. Razafinarivo; Jean-Jacques Rakotomalala; Spencer C. Brown; Mickael Bourge; Serge Hamon; Alexandre de Kochko; Valérie Poncet; Christine Dubreuil-Tranchant; Emmanuel Couturon; Romain Guyot; Perla Hamon (Tree Genetics & Genomes, 2012)

Methanogenic potential of Arctic and Antarctic subglacial environments with contrasting organic carbon sources - Marek Stibal; Jemma L. Wadham; Grzegorz P. Lis; Jon Telling; Richard D. Pancost; Ashley Dubnick; Martin J. Sharp; Emily C. Lawson; Catriona E. H. Butler; Fariha Hasan; Martyn Tranter; Alexandre M. Anesio (Global Change Biology, 2012)
Subglacial environments are largely anoxic, contain organic carbon ( OC ) overridden by glacier ice during periods of advance, and harbour active microbial communities. This creates favourable conditions for OC degradation via methanogenesis. It has been hypothesized that OC beneath ice sheets is converted to methane ( CH 4 ) and may be released to the atmosphere during retreat. However, there are limited data available to support this contention. Here, we present new data on the abundance, diversity and activity of methanogenic archaea and the amount and character of OC in subglacial sediments from Arctic and Antarctic glacial systems based on different substrate types. We employed long‐term laboratory incubations to quantify the CH 4 production potential in different subglacial settings. Significant numbers of methanogens (up to 7 × 10 4 cells g −1 ) were detected in the samples and clones of Methanomicrobiales and Methanosarcinales were identified in clone libraries. Long lag periods (up to >200 days) were observed before significant CH 4 concentrations were measured. We report order of magnitude differences in rates of CH 4 production (10 1 –10 5 fmol g −1 d −1 ) in different subglacial sediments, reflecting contrasts in the origin of the sediment and the OC character. Hence, we predict that contrasting rates of CH 4 production are likely to occur beneath glaciers and ice sheets that overran different types of substrate. We subsequently estimated the potential for CH 4 production beneath the Laurentide/Inuitian/Cordilleran and Fennoscandian Ice Sheets during a typical 85 ka Quaternary glacial/interglacial cycle. CH 4 production from lacustrine‐derived OC is likely to be an order of magnitude higher (~6.3–27 Pg C) than that from overridden soils (~0.55–0.68 Pg C), possibly due to a difference in lability between lacustrine and soil OC . While representing a fraction of the entire OC pool (~418–610 Pg C), this finding highlights the importance of considering the character of different OC pools when calculating subglacial CH 4 production.

Endo-xylanase GH11 activation by the fungal metabolite eugenitin - Willian J. Andrioli; André R. L. Damásio; Tony M. Silva; Vinícius B. da Silva; Alexandre Maller; N. P. D. Nanayakkara; Carlos H. T. P. Silva; Maria L. T. M. Polizeli; Jairo K. Bastos (Biotechnology Letters, 2012)

Global transcriptional analysis of primitive thymocytes reveals accelerated dynamics of T cell specification in fetal stages - Nikolai N. Belyaev; Judit Biró; Dimitrios Athanasakis; Delmiro Fernandez-Reyes; Alexandre J. Potocnik (Immunogenetics, 2012)

Secondary metabolites isolated from Piper chimonantifolium and their antifungal activity - João Henrique G. Lago; Alexandre T. Ito; César M. Fernandes; Maria Claudia M. Young; Massuo J. Kato (Natural Product Research, 2012)

Integrating biogeographical processes and local community assembly - Joaquín Hortal; Paulo De Marco Jr; Ana M. C. Santos; J . Alexandre F. Diniz‐Filho (Journal of Biogeography, 2012)

Prokaryotic diversity in sediments beneath two polar glaciers with contrasting organic carbon substrates - Marek Stibal; Fariha Hasan; Jemma L. Wadham; Martin J. Sharp; Alexandre M. Anesio (Extremophiles, 2012)

Host and habitat specialization of avian malaria in Africa - CLAIRE LOISEAU; RYAN J. HARRIGAN; ALEXANDRE ROBERT; RAURI C. K. BOWIE; HENRI A. THOMASSEN; THOMAS B. SMITH; RAVINDER N. M. SEHGAL (Molecular Ecology, 2012)
Studies of both vertebrates and invertebrates have suggested that specialists, as compared to generalists, are likely to suffer more serious declines in response to environmental change. Less is known about the effects of environmental conditions on specialist versus generalist parasites. Here, we study the evolutionary strategies of malaria parasites ( Plasmodium spp.) among different bird host communities. We determined the parasite diversity and prevalence of avian malaria in three bird communities in the lowland forests in Cameroon, highland forests in East Africa and fynbos in South Africa. We calculated the host specificity index of parasites to examine the range of hosts parasitized as a function of the habitat and investigated the phylogenetic relationships of parasites. First, using phylogenetic and ancestral reconstruction analyses, we found an evolutionary tendency for generalist malaria parasites to become specialists. The transition rate at which generalists become specialists was nearly four times as great as the rate at which specialists become generalists. We also found more specialist parasites and greater parasite diversity in African lowland rainforests as compared to the more climatically variable habitats of the fynbos and the highland forests. Thus, with environmental changes, we anticipate a change in the distribution of both specialist and generalist parasites with potential impacts on bird communities.

Experimental climate effect on seasonal variability of polyphenol/phenoloxidase interplay along a narrow fen–bog ecological gradient in Sphagnum fallax - VINCENT E. J. JASSEY; GENEVIÈVE CHIAPUSIO; DANIEL GILBERT; ALEXANDRE BUTTLER; MARIE‐LAURE TOUSSAINT; PHILIPPE BINET (Global Change Biology, 2011)
Extracellular phenoloxidase enzymes play an important role in the stability of soil carbon storage by contributing to the cycling of complex recalcitrant phenolic compounds. Climate warming could affect peatland functioning through an alteration of polyphenol/phenoloxidase interplay, which could lead them to becoming weaker sinks of carbon. Here, we assessed the seasonal variability of total phenolics and phenoloxidases subjected to 2–3 °C increase in air temperature using open‐top chambers. The measurements were performed along a narrow fen–bog ecological gradient over one growing season. Climate warming had a weak effect on phenoloxidases, but reduced phenolics in both fen and bog areas. Multivariate analyses revealed a split between the areas and also showed that climate warming exacerbated the seasonal variability of polyphenols, culminating in a destabilization of the carbon cycle. A negative relationship between polyphenols and phenoloxidases was recorded in controls and climate treatments suggesting an inhibitory effect of phenolics on phenoloxidases. Any significant decrease of phenolics through repeatedly elevated temperature would greatly impact the ecosystem functioning and carbon cycle through an alteration of the interaction of polyphenols with microbial communities and the production of extracellular enzymes. Our climate treatments did not have the same impact along the fen–bog gradient and suggested that not all the peatland habitats would respond similarly to climate forcing.

Dosage-dependent shift in the spore community of arbuscular mycorrhizal fungi following application of tannery sludge - André S. Nakatani; Denise L. C. Mescolotti; Marco A. Nogueira; Alexandre M. Martines; Marina Y. H. Miyauchi; Sidney L. Stürmer; Elke J. B. N. Cardoso (Mycorrhiza, 2011)

Detecting arthropod intraguild predation in the field - Alexandre Aebi; Peter M. J. Brown; Patrick De Clercq; Louis Hautier; Andy Howe; Brecht Ingels; Hans-Peter Ravn; John J. Sloggett; Renate Zindel; Alison Thomas (BioControl, 2011)

Two novel Ty1-copia retrotransposons isolated from coffee trees can effectively reveal evolutionary relationships in the Coffea genus (Rubiaceae) - Perla Hamon; Pierre-Olivier Duroy; Christine Dubreuil-Tranchant; Paulo Mafra D’Almeida Costa; Caroline Duret; Norosoa J. Razafinarivo; Emmanuel Couturon; Serge Hamon; Alexandre de Kochko; Valérie Poncet; Romain Guyot (Molecular Genetics and Genomics, 2011)

Linkage mapping of the Phg-1 and Co-1 4 genes for resistance to angular leaf spot and anthracnose in the common bean cultivar AND 277 - Maria Celeste Gonçalves-Vidigal; Anelise S. Cruz; Alexandre Garcia; J. Kami; Pedro S. Vidigal Filho; Lorenna L. Sousa; P. McClean; P. Gepts; M. A. Pastor-Corrales (Theoretical and Applied Genetics, 2011)

Vision in click beetles (Coleoptera: Elateridae): pigments and spectral correspondence between visual sensitivity and species bioluminescence emission - Abner B. Lall; Thomas W. Cronin; Alexandre A. Carvalho; John M. de Souza; Marcelo P. Barros; Cassius V. Stevani; Etelvino J. H. Bechara; Dora F. Ventura; Vadim R. Viviani; Avionne A. Hill (Journal of Comparative Physiology A, 2010)

Assessing plausible rates of population growth in humpback whales from life-history data - Alexandre N. Zerbini; Phillip J. Clapham; Paul R. Wade (Marine Biology, 2010)

A paradox revealed: karyotype evolution in the four-horned antelope occurs by tandem fusion (Mammalia, Bovidae, Tetracerus quadricornis) - Anne Ropiquet; Alexandre Hassanin; Eva Pagacova; Michèle Gerbault-Seureau; Halina Cernohorska; Svatka Kubickova; Céline Bonillo; Jiri Rubes; Terence J. Robinson (Chromosome Research, 2010)

A device to improve the Schleger and Turner method for sweating rate measurements - Alfredo Manuel Franco Pereira; Alexandre Alves; Paulo Infante; Evaldo A. L. Titto; Flávio Baccari; J. A. Afonso Almeida (International Journal of Biometeorology, 2010)

Ecological relationships between phytoplankton communities and different spatial scales in European reservoirs: implications at catchment level monitoring programmes - Edna Cabecinha; Paul J. Van den Brink; João Alexandre Cabral; Rui Cortes; Martinho Lourenço; Miguel Ângelo Pardal (Hydrobiologia, 2009)

Combined effects of food quality and temperature on somatic growth and reproduction of two freshwater cladocerans - HÉlène Masclaux; Alexandre Bec; Martin J. Kainz; Christian Desvilettes; Lionel Jouve; Gilles Bourdier (Limnology and Oceanography, 2009)
We investigated the effect of food quality on somatic growth and reproduction of zooplankton at different temperatures (12°C, 15°C, 20°C, and 25°C). Standardized growth experiments of two cladocerans, Daphnia magna and Simocephalus vetulus , were performed on (1) high‐quality food ( Cryptomonas sp.), (2) relatively low‐quality food ( Scenedesmus obliquus ), and (3) intermediate‐quality food ( Cryptomonas : Scenedesmus mixture). Food quality constraints on somatic growth and reproduction of the two cladocerans decreased with increasing temperature. For D. magna and for S. vetulus , differences between clutch size and growth rate of individuals fed on the three food sources were highly pronounced when they were reared at 12°C and 15°C; however, such differences decreased at 20°C and were negligible at 25°C. Variations in food quality constraints with temperature can be explained by the variability of dietary polyunsaturated fatty acids, such as eicosapentaenoic acid and stearidonic acid requirements of these cladocerans. We conclude that dietary constraints exerted by food quality for zooplankton development vary as a function of different temperature conditions.

Cloud condensation nuclei from biomass burning during the Amazonian dry-to-wet transition season - Jorge Alberto Martins; Fábio Luiz T. Gonçalves; Carlos A. Morales; Gilberto F. Fisch; Francisco Geraldo M. Pinheiro; João Bosco V. Leal Júnior; Carlos J. Oliveira; Emerson M. Silva; José Carlos P. Oliveira; Alexandre A. Costa; Maria Assunção F. Silva Dias (Meteorology and Atmospheric Physics, 2009)

Travelling and hunting in a changing Arctic: assessing Inuit vulnerability to sea ice change in Igloolik, Nunavut - Gita J. Laidler; James D. Ford; William A. Gough; Theo Ikummaq; Alexandre S. Gagnon; Slawomir Kowal; Kevin Qrunnut; Celina Irngaut (Climatic Change, 2009)

Analyses of associations with asthma in four asthma population samples from Canada and Australia - Denise Daley; Mathieu Lemire; Loubna Akhabir; Moira Chan-Yeung; Jian Qing He; Treena McDonald; Andrew Sandford; Dorota Stefanowicz; Ben Tripp; David Zamar; Yohan Bosse; Vincent Ferretti; et al. (Human Genetics, 2009)

Identification of susceptibility genes for complex diseases using pooling-based genome-wide association scans - Yohan Bossé; François Bacot; Alexandre Montpetit; Johan Rung; Hui-Qi Qu; James C. Engert; Constantin Polychronakos; Thomas J. Hudson; Philippe Froguel; Robert Sladek; Martin Desrosiers (Human Genetics, 2009)

Record of feeding by humpback whales ( Megaptera novaeangliae ) in tropical waters off Brazil - Luiz Cláudio Pinto de Sá Alves; Artur Andriolo; Alexandre N. Zerbini; José Luís Altmayer Pizzorno; Phillip J. Clapham (Marine Mammal Science, 2009)

High microbial activity on glaciers: importance to the global carbon cycle - ALEXANDRE M. ANESIO; ANDREW J. HODSON; ANDREAS FRITZ; ROLAND PSENNER; BIRGIT SATTLER (Global Change Biology, 2009)
Cryoconite holes, which can cover 0.1–10% of the surface area of glaciers, are small, water‐filled depressions (typically In situ primary production and respiration in cryoconites during the summer is often comparable with that found in soils in warmer and nutrient richer regions. Considering only glacier areas outside Antarctica and a conservative average cryoconite distribution on glacial surfaces, we found that on a global basis cryoconite holes have the potential to fix as much as 64 Gg of carbon per year (i.e. 98 Gg of photosynthesis minus 34 Gg of community respiration). Most lakes and rivers are generally considered as heterotrophic systems, but our results suggest that glaciers, which contain 75% of the freshwater of the planet, are largely autotrophic systems.

Growth and carcass traits of Creole goats under different pre-weaning, fattening and slaughter conditions - L. Liméa; J. Gobardham; G. Gravillon; A. Nepos; G. Alexandre (Tropical Animal Health and Production, 2009)

Spatial species‐richness gradients across scales: a meta‐analysis - Richard Field; Bradford A. Hawkins; Howard V. Cornell; David J. Currie; J. Alexandre F. Diniz‐Filho; Jean‐François Guégan; Dawn M. Kaufman; Jeremy T. Kerr; Gary G. Mittelbach; Thierry Oberdorff; Eileen M. O’Brien; John R. G. Turner (Journal of Biogeography, 2009)
Aim We surveyed the empirical literature to determine how well six diversity hypotheses account for spatial patterns in species richness across varying scales of grain and extent. Location Worldwide. Methods We identified 393 analyses (‘cases’) in 297 publications meeting our criteria. These criteria included the requirement that more than one diversity hypothesis was tested for its relationship with species richness. We grouped variables representing the hypotheses into the following ‘correlate types’: climate/productivity, environmental heterogeneity, edaphics/nutrients, area, biotic interactions and dispersal/history (colonization limitation or other historical or evolutionary effect). For each case we determined the ‘primary’ variable: the one most strongly correlated with taxon richness. We defined ‘primacy’ as the proportion of cases in which each correlate type was represented by the primary variable, relative to the number of times it was studied. We tested for differences in both primacy and mean coefficient of determination of the primary variable between the hypotheses and between categories of five grouping variables: grain, extent, taxon (animal vs. plant), habitat medium (land vs. water) and insularity (insular vs. connected). Results Climate/productivity had the highest overall primacy, and environmental heterogeneity and dispersal/history had the lowest. Primacy of climate/productivity was much higher in large‐grain and large‐extent studies than at smaller scales. It was also higher on land than in water, and much higher in connected systems than in insular ones. For other hypotheses, differences were less pronounced. Throughout, studies on plants and animals showed similar patterns. Coefficients of determination of the primary variables differed little between hypotheses and across the grouping variables, the strongest effects being low means in the smallest grain class and for edaphics/nutrients variables, and a higher mean for water than for land in connected systems but vice versa in insular systems. We highlight areas of data deficiency. Main conclusions Our results support the notion that climate and productivity play an important role in determining species richness at large scales, particularly for non‐insular, terrestrial habitats. At smaller extents and grain sizes, the primacy of the different types of correlates appears to differ little from null expectation. In our analysis, dispersal/history is rarely the best correlate of species richness, but this may reflect the difficulty of incorporating historical factors into regression models, and the collinearity between past and current climates. Our findings are consistent with the view that climate determines the capacity for species richness. However, its influence is less evident at smaller spatial scales, probably because (1) studies small in extent tend to sample little climatic range, and (2) at large grains some other influences on richness tend to vary mainly within the sampling unit.

Generation and characterization of recombinant feline β-galactosidase for preclinical enzyme replacement therapy studies in GM1 gangliosidosis - Tatiana I. Samoylova; Douglas R. Martin; Nancy E. Morrison; Misako Hwang; Anna M. Cochran; Alexandre M. Samoylov; Henry J. Baker; Nancy R. Cox (Metabolic Brain Disease, 2008)

Germ-line DNA copy number variation frequencies in a large North American population - George Zogopoulos; Kevin C. H. Ha; Faisal Naqib; Sara Moore; Hyeja Kim; Alexandre Montpetit; Frederick Robidoux; Philippe Laflamme; Michelle Cotterchio; Celia Greenwood; Stephen W. Scherer; Brent Zanke; et al. (Human Genetics, 2007)

Ultradian cycles in mice: definitions and links with REMS and NREMS - O. Le Bon; D. Popa; E. Streel; C. Alexandre; C. Lena; P. Linkowski; J. Adrien (Journal of Comparative Physiology A, 2007)

The issue of outwelling in the Guadiana River estuary (Portugal): some findings and research suggestions in the context of recent evidence - Alexandre Moniz de Bettencourt; Luís S. Quaresma; Maria J. Lança (Hydrobiologia, 2007)

Widespread capacity to metabolize polychlorinated biphenyls by diverse microbial communities in soils with no significant exposure to PCB contamination - Alexandre J. Macedo; Kenneth N. Timmis; Wolf‐Rainer Abraham (Environmental Microbiology, 2007)
Summary The purpose of this work was to determine the extent of microbial metabolic potential for polychlorinated biphenyls (PCBs) in soils that have had no previous exposure to this class of xenobiotic pollutants. Soil and sediment samples of distinct characteristics from six sites in Germany were used to inoculate PCB oil (Aroclor 1242) microdroplets. All samples yielded multispecies biofilms, as revealed by single‐strand conformation polymorphism (SSCP) analyses of polymerase chain reaction (PCR) analysis of 16S rRNA genes, and sequence analysis of the main amplicons. Microbes representing 20 different operational taxonomic units (OTUs) were identified in the biofilms, but only a few were common to all biofilms, namely those closely related to Aquabacterium sp., Caulobacter sp., Imtechium assamiensis , Nevskia ramosa , Parvibaculum lavamentivorans and Burkholderia sp. The PCB biofilm communities were always distinct from control biofilms developing from the same samples in the absence of PCB. All PCB droplet‐grown biofilms degraded multiple PCB congeners but differed in the congener spectra they degraded. These findings reveal that microbial potential to degrade PCBs is widespread in soils that have not been subjected to PCB contamination, and that this potential is characteristic of consortia of very diverse phylogenetic composition.

Lack of evidence for effect modification by estrogen of association between body mass index and colorectal cancer risk among postmenopausal women - Yiting Wang; Eric J. Jacobs; Lauren R. Teras; Alexandre L. Pavluck; Carmen Rodriguez; Michael J. Thun; Eugenia E. Calle (Cancer Causes & Control, 2007)

Longitudinal range expansion and cryptic eastern species in the western Palaearctic oak gallwasp, Andricus coriarius - RICHARD J. CHALLIS; SERAP MUTUN; JOSE‐LUIS NIEVES‐ALDREY; SONJA PREUSS; ANTONIS ROKAS; ALEXANDRE AEBI; EBRAHIM SADEGHI; MAJID TAVAKOLI; GRAHAM N. STONE (Molecular Ecology, 2007)
The oak gallwasp Andricus coriarius is distributed across the Western Palaearctic from Morocco to Iran. It belongs to a clade of host‐alternating Andricus species that requires host oaks in two sections of Quercus subgenus Quercus to complete its lifecycle, a requirement that has restricted the historic distribution and dispersal of members of this clade. Here we present nuclear and mitochondrial sequence evidence from the entire geographic range of A. coriarius to investigate the genetic legacy of longitudinal range expansion. We show A. coriarius as currently understood to be para‐ or polyphyletic, with three evolutionarily independent (but partially sympatric) lineages that diverged c. 10 million years ago (mya). The similarities in gall structure that have justified recognition of single species to date thus represent either strong conservation of an ancestral state or striking convergence. All three lineages originated in areas to the east of Europe, underlining the significance of Turkey, Iran and the Levant as ‘cradles’ of gallwasp evolution. One of the three lineages gave rise to all European populations, and range expansion from a putative Eastern origin to the present distribution is predicted to have occurred around 1.6 mya.

Glycemic load, glycemic index, and carbohydrate intake in relation to pancreatic cancer risk in a large US cohort - Alpa V. Patel; Marjorie L. McCullough; Alexandre L. Pavluck; Eric J. Jacobs; Michael J. Thun; Eugenia E. Calle (Cancer Causes & Control, 2007)

Radiation and speciation of pelagic organisms during periods of global warming: the case of the common minke whale, Balaenoptera acutorostrata - LUIS A. PASTENE; MUTSUO GOTO; NAOHISA KANDA; ALEXANDRE N. ZERBINI; DAN KEREM; KAZUO WATANABE; YOSHITAKA BESSHO; MASAMI HASEGAWA; RASMUS NIELSEN; FINN LARSEN; PER J. PALSBØLL (Molecular Ecology, 2007)
How do populations of highly mobile species inhabiting open environments become reproductively isolated and evolve into new species? We test the hypothesis that elevated ocean‐surface temperatures can facilitate allopatry among pelagic populations and thus promote speciation. Oceanographic modelling has shown that increasing surface temperatures cause localization and reduction of upwelling, leading to fragmentation of feeding areas critical to pelagic species. We test our hypothesis by genetic analyses of populations of two closely related baleen whales, the Antarctic minke whale ( Balaenoptera bonaerensis ) and common minke whale ( Balaenoptera acutorostrata ) whose current distributions and migration patterns extent are largely determined by areas of consistent upwelling with high primary production. Phylogeographic and population genetic analyses of mitochondrial DNA control‐region nucleotide sequences collected from 467 whales sampled in four different ocean basins were employed to infer the evolutionary relationship among populations of B. acutorostrata by rooting an intraspecific phylogeny with a population of B. bonaerensis . Our findings suggest that the two species diverged in the Southern Hemisphere less than 5 million years ago (Ma). This estimate places the speciation event during a period of extended global warming in the Pliocene. We propose that elevated ocean temperatures in the period facilitated allopatric speciation by disrupting the continuous belt of upwelling maintained by the Antarctic Circumpolar Current. Our analyses revealed that the current populations of B. acutorostrata likely diverged after the Pliocene some 1.5 Ma when global temperatures had decreased and presumably coinciding with the re‐establishment of the polar–equatorial temperature gradient that ultimately drives upwelling. In most population samples, we detected genetic signatures of exponential population expansions, consistent with the notion of increasing carrying capacity after the Pliocene. Our hypothesis that prolonged periods of global warming facilitate speciation in pelagic marine species that depend on upwelling should be tested by comparative analyses in other pelagic species.

Ticks (Acari: Ixodidae) parasitizing humans in an Atlantic rainforest reserve of Southeastern Brazil with notes on host suitability - Matias P. J. Szabó; Marcelo B. Labruna; Karina C. Castagnolli; Marcos V. Garcia; Adriano Pinter; Viviane A. Veronez; Geórgia M. Magalhães; Márcio B. Castro; Alexandre Vogliotti (Experimental and Applied Acarology, 2006)

MTHFR (C677T and A1298C) Polymorphisms and Risk of Sporadic Distal Colorectal Adenoma in the UK Flexible Sigmoidoscopy Screening Trial (United Kingdom) - Panagiota N. Mitrou; Mark A. Watson; Alexandre S. Loktionov; Christopher Cardwell; Marc J. Gunter; Wendy S. Atkin; Christopher P. Macklin; Tom Cecil; Timothy D. Bishop; John Primrose; Sheila A. Bingham (Cancer Causes & Control, 2006)

Effects of copper on energy metabolism and larval development in the midge Chironomus riparius - María J. Servia; Alexandre R.R. Péry; Micheline Heydorff; Jeanne Garric; Laurent Lagadic (Ecotoxicology, 2006)

Spatial Variability of Irrigated Corn Yield in Relation to Field Topography and Soil Chemical Characteristics - J. R. Marques Da Silva; C. Alexandre (Precision Agriculture, 2005)

Macroecological correlates and spatial patterns of anuran description dates in the Brazilian Cerrado - José Alexandre F. Diniz‐Filho; Rogério Pereira Bastos; Thiago F. L. V. B. Rangel; Luis M. Bini; Priscilla Carvalho; Rodrigo J. Silva (Global Ecology and Biogeography, 2005)
Aim To quantify the relationship between the description dates of anuran species in the Brazilian Cerrado and some macroecological traits, and to verify the spatial patterns of average description dates and their correlation with human occupation and biodiversity knowledge. Location Brazilian Cerrado (South America). Methods The average date of description of 131 species of anurans found in 181 cells overlaying the Brazilian Cerrado was recorded. Description date was regressed across species on body size and geographical range size. Phylogenetic effects that could bias the significance tests of the multiple regression model of description dates on macroecological traits were taken into account using a phylogenetic subtraction method in which families and genera were classificatory factors in a nested two‐way analysis of variance ( anova ) model. We also conducted a spatial analysis of the average description date that was estimated for each cell. This cell‐based metric was regressed on human population size, the year of foundation of the municipalities and the number of inventories undertaken in each cell. The influence of spatial autocorrelation patterns was taken into account by using the geographically effective number of degrees of freedom. Results The number of new species being discovered in the Brazilian Cerrado has been increasing, especially over the last 50 years. Cross‐species analyses indicated that description dates were negatively correlated with body size and geographical range size, taking phylogenetic effects into account. Even after controlling for the spatial structures in all variables, average description date was positively correlated with human population in geographical space, but because of multicolinearity structure in the data, it was not possible to quantify the independent influence of human population and number of inventories on description date. Conclusions As found in previous papers, large‐bodied and widely distributed species are likely to be described first. Species yet to be discovered are probably small‐bodied and with narrow distributions, more restricted to the Cerrado biome. Also, the explicit spatial approach showed that the average description date is spatially correlated with total human population and biodiversity knowledge in the Cerrado region. Our findings suggest that incorporating human population density into the reserve design algorithms, which has usually been done to avoid or minimize conservation conflicts, may also produce good results because this will preserve many places where most of the non‐described species will probably be found in the future.

Evidence for a novel glaucoma locus at chromosome 3p21-22 - Paul N. Baird; Simon J. Foote; David A. Mackey; Jamie Craig; Terence P. Speed; Alexandre Bureau (Human Genetics, 2005)

Fourth meeting of the European Network of Research Tissue Banks – Future strategy to increase collaborations in the supply of human tissue for biomedical research - Samantha Orr; Eliane Alexandre; Brian J Clark; Neil Gray; Heiki Helin; Rivka Ravid; Mel Read; Lysiane Richert; Retlav Roosipuu; Ann-Cathrine Jonsson-Rylander; Carina Syring; Tambet Teesalu; et al. (Cell and Tissue Banking, 2005)

Trace element partitioning and substitution mechanisms in calcium perovskites - Alexandre Corgne; Bernard J. Wood (Contributions to Mineralogy and Petrology, 2005)

Compositional effects on element partitioning between Mg-silicate perovskite and silicate melts - Christian Liebske; Alexandre Corgne; Daniel J. Frost; David C. Rubie; Bernard J. Wood (Contributions to Mineralogy and Petrology, 2005)

An atypical form of erythrokeratodermia variabilis maps to chromosome 7q22 - Thomas G. Saba; Alexandre Montpetit; Andrei Verner; Pierre Rioux; Thomas J. Hudson; Rgen Drouin; Christian A. Drouin (Human Genetics, 2005)

Book Review: Yoram Rubin, Applied Stochastic Hydrogeology, Oxford University Press, New York, NY, 2003, xix, 391 p. USD 115.00 (ISBN 0 19513 804 X) - Alexandre J. Desbarats (Transport in Porous Media, 2004)

Studies on endocytic mechanisms of the Menkes copper-translocating P-type ATPase (ATP7A; MNK) – Endocytosis of the Menkes protein - Cinnamon Lane; Michael J. Petris; Alexandre Benmerah; Mark Greenough; James Camakaris (BioMetals, 2004)

New affinity procedure for the isolation and further characterization of the blood group B specific lectin from the red marine alga Ptilota plumosa - Alexandre H. Sampaio; David J. Rogers; Clive J. Barwell; Silvana Saker-Sampaio; Kyria S. Nascimento; Celso S. Nagano; Wladimir R.L. Farias (Journal of Applied Phycology, 2002)

Influence of Pre-, Intra- and Post-Operative Parameters of Donor Liver on the Outcome of Isolated Human Hepatocytes - E. Alexandre; M. Cahn; C. Abadie-Viollon; N. Meyer; B. Heyd; G. Mantion; J. Cinqualbre; P. David; D. Jaeck; L. Richert (Cell and Tissue Banking, 2002)

An experimental study of element partitioning between magnetite, clinopyroxene and iron-bearing silicate liquids with particular emphasis on vanadium - Michael J. Toplis; Alexandre Corgne (Contributions to Mineralogy and Petrology, 2002)

The antidepressant-like effect induced by the sigma1 (σ1) receptor agonist igmesine involves modulation of intracellular calcium mobilization - Alexandre Urani; Pascal Romieu; Elodie Portales-Casamar; François J. Roman; Tangui Maurice (Psychopharmacology, 2002)

Characterization of the sugar-binding specificity of the toxic lectins isolated from Abrus pulchellus seeds - Marcio V. Ramos; Alexandre H. Sampaio; Benildo S. Cavada; Juan J. Calvete; Thalles B. Grangeiro; Henri Debray (Glycoconjugate Journal, 2001)

Effects of alprazolam on the acoustic startle response in humans - Antoni Rodríguez-Fornells; Jordi Riba; Alexandre Gironell; Jaume Kulisevsky; M. J. Barbanoj (Psychopharmacology, 1999)

A new isolation procedure and further characterisation of the lectin from the red marine alga Ptilota serrata - Alexandre H. Sampaio; David J. Rogers; Clive J. Barwell; Silvana Saker-Sampaio; Francisco H. F. Costa; Márcio V. Ramos (Journal of Applied Phycology, 1998)

Energy and substrate metabolism during a 42-day bed-rest in a head-down tilt position in humans - P. Ritz; K. J. Acheson; P. Gachon; L. Vico; J. J. Bernard; C. Alexandre; B. Beaufrre (European Journal of Applied Physiology, 1998)

Induction and inhibition of human lymphocyte transformation by the lectin from the red marine alga Amansia multifida - Hermenio C. Lima; Francisco H. F. Costa; Alexandre H. Sampaio; Samya A. Neves; Norma M. B. Benevides; Darlio I. A. Teixeira; David J. Rogers; Ana Lúcia P. Freitas (Journal of Applied Phycology, 1998)

Interactive effects of subanesthetic ketamine and subhypnotic lorazepam in humans - John H. Krystal; Laurence P. Karper; Alexandre Bennett; D. Cyril D'Souza; Anissa Abi-Dargham; Kristen Morrissey; Danielle Abi-Saab; J. Douglas Bremner; M. B. Bowers Jr.; Raymond F. Suckow; Philip Stetson; George R. Heninger; et al. (Psychopharmacology, 1998)

Homologous oxypiperidines as inhibitors of protein synthesis in vitro and ex vivo - Dmitrij A. Kuznetsov; Nikolay V. Zavijalov; Gennadij J. Kelman; Alexandre V. Govorkov (Archives of Toxicology, 1987)